negative electrode for electrochemical cells

By using sintered iron agglomerated particles and direct reduced iron (DRI) materials to construct composite metal electrodes, the problem of difficulty in achieving long-term energy storage in existing energy storage technologies is solved, and an efficient and stable long-term energy storage system is achieved.

CN112805851BActive Publication Date: 2025-03-18FORM ENERGY INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN201980063958.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-28
Filing Date
2019-07-26
Publication Date
2025-03-18
Estimated Expiration
2039-07-26

AI Technical Summary

Technical Problem

Existing energy storage technologies are difficult to achieve long-term and ultra-long-term (≥8 hours) energy storage systems, especially in terms of matching power generation and demand in the power grid.

Method used

A composite metal electrode consisting of sintered iron agglomerated particles, including metal agglomerated particles arranged in multiple layers, is used to treat the agglomerated particles by mechanical, chemical and thermal methods to improve their performance.

Benefits of technology

It realizes efficient operation of long-term energy storage systems, can maintain charge for at least 24 hours, and improves the energy density and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112805851B_ABST
    Figure CN112805851B_ABST
Patent Text Reader

Abstract

Multiple embodiments provide a battery, a large-capacity energy storage system including the battery, and / or a method of operating the large-capacity energy storage system including the battery. In multiple embodiments, the battery may include a first electrode, an electrolyte, and a second electrode, wherein one or both of the first electrode and the second electrode include direct reduced iron ("DRI"). In multiple embodiments, the DRI may be in the form of a pellet. In multiple embodiments, based on the total mass of the pellet, the pellet may include at least about 60% by weight of iron by elemental mass. In multiple embodiments, one or both of the first electrode and the second electrode include about 60% to about 90% iron and about 1% to about 40% of a component, the component including one or more materials selected from SiO2, Al2O3, MgO, CaO and TiO2.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims priority to U.S. Provisional Patent Application No. 62 / 711,253, entitled “Negative Electrode for Metal-Air Batteries,” filed on July 27, 2018, U.S. Provisional Patent Application No. 62 / 790,668, entitled “Negative Electrode for Metal-Air Batteries,” filed on January 10, 2019, and U.S. Provisional Patent Application No. 62 / 868,511, entitled “Negative Electrode for Metal-Air Batteries,” filed on June 28, 2019. The entire contents of all three applications are incorporated herein by reference for all purposes. Background Art

[0003] Energy storage technologies play an increasingly important role in the electric grid; at the most basic level, these storage benefits facilitate better matching of generation and demand on the grid. The services provided by energy storage devices are beneficial to the grid across multiple time scales (from milliseconds to years). Today, energy storage technologies exist that can support time scales from milliseconds to hours, but there is also a need for long-duration and ultra-long-duration (≥8 hours total) energy storage systems.

[0004] This background technology section is intended to introduce various aspects of the art that may be associated with embodiments of the present invention. Therefore, the foregoing discussion in this section provides a framework for a better understanding of the present invention and should not be regarded as an admission of prior art. Summary of the invention

[0005] Disclosed are materials, designs, and methods of fabrication of metal electrodes for electrochemical cells. In various embodiments, the negative electrode includes metal bodies arranged in one or more configurations, including multiple layers.

[0006] In various embodiments, the pellets may include one or more forms of iron, ranging from highly reduced (more metallic) iron to highly oxidized (more ionic) iron. In various embodiments, the pellets may include a variety of iron compounds, such as iron oxide, iron hydroxide, iron sulfide, or combinations thereof. In various embodiments, the pellets may include one or more secondary phases, such as silicon dioxide (SiO2) or silicates, calcium oxide (CaO), magnesium oxide (MgO), and the like.

[0007] In various embodiments, the pellets can be sintered iron agglomerates having a variety of different shapes. In various embodiments, the sintered iron agglomerated particles can be formed in a furnace, such as a continuous feed calciner, a batch feed calciner, a shaft furnace, a rotary calciner, a rotary hearth furnace, etc. In various embodiments, the pellets can include reduced and / or sintered iron-containing precursors in a form known to those skilled in the art, such as direct reduced iron (DRI) and / or its byproduct materials. Various embodiments can include treating the pellets, including DRI pellets, using mechanical methods, chemical methods, and / or thermal methods, and then introducing the pellets into an electrochemical cell.

[0008] In various embodiments, the negative electrode may be a composite metal electrode consisting of a mixture of spherical or substantially spherical metal pellets and a powdered metal raw material. In various embodiments, the powdered metal raw material may be wetted by an electrolyte. In various embodiments, the negative electrode may be composed of a mixture of iron ore (e.g., taconite, etc.) pellets and conductive DRI fines, sponge iron and / or atomized iron. "DRI fines" should be understood to mean particles that are smaller in size than DRI pellets but are produced simultaneously with DRI pellets, or particles produced from DRI pellets by crushing, processing, or thermal methods or chemical means.

[0009] In various embodiments, the negative electrode may include pellets that may be aggregated in an ordered array. In various embodiments, the pellets are packed in a bed such that macropores are created between two or more pellets that are in contact with each other. In various embodiments, the pellets may each include micropores. In various embodiments, the electrolyte may fill micropores or macropores, or flow through the interstitial space around the pellets comprising the electrode.

[0010] In various embodiments, the iron powder layer can form an interface between a pellet and a current collector of a negative electrode, wherein the negative electrode further comprises an iron powder layer configured to form an interface between the pellet and a current collector of an electrochemical cell.

[0011] Various embodiments may include systems and methods for monitoring the state of charge of a negative electrode including metal pellets arranged in one or more layers.

[0012] In various embodiments, the pellets can be synthesized in a first stage of a dual energy storage power plant and used in the negative electrode in a second stage of the dual energy storage power plant.

[0013] A plurality of embodiments may provide a battery comprising a first electrode, an electrolyte, and a second electrode, wherein one or both of the first electrode and the second electrode comprise direct reduced iron ("DRI"). In a plurality of embodiments, the DRI is in the form of pellets. In a plurality of embodiments, the pellets comprise at least about 60% by weight of iron by elemental mass, based on the total mass of the pellets. In a plurality of embodiments, the pellets comprise at least about 60% by weight of metallic iron based on the total mass of the pellets, the average particle size of the pellets being 4 mm to 20 mm, and the pellets accounting for at least 60% of the total mass of at least one of the first electrode and the second electrode. In a plurality of embodiments, the pellets comprise at least about 80% by weight of metallic iron based on the total mass of the pellets. In a plurality of embodiments, the pellets comprise from about 90% to about 98% by weight of metallic iron based on the total mass of the pellets. In a plurality of embodiments, the pellets are spherical, rod-shaped, disc-shaped, plate-shaped, briquette-shaped, or a combination thereof. In a plurality of embodiments, the pellets are briquette-shaped and comprise hot briquette iron. In various embodiments, the hot briquette iron blocks are formed from powdered iron fines or iron pellets. In various embodiments, the average length of the pellets ranges from about 10 mm to about 500 mm, the average width ranges from about 5 mm to about 250 mm, and the average height ranges from about 5 mm to about 200 mm. In various embodiments, the DRI comprises iron ore, direct reduction grade iron ore, reduced taconite, wüstite, magnetite, hematite, cementite, iron oxide, or any combination thereof. In various embodiments, the DRI comprises DRI fines or DRI powder. In various embodiments, the pellets have an average internal porosity ranging from about 10 volume % to about 90 volume %. In various embodiments, the pellets have an average internal porosity ranging from about 0.19 m 2 / g to about 18m 2 / g of average specific surface area. In various embodiments, the granules have a volume weighted average pore size ranging from 1 micron to 10 microns. In various embodiments, at least one of the first electrode and the second electrode has a thickness greater than 0.1 cm. In various embodiments, the granules are spherical and have an average diameter ranging from about 0.5 mm to about 10 cm. In various embodiments, based on the total weight of the granules, the granules include more than 0.5 wt % of a silicon dioxide-containing compound. In various embodiments, based on the total mass of the granules, the granules include about 1 wt % to about 5 wt % of a silicon dioxide-containing compound by elemental mass. In various embodiments, based on the total mass of the granules, the granules include about 1 wt % to about 25 wt % of a silicon dioxide-containing compound by elemental mass. In various embodiments, the filling rate of the granules in at least one of the first electrode and the second electrode is 30% to 74%. In various embodiments, the granules include: a primary phase comprising iron; and a second phase comprising silicon or another metal. In various embodiments, the granules include: a primary phase comprising iron; and a second phase comprising cementite. In various embodiments, the second phase comprises silica or a silicate. In various embodiments, the second phase comprises titanium, vanadium, manganese, magnesium, calcium, phosphorus, carbon, aluminum, zirconium, or any combination thereof. In various embodiments, at least one of the first electrode and the second electrode comprises a single layer of the granules or a multilayer of the granules. In various embodiments, the electrolyte penetrates between the granules. In various embodiments, the battery further comprises a current collector electrically connected to the granules. In various embodiments, the current collector contacts the lower surface of at least one of the first electrode and the second electrode, contacts the side surface of at least one of the first electrode and the second electrode, extends through at least one of the first electrode and the second electrode, or any combination of the above. In various embodiments, the granules are sintered iron agglomerated particles. In various embodiments, the sintered iron agglomerated particles are made using a continuous feed calciner, a batch calciner, a shaft furnace, or any other type of furnace. In various embodiments, the second electrode further comprises a slurry or a gel. In various embodiments, at least one of the first electrode and the second electrode is a composite metal electrode comprising a mixture of the pellets and a smaller metal pellet composition. In various embodiments, the smaller metal particle composition is a powdered metal feedstock. In various embodiments, the powdered metal feedstock is wetted by the electrolyte. In various embodiments, the smaller metal particle composition comprises DRI fines, sponge iron, atomized iron, or any combination thereof. In various embodiments, the pellets comprise DRI taconite.In a plurality of embodiments, the granules are synthesized in a first operating stage of a dual-purpose energy storage power station including the battery, and are loaded into at least one of the first electrode and the second electrode in a second operating stage of the dual-purpose energy storage power station. In a plurality of embodiments, the granules are packed in a bed so that macropores are generated between two or more granules in contact with each other; and each of the granules includes micropores on its respective outer surface. In a plurality of embodiments, the granules are fused together. In a plurality of embodiments, the granules are chemically pretreated, mechanically pretreated, thermally pretreated, electrically pretreated, and / or electrochemically pretreated to fuse at least a portion of the granules and fill them in the bed. In a plurality of embodiments, the battery further comprises a pump configured to cause the liquid electrolyte to flow through the granules in the packed bed. In a plurality of embodiments, each of the granules includes micropores on its respective outer surface. In a plurality of embodiments, the granules include pores generated by immersing the granules in an etching bath, and then installing them in at least one of the first electrode and the second electrode. In a plurality of embodiments, the etching bath is an acid bath. In various embodiments, at least one of the first electrode and the second electrode further comprises an additive pellet comprising Bi2O3 or a metal sulfide. In various embodiments, the additive pellet comprises FeS, FeS2, Na2S or a combination thereof. In various embodiments, the pellet is a sintered iron pellet consisting of a crushed direct reduced iron ("DRI") precursor and / or DRI fines. In various embodiments, the pellet is mechanically pretreated, chemically pretreated, electrically pretreated, electrochemically pretreated and / or thermally pretreated before being installed in at least one of the first electrode and the second electrode. In various embodiments, the pretreatment comprises precharging the pellet. In various embodiments, the pellet is first composed of at least a portion of cementite (Fe3C) and then the battery is operated. In various embodiments, at least one of the first electrode and the second electrode further comprises an iron powder layer configured to form an interface between the pellet and a current collector of the battery. In various embodiments, the battery may further comprise a monitoring system configured to monitor the state of charge (SOC) and / or state of health of at least one of the first electrode and the second electrode. In various embodiments, the monitoring system comprises one or more sensors connected to a controller. In various embodiments, the one or more sensors are selected from strain gauges, Mossbauer spectrometers, CCD detectors, ultrasonic transducers, ion sensing electrodes, thermocouples, and gas sensors. In various embodiments, at least one of the first electrode and the second electrode is a composite metal electrode comprising a mixture of the pellets and a conductive material dispersed between the pellets. In various embodiments, the conductive material comprises one or more conductive fibers, one or more wires, one or more meshes, and / or one or more sheets.In various embodiments, the first electrode is a negative electrode and includes the DRI. In various embodiments, the battery may further include an additive delivery system configured to add one or more additives to the electrolyte. In various embodiments, the additive delivery system delivers liquid additives or solid additives. In various embodiments, the one or more additives include salts. In various embodiments, the salts are carbonates or polysulfide salts. In various embodiments, the one or more additives include sulfur-based additives. In various embodiments, the one or more additives include surfactant additives. In various embodiments, the one or more additives are configured to mitigate self-discharge and / or inhibit hydrogen evolution reaction (HER). In various embodiments, at least one of the first electrode and the second electrode is under compression. In various embodiments, at least one of the first electrode and the second electrode includes additional conductive material. In various embodiments, the additional conductive material surrounds the iron-containing pellets. In various embodiments, the additional conductive material is a foil, sheet, mesh or wire.

[0014] Various embodiments may provide a method for operating an energy storage power station, comprising operating the energy storage power station to produce active materials; and using the active materials in the energy storage power station for long-term energy storage. In various embodiments, the production of the active materials may use renewable electricity.

[0015] Multiple embodiments can provide a large-capacity energy storage system, including one or more batteries, wherein at least one of the one or more batteries includes a first electrode, an electrolyte, and a second electrode, wherein one or both of the first electrode and the second electrode include direct reduced iron ("DRI"). In multiple embodiments, at least one of the first electrode and the second electrode includes DRI, which is a negative electrode including direct reduced iron ("DRI") pellets. In multiple embodiments, at least one of the first electrode and the second electrode also includes additive pellets. In multiple embodiments, the additive pellets are composed of FeS, FeS2, Bi2O3 or metal sulfides. In multiple embodiments, the DRI includes sintered iron pellets composed of crushed direct reduced iron ("DRI") precursors and / or DRI fines. In multiple embodiments, the DRI is composed of direct reduced iron ("DRI") pellets, which are mechanically pretreated, chemically pretreated, and / or thermally pretreated and then installed on at least one of the first electrode and the second electrode. In various embodiments, the DRI comprises at least about 60 wt % metallic iron based on the total mass of the pellets, the DRI comprises direct reduced iron pellets having an average size of 4 mm to 20 mm, and the direct reduced iron pellets account for at least 60% of the total mass of at least one of the first electrode and the second electrode. In various embodiments, the bulk energy storage system is a long time energy storage (LODES) system.

[0016] Multiple embodiments may provide a long-term energy storage system configured to maintain a charge for at least 24 hours, the system comprising a housing, a first electrode, a second electrode, and an electrolyte, the first electrode comprising: about 60% to about 90% iron, and about 1% to about 40% of a component comprising one or more materials selected from SiO2, Al2O3, MgO, CaO, and TiO2. In multiple embodiments, the component may include about 1.5% to about 7.5% SiO2. In multiple embodiments, the component may include about 0.3% to about 3% Al2O3. In multiple embodiments, the component may include about 0.25% to about 2% MgO. In multiple embodiments, the component may include about 0.75% to about 2.5% CaO. In multiple embodiments, the component may include about 0.25% to about 1.5% TiO2. In multiple embodiments, the component may include about 1% to about 10% SiO2. In multiple embodiments, the component may include about 0.2% to about 5% Al2O3. In various embodiments, the composition may include about 0.1% to about 10% MgO. In various embodiments, the composition may include about 0.9% to about 10% CaO. In various embodiments, the composition may include about 0.05% to about 5% TiO2. In various embodiments, at least 50% of the iron is Fe 0 In various embodiments, at least 50% of the iron is metallic iron. In various embodiments, the iron comprises Fe 0 , Fe 2+ and Fe 3+ In various embodiments, the storage system has a rated power of at least about 100 MW, a rated duration of at least about 100 hours, and an energy rating of at least 2,000 MWh. In various embodiments, the storage device is a system having a rated power of about 50 MW to about 500 MW, a rated duration of about 25 hours to about 500 hours, and an energy rating of about 3,000 MWh to about 90,000 MWh. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a schematic diagram of an electrochemical cell according to various embodiments of the present disclosure.

[0018] Figure 2A is a schematic diagram of an electrochemical cell according to various embodiments of the present disclosure.

[0019] Figure 2B is a schematic diagram of an electrochemical cell according to various embodiments of the present disclosure.

[0020] Figure 3Ais a schematic diagram of an example of a continuous feed calciner configured to form sintered agglomerated particles according to various embodiments of the present disclosure.

[0021] Figure 3B is a process flow diagram of an embodiment of a method for forming a sintered porous metal electrode.

[0022] Figure 3C is a block diagram of an embodiment of a system for forming a sintered porous metal electrode.

[0023] Figure 3D is a block diagram of an embodiment of a system for forming a sintered porous metal electrode.

[0024] Figure 4 is a schematic diagram of an electrochemical cell according to various embodiments of the present disclosure, the electrochemical cell including a composite metal electrode having spherical pellets and a metal feedstock.

[0025] Figure 5 is a process flow diagram illustrating an embodiment of a method for in situ synthesis of active materials for large capacity energy storage systems using renewable overproduction.

[0026] Figure 6 yes Figure 1 Schematic diagram of an electrochemical cell showing magnified views of macropores and micropores according to various embodiments of the present disclosure.

[0027] Figure 7 According to various embodiments of the present disclosure Figure 1 Schematic diagram of a pellet of an electrochemical cell.

[0028] Fig. 8A is a schematic diagram of an electrochemical cell according to various embodiments of the present disclosure.

[0029] Figure 8B is a schematic diagram of an electrochemical cell according to various embodiments of the present disclosure.

[0030] Figure 8C is a schematic diagram of a series of fluidically connected electrochemical cells according to various embodiments of the present disclosure.

[0031] Fig. 9 is a schematic diagram of an electrochemical cell including a mixture of active material and additive material pellets according to various embodiments of the present disclosure.

[0032] Fig.10 is a schematic diagram of an electrochemical cell according to various embodiments of the present disclosure.

[0033] Fig.11 is a schematic diagram of an electrochemical cell according to various embodiments of the present disclosure.

[0034] Figures 12A-12F is a schematic diagram of an electrochemical cell according to various embodiments of the present disclosure.

[0035] Fig.13A is a schematic diagram of an electrochemical cell according to various embodiments of the present disclosure.

[0036] Fig. 13B is a schematic diagram of an electrochemical cell according to various embodiments of the present disclosure.

[0037] Fig.14 is a schematic diagram of a filtration device according to various embodiments of the present disclosure.

[0038] Figure 15-Figure 23 Several system examples are shown in which one or more aspects of various embodiments may be used as part of a bulk energy storage system.

[0039] Figure 24A-Figure 24D Graphs showing the first cycle discharge capacity (mAh / gDRI), discharge versus cycle number, coulombic efficiency, and subsequent cycle discharge capacity (mAh / gDRI) of the DRI electrode, respectively. DETAILED DESCRIPTION

[0040] A number of embodiments will be described in detail with reference to the accompanying drawings. The same reference numerals are used as much as possible in all drawings to refer to the same or similar parts. Reference to specific examples and implementations is for illustrative purposes, not for limiting the scope of the claims. The following description of the embodiments of the present invention is not intended to limit the present invention to these embodiments, but to enable those skilled in the art to make and use the present invention. Unless otherwise indicated, the drawings are not drawn to scale.

[0041] As used herein, room temperature is 25° C. unless otherwise specified. Also, standard temperature and standard pressure are 25° C. and 1 atmosphere. Unless otherwise expressly stated, all tests, test results, physical properties, and temperature-related, pressure-related, or both-related values ​​are provided at standard ambient temperature and pressure.

[0042] In general, unless otherwise indicated, the term "about" and the symbol "~" as used herein are intended to encompass a variation or range of ±10%, or the experimental or instrument error associated with obtaining the stated value, whichever is greater.

[0043] Recitation of ranges of values ​​as used herein are merely intended to serve as a shorthand method of referring individually to each separate value falling within the range, unless otherwise indicated herein. Unless otherwise indicated herein, each separate value within a range is incorporated into the specification as if it were individually recited herein.

[0044] Unless otherwise specified, the terms "%", "weight %" and "mass %" used herein are used interchangeably and refer to the weight of the first component as a percentage of the total weight, such as a formulation, mixture, particle, granule, material, structure or product. Unless otherwise specified, "volume %" and "% volume" and similar such terms used herein refer to the volume of the first component as a percentage of the total volume, such as a formulation, mixture, particle, granule, material, structure or product.

[0045] The following examples are provided to illustrate various embodiments of the systems and methods of the present invention. These examples are for illustrative purposes, may be prophetic, and should not be considered limiting, and do not otherwise limit the scope of the present invention.

[0046] It should be noted that no underlying theory is required to provide or elaborate novel and groundbreaking methods, materials, performances, or other beneficial features and properties of or related to the subject matter of the embodiments of the present invention. However, multiple theories are provided in this specification to further advance the technology in this field. The theories proposed in this specification, unless otherwise explicitly stated, in no way limit, restrict, or narrow the scope of protection provided by the claimed invention. These theories may not be required or practiced to utilize the present invention. It should also be understood that the present invention may lead to new and heretofore unknown theories to explain the functional characteristics of the embodiments of the methods, articles, materials, devices, and systems of the present invention; and these later developed theories will not limit the scope of protection provided by the present invention.

[0047] The multiple embodiments of the systems, devices, techniques, methods, applications and operations described in this specification can be used in multiple other applications and other fields in addition to those described herein. In addition, for example, these embodiments can be used for: other devices or applications that may be developed in the future; and, according to the teachings of this specification, existing devices or applications that can be partially modified. In addition, the multiple embodiments and examples described in this specification can be used together with each other in whole or in part and in different combinations and multiple combinations. Therefore, the configurations provided in the multiple embodiments of this specification can be used together with each other. For example, components of the embodiments with A, A' and B and components of the embodiments with A", C and D can be used together in multiple embodiments according to the teachings of this specification, for example, A, C, D and A, A", C and D, etc. Therefore, the scope of protection provided by the present invention should not be limited to the specific embodiments, configurations or arrangements described in the embodiments in the specific embodiments, examples or specific drawings.

[0048] Unless otherwise indicated, the term "specific gravity" (also called "apparent density") as used herein should be given its broadest possible meaning and generally refers to the weight per unit volume of a structure, such as the volumetric shape of a material. This property will include the internal porosity of the particle as a fraction of its volume. It can also be measured using, among other techniques, a low viscosity fluid that wets the surface of the particle.

[0049] Unless otherwise indicated, the term "actual density" (which may also be referred to as true density) as used herein should be given its broadest possible meaning and the general average weight per unit volume of a material when no voids are present in the material. This measurement and property substantially eliminates any internal porosity in the material, e.g., it does not include any voids in the material.

[0050] Therefore, porous foam balls (e.g., Nerf @ The weight of the container filled with balls is the volume density of the balls:

[0051]

[0052] The weight of a single ball compared to the spherical volume of the ball is its apparent density:

[0053]

[0054] The weight of the material that makes up the skeleton of the ball, i.e. the ball with all the void volume removed, compared to the remaining volume of that material will be the actual density:

[0055]

[0056] Embodiments of the present invention include instruments, systems and methods for long-term and ultra-long-term, low-cost, energy storage. In this article, unless otherwise expressly stated, "long-term" and "ultra-long-term" and similar terms should be given their broadest possible meaning, including energy storage times of 8 hours or more, such as 8 hours of energy storage time, 8 hours to 20 hours of energy storage time, 20 hours of energy storage time, 20 hours to 24 hours of energy storage time, 24 hours of energy storage time, 24 hours to a week of energy storage time, a week to a year of energy storage time (e.g., from days to weeks to months), etc., and may include LODES systems. In addition, unless otherwise expressly stated, the terms "long-term" and "ultra-long-term", "energy storage cells" including "electrochemical cells", and similar terms should be given their broadest possible interpretation; including electrochemical cells that can be configured to store energy over a time span of days, weeks, or quarters.

[0057] Typically, in one embodiment, the long-term energy storage cell can be a long-term electrochemical cell. Typically, such a long-term electrochemical cell can store electricity generated by a power generation system in the following circumstances: (i) when the power source or fuel used for power generation is available, sufficient, cheap, and combinations and variations of these; (ii) when the power supply requirement or power demand of the power grid, consumer or other user is less than the amount of electricity generated by the power generation system, the price obtained by providing electricity to the power grid, consumer or other user is lower than the economically effective point of power generation (for example, the cost of power generation exceeds the market price of electricity), and combinations and variations of these; and (iii), combinations and variations of (i) and (ii) and other reasons. Then, when economic or other needs arise, the electrical energy stored in the long-term electrochemical cell can be distributed to the power grid, consumer or other user. For example, the electrochemical cell can be configured to store energy generated by solar cells in summer months when the sun is abundant and solar power generation exceeds the demand of the power grid, and release the stored energy in winter months when the sun is not enough to meet the demand of the power grid.

[0058] Various embodiments related to the use of direct reduced iron (DRI) as a material for a battery (or battery cell), as part of a battery (or battery cell), and combinations and variations of these are discussed. In various embodiments, the DRI may be made from a material obtained by reducing natural iron ore or processing iron ore, or may be a material obtained by reducing natural iron ore or processing iron ore, the reduction being carried out without reaching the melting temperature of iron. In various embodiments, the iron ore may be taconite or magnetite or hematite or goethite, etc. In various embodiments, the DRI may be in the form of pellets, which may be spherical or substantially spherical. In various embodiments, the DRI may be porous, containing open and / or closed internal porosity. In various embodiments, the DRI may include material that has been further processed by hot briquetting or cold briquetting. In various embodiments, the DRI may be produced by reducing iron ore pellets to form a more metallic (higher degree of reduction, lower degree of oxidation) material, such as metallic iron (Fe 0), pyrite (FeO), or a composite pellet comprising metallic iron and a residual oxide phase. In multiple non-limiting embodiments, the DRI can be a reduced iron ore taconite, a directly reduced ("DR") taconite, a reduced "blast furnace (BF) grade" pellet, a reduced "electric arc furnace (EAF) grade" pellet, a "cold direct reduced iron (CDRI)" pellet, a direct reduced iron ("DRI") pellet, a hot briquette iron (HBI), or any combination thereof. In the steel manufacturing industry, DRI is sometimes referred to as "sponge iron", and this usage is particularly common in India. Embodiments of the iron material used in the multiple embodiments described herein, including, for example, embodiments of the DRI material, including as an electrode material, can have one, more or all of the material properties described in Table 1 below. Unless otherwise expressly stated, the following terms used in this specification, including Table 1, have the following meanings: “specific surface area” refers to the total surface area of ​​a material per unit mass, including the surface area of ​​pores in a porous structure; “carbon content” or “carbon (wt%)” refers to the percentage of the total carbon mass to the total mass of DRI; “cementite content” or “cementite (wt%)” refers to the percentage of the mass of Fe3C to the total mass of DRI; “total Fe (wt%)” refers to the percentage of the total iron mass to the total mass of DRI; “metallic Fe (wt%)” refers to the percentage of the Fe3C mass to the total mass of DRI. 0 The percentage of the mass of Fe in the state to the total mass of DRI; “metallization” refers to the 0 Unless otherwise stated, weight percentages, volume percentages and apparent densities used herein should be understood to exclude any electrolyte that penetrates into the porosity or fugitive additives within the porosity.

[0059] Table 1

[0060]

[0061]

[0062] *Specific surface area is preferably determined by the Brunauer-Emmett-Teller adsorption method ("BET"), and more preferably as described in ISO 9277 according to BET (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as methylene blue (MB) staining, ethylene glycol monoethyl ether (EGME) adsorption, electrokinetic analysis of complex ion adsorption, and protein precipitation (PR) methods, can be used to provide results that can be correlated with BET results.

[0063] ** Actual density is preferably determined by helium (He) pycnometry, more preferably as described in ISO 12154 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests may be employed to provide results that can be correlated with He pycnometry results. Actual density may also be referred to in the art as "true density" or "skeletal density."

[0064] ***Apparent density is preferably determined by immersion in water, more preferably as described in ISO 15968 (the entire disclosure of which is incorporated herein by reference); it will be appreciated that other tests may be employed to provide results that can be correlated with He pycnometry results. Porosity may be defined as the ratio of apparent density to actual density:

[0065]

[0066] ****d 孔,90%体积 Preferably measured by mercury (Hg) intrusion porosimetry, more preferably as described in ISO 15901-1 (the entire disclosure of which is incorporated herein by reference); it will be appreciated that other tests (e.g. gas adsorption) may be employed to provide results that can be correlated with the mercury intrusion results. 孔,90%体积 The pore size that is larger than 90% of the total pore volume.

[0067] *****d 孔,50%表面积 Preferably measured by mercury (Hg) intrusion porosimetry, more preferably as described in ISO 15901-1 (the entire disclosure of which is incorporated herein by reference); it will be appreciated that other tests (e.g. gas adsorption) may be employed to provide results that can be correlated with the mercury intrusion results. 孔,50%表面积 50% of the free surface area is larger than the pore size.

[0068] #Total Fe (wt%) is preferably determined by dichromate titration, more preferably as described in ASTM E246-10 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as tin (II) chloride reduction titration, titanium (III) chloride reduction titration, inductively coupled plasma (ICP) spectroscopy, can be used to provide results that can be correlated with dichromate titration.

[0069] ##Metallic Fe (wt%) is preferably determined by iron (III) chloride titration, more preferably as described in ISO 16878 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests (such as bromine-methanol titration) can be used to provide results related to iron (III) chloride titration.

[0070] ###The metallization ratio (%) is preferably determined by the ratio of metallic Fe to total Fe, each of which is preferably determined by the aforementioned method.

[0071] ####Carbon (wt%) is preferably determined by infrared absorption after combustion in an induction furnace, more preferably as described in ISO 9556 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as various combustion and inert gas fusion techniques (as described in ASTM E1019-18), may be used to provide results that can be correlated to infrared absorption after combustion in an induction furnace.

[0072] #####Fe 2+ (Weight %) is preferably determined by titration, more preferably as described in ASTM D3872-05 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as Mössbauer spectroscopy, X-ray absorption spectroscopy, etc., can be used to provide results that can be correlated with titration.

[0073] $Fe 3+ (wt%) is preferably composed of total Fe (wt%), metallic Fe (wt%), Fe 2+ (wt%) and Fe 3+ Specifically, according to the law of mass conservation, total Fe (weight %) = metal Fe (weight %) + Fe 2+ (wt%) +Fe 3+ (wt%) must hold true, so Fe 3+ (wt%) can be obtained by Fe 3+ (weight %) = total iron (weight %) - metallic Fe (weight %) - Fe 2+ (wt%) was calculated.

[0074] $$SiO2 (wt%) is preferably determined by a gravimetric method, more preferably as described in ISO 2598-1 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as reduced molybdenum silicate spectrophotometry, X-ray diffraction (XRD) can be used to provide results that can be correlated with the gravimetric method. In certain methods, the SiO2 wt% is not determined directly, but the Si concentration (including neutral and ionic species) is measured and the SiO2 wt% is calculated assuming a stoichiometric SiO2; that is, a Si:O molar ratio of 1:2 is assumed.

[0075] $$$ Ferrite (wt. %, XRD) is preferably determined by X-ray diffraction (XRD).

[0076] $$$$Wuxite (FeO, wt. %, XRD) is preferably determined by X-ray diffraction (XRD).

[0077] $$$$$Goethite (FeOOH, wt. %, XRD) is preferably determined by X-ray diffraction (XRD).

[0078] + Cementite (Fe3C, wt. %, XRD) is preferably determined by X-ray diffraction (XRD).

[0079] In addition, embodiments of iron materials for use in the various embodiments described herein, including, for example, embodiments of DRI materials, including as electrode materials, can have one or more of the following properties, characteristics, or characteristics (note that values ​​from one row or column may appear with values ​​from a different row or column) as shown in Table 1A.

[0080] Table 1A

[0081]

[0082]

[0083] Total Fe (wt%) is preferably determined by dichromate titration, more preferably as described in ASTM E246-10 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as tin (II) chloride reduction titration, titanium (III) chloride reduction titration, inductively coupled plasma (ICP) spectroscopy, can be used to provide results that can be correlated with dichromate titration.

[0084] ! ! SiO2 (wt%) is preferably determined by a gravimetric method, more preferably as described in ISO 2598-1 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as reduced molybdenum silicate spectrophotometry, X-ray diffraction (XRD) can be used to provide results that can be correlated with the gravimetric method. In some methods, the SiO2 wt% is not determined directly, but the Si concentration (including neutral and ionic species) is measured and the SiO2 wt% is calculated assuming the stoichiometry of SiO2; that is, the molar ratio of Si:O is assumed to be 1:2.

[0085] ! ! ! Al2O3 (wt%) is preferably determined by flame atomic absorption spectrometry, more preferably as described in ISO 4688-1 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as X-ray diffraction (XRD), can be used to provide results that can be correlated with flame atomic absorption spectrometry. In some methods, the Al2O3 wt% is not determined directly, but the Al concentration (including neutral and ionic species) is measured and the Al2O3 wt% is calculated assuming the stoichiometry of Al2O3; that is, the molar ratio of Al:O is assumed to be 2:3.

[0086] MgO (wt%) is preferably determined by flame atomic absorption spectrometry, more preferably as described in ISO 10204 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as X-ray diffraction (XRD), may be employed to provide results that can be correlated with flame atomic absorption spectrometry. In certain methods, the MgO wt% is not determined directly, but rather the Mg concentration (including neutral and ionic species) is measured and the MgO wt% is calculated assuming a stoichiometric MgO; that is, a molar ratio of Mg:O is assumed to be 1:1.

[0087] !!!!!! CaO (wt%) is preferably determined by flame atomic absorption spectrometry, more preferably as described in ISO 10203 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as X-ray diffraction (XRD), may be employed to provide results that can be correlated with flame atomic absorption spectrometry. In certain methods, the CaO wt% is not determined directly, but rather the Ca concentration (including neutral and ionic species) is measured and the CaO wt% is calculated assuming a stoichiometric CaO; that is, a Ca:O molar ratio of 1:1 is assumed.

[0088] &TiO2 (wt%) is preferably determined by diantipyryl methane spectrophotometry, more preferably as described in ISO 4691 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as X-ray diffraction (XRD), can be used to provide results that can be correlated with diantipyryl methane spectrophotometry. In certain methods, the TiO2 wt% is not determined directly, but the Ti concentration (including neutral and ionic species) is measured and the TiO2 wt% is calculated assuming the stoichiometry of TiO2; that is, the molar ratio of Ti:O is assumed to be 1:2.

[0089] &&The actual density is preferably determined by helium (He) pycnometry, more preferably as described in ISO 12154 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests may be used to provide results that can be correlated with He pycnometry results. The actual density may also be referred to in the art as "true density" or "skeletal density."

[0090] &&&The apparent density is preferably determined by immersion in water, more preferably as described in ISO 15968 (the entire disclosure of which is incorporated herein by reference); other tests may be used to provide results that can be correlated with the He pycnometry results.

[0091] &&&&Volume density (kg / m 3) is preferably determined by measuring the mass of a test portion introduced into a container of known volume up to the level of its surface, more preferably as described in method 2 of ISO 3852 (the entire contents of which are incorporated herein by reference); it will be appreciated that other tests may be employed to provide results that can be correlated with mass methods.

[0092] &&&&&&Porosity is preferably determined by the ratio of apparent density to actual density:

[0093]

[0094] The properties listed in Table 1 may also be present in embodiments in addition to or in place of the properties in Table 1A. Greater or lesser values ​​of these properties may also be present in various embodiments.

[0095] In an embodiment, the specific surface area of ​​the pellets may be about 0.05 m 2 / g to about 35m 2 / g, about 0.1m 2 / g to about 5m 2 / g, about 0.5m 2 / g to about 10m 2 / g, about 0.2m 2 / g to about 5m 2 / g, about 1m 2 / g to about 5m 2 / g, about 1m 2 / g to about 20m 2 / g, greater than about 1m 2 / g, greater than about 2m 2 / g, less than about 5m 2 / g, less than about 15m 2 / g, less than about 20m 2 / g, and combinations and variations of these specific surface areas, as well as larger or smaller values.

[0096] Typically, iron ore pellets are produced by crushing, grinding or milling iron ore into a fine powder and then concentrated by removing impurity phases (called "gangue") released by the grinding operation. Typically, the purity of the resulting concentrate is increased as the ore is ground into a finer (smaller) particle size. The concentrate is then made into pellets by a pelletizing process or a balling process (e.g., using a drum pelletizer or a disc pelletizer). Typically, higher energy input is required to produce higher purity ore pellets. Iron ore pellets are typically marketed or sold in two main categories: blast furnace (BF) grade pellets and direct reduction (DR grade) (sometimes also called electric arc furnace (EAF) grade), the main difference being that the BF grade pellets have a higher content of SiO2 and other impurity phases relative to the DR grade pellets. Typical key parameters for DR grade pellets or feedstocks are: total Fe content (mass percentage) in the range of 63 wt%-69 wt% (e.g. 67 wt%) and SiO2 content (mass percentage) less than 3 wt% (e.g. 1 wt%). Typical key parameters for BF grade pellets or feedstocks are: total Fe content (mass percentage) in the range of 60 wt%-67 wt% (e.g. 63 wt%) and SiO2 content (mass percentage) in the range of 2 wt%-8 wt% (e.g. 4 wt%).

[0097] In certain embodiments, DRI may be produced by reducing "blast furnace" pellets, in which case the resulting DRI may have material properties as described below in Table 2. Using reduced BF grade DRI may be advantageous because less input energy is required to produce the pellets, which translates into lower finished material costs.

[0098] Table 2

[0099]

[0100]

[0101] *Specific surface area is preferably determined by the Brunauer-Emmett-Teller adsorption method ("BET"), more preferably as described in ISO 9277 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as methylene blue (MB) staining, ethylene glycol monoethyl ether (EGME) adsorption, electrokinetic analysis of complex ion adsorption, and protein precipitation (PR) methods, can be used to provide results that can be correlated with BET results.

[0102] ** Actual density is preferably determined by helium (He) pycnometry, more preferably as described in ISO 12154 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests may be employed to provide results that can be correlated with He pycnometry results. Actual density may also be referred to in the art as "true density" or "skeletal density."

[0103] ***Apparent density is preferably determined by immersion in water, and more preferably as described in ISO 15968 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests may be employed to provide results that can be correlated with He pycnometry results. Porosity may be defined as the ratio of apparent density to actual density:

[0104]

[0105] ****d 孔,90%体积 Preferably measured by mercury (Hg) intrusion porosimetry, more preferably as described in ISO 15901-1 (the entire disclosure of which is incorporated herein by reference); it will be appreciated that other tests (e.g. gas adsorption) may be employed to provide results that can be correlated with the mercury intrusion results. 孔,90%体积 The pore size that is larger than 90% of the total pore volume.

[0106] *****d 孔,50%表面积 Preferably measured by mercury (Hg) intrusion porosimetry, more preferably as described in ISO 15901-1 (the entire disclosure of which is incorporated herein by reference); it will be appreciated that other tests (e.g. gas adsorption) may be employed to provide results that can be correlated with the mercury intrusion results. 孔,50%表面积 50% of the free surface area is larger than the pore size.

[0107] #Total Fe (wt%) is preferably determined by dichromate titration, more preferably as described in ASTM E246-10 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as tin (II) chloride reduction titration, titanium (III) chloride reduction titration, inductively coupled plasma (ICP) spectroscopy, can be used to provide results that can be correlated with dichromate titration.

[0108] ##Metallic Fe (wt%) is preferably determined by iron (III) chloride titration, more preferably as described in ISO 16878 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests (such as bromine-methanol titration) can be used to provide results related to iron (III) chloride titration.

[0109] ###The metallization ratio (%) is preferably determined by the ratio of metallic Fe to total Fe, each of which is preferably determined by the aforementioned method.

[0110] ####Carbon (wt%) is preferably determined by infrared absorption after combustion in an induction furnace, more preferably as described in ISO 9556 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as various combustion and inert gas fusion techniques (as described in ASTM E1019-18), may be used to provide results that can be correlated to infrared absorption after combustion in an induction furnace.

[0111] #####Fe 2+ (Weight %) is preferably determined by titration, more preferably as described in ASTM D3872-05 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as Mössbauer spectroscopy, X-ray absorption spectroscopy, etc., can be used to provide results that can be correlated with titration.

[0112] Fe 3+ (wt%) is preferably composed of total Fe (wt%), metallic Fe (wt%), Fe 2+ (wt%) and Fe 3+ Specifically, according to the law of mass conservation, total Fe (weight %) = metal Fe (weight %) + Fe 2+ (wt%) +Fe 3+ (wt%) must hold true, so Fe 3+ (wt%) can be obtained by Fe 3+ (weight %) = total iron (weight %) - metallic Fe (weight %) - Fe 2+ (wt%) was calculated.

[0113] $$SiO2 (wt%) is preferably determined by a gravimetric method, more preferably as described in ISO 2598-1 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as reduced molybdenum silicate spectrophotometry, X-ray diffraction (XRD) can be used to provide results that can be correlated with the gravimetric method. In certain methods, the SiO2 wt% is not determined directly, but the Si concentration (including neutral and ionic species) is measured and the SiO2 wt% is calculated assuming a stoichiometric SiO2; that is, a Si:O molar ratio of 1:2 is assumed.

[0114] $$$ Ferrite (wt. %, XRD) is preferably determined by X-ray diffraction (XRD).

[0115] $$$$Wuxite (FeO, wt. %, XRD) is preferably determined by X-ray diffraction (XRD).

[0116] $$$$$Goethite (FeOOH, wt. %, XRD) is preferably determined by X-ray diffraction (XRD).

[0117] + Cementite (Fe3C, wt. %, XRD) is preferably determined by X-ray diffraction (XRD).

[0118] In addition to or in place of the properties in Table 1 and / or Table 1A, the properties listed in Table 2 may also be present in embodiments. Greater or lesser values ​​of these properties may also be present in various embodiments.

[0119] In certain embodiments, DRI may be produced by reducing DR grade pellets, in which case the resulting DRI may have the material properties described below in Table 3. Using reduced DR grade DRI may be advantageous because higher Fe content in the pellets increases the energy density of the battery.

[0120] Table 3

[0121]

[0122] *Specific surface area is preferably determined by the Brunauer-Emmett-Teller adsorption method ("BET"), more preferably as described in ISO 9277 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as methylene blue (MB) staining, ethylene glycol monoethyl ether (EGME) adsorption, electrokinetic analysis of complex ion adsorption, and protein precipitation (PR) methods, can be used to provide results that can be correlated with BET results.

[0123] ** Actual density is preferably determined by helium (He) pycnometry, more preferably as described in ISO 12154 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests may be employed to provide results that can be correlated with He pycnometry results. Actual density may also be referred to in the art as "true density" or "skeletal density."

[0124] ***Apparent density is preferably determined by immersion in water, more preferably as described in ISO 15968 (the entire disclosure of which is incorporated herein by reference); other tests may be employed to provide results that can be correlated with He pycnometry results. Porosity may be defined as the ratio of apparent density to actual density:

[0125]

[0126] ****d 孔,90%体积 Preferably measured by mercury (Hg) intrusion porosimetry, more preferably as described in ISO 15901-1 (the entire disclosure of which is incorporated herein by reference); it will be appreciated that other tests (e.g. gas adsorption) may be employed to provide results that can be correlated with the mercury intrusion results. 孔,90%体积 The pore size that is larger than 90% of the total pore volume.

[0127] *****d 孔,50%表面积 Preferably measured by mercury (Hg) intrusion porosimetry, more preferably as described in ISO 15901-1 (the entire disclosure of which is incorporated herein by reference); it will be appreciated that other tests (such as gas adsorption) may be employed to provide results that can be correlated with mercury intrusion results. 孔,50%表面积 50% of the free surface area is larger than the pore size.

[0128] #Total Fe (wt%) is preferably determined by dichromate titration, more preferably as described in ASTM E246-10 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as tin (II) chloride reduction titration, titanium (III) chloride reduction titration, inductively coupled plasma (ICP) spectroscopy, can be used to provide results that can be correlated with dichromate titration.

[0129] ##Metallic Fe (wt%) is preferably determined by iron (III) chloride titration, more preferably as described in ISO 16878 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests (such as bromine-methanol titration) can be used to provide results related to iron (III) chloride titration.

[0130] ###The metallization ratio (%) is preferably determined by the ratio of metallic Fe to total Fe, each of which is preferably determined by the aforementioned method.

[0131] ####Carbon (wt%) is preferably determined by infrared absorption after combustion in an induction furnace, more preferably as described in ISO 9556 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as various combustion and inert gas fusion techniques (as described in ASTM E1019-18), may be used to provide results that can be correlated to infrared absorption after combustion in an induction furnace.

[0132] #####Fe 2+ (Weight %) is preferably determined by titration, more preferably as described in ASTM D3872-05 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as Mössbauer spectroscopy, X-ray absorption spectroscopy, etc., can be used to provide results that can be correlated with titration.

[0133] $Fe 3+ (wt%) is preferably composed of total Fe (wt%), metallic Fe (wt%), Fe 2+ (wt%) and Fe 3+ Specifically, according to the law of mass conservation, total Fe (weight %) = metal Fe (weight %) + Fe 2+(wt%) +Fe 3+ (wt%) must hold true, so Fe 3+ (wt%) can be obtained by Fe 3+ (weight %) = total iron (weight %) - metallic Fe (weight %) - Fe 2+ (wt%) was calculated.

[0134] $$SiO2 (wt%) is preferably determined by a gravimetric method, more preferably as described in ISO 2598-1 (the entire disclosure of which is incorporated herein by reference); it should be understood that other tests, such as reduced molybdenum silicate spectrophotometry, X-ray diffraction (XRD) can be used to provide results that can be correlated with the gravimetric method. In certain methods, the SiO2 wt% is not determined directly, but the Si concentration (including neutral and ionic species) is measured and the SiO2 wt% is calculated assuming a stoichiometric SiO2; that is, a Si:O molar ratio of 1:2 is assumed.

[0135] $$$ Ferrite (wt. %, XRD) is preferably determined by X-ray diffraction (XRD).

[0136] $$$$Wuxite (FeO, wt. %, XRD) is preferably determined by X-ray diffraction (XRD).

[0137] $$$$$Goethite (FeOOH, wt. %, XRD) is preferably determined by X-ray diffraction (XRD).

[0138] + Cementite (Fe3C, wt. %, XRD) is preferably determined by X-ray diffraction (XRD).

[0139] The properties listed in Table 3 may also be present in embodiments in addition to or in place of the properties in Table 1, Table 1A, and / or Table 2. Greater or lesser values ​​of these properties may also be present in various embodiments.

[0140] In various embodiments, the conductive granule bed includes (e.g., for providing, as a component, constituting, etc.) an electrode in an energy storage system. In embodiments of the electrode, the granules include iron-containing materials, reduced iron materials, non-oxidized iron, high-oxidized iron, iron with a valence of 0 to 3+, and combinations and variations of these materials. In embodiments of the electrode, the granules include iron having one or more of the characteristics listed in Table 1, Table 1A, Table 2, and Table 3. In embodiments, the granules have porosity, such as an open pore structure, which may have, for example, a pore size ranging from a few nanometers to a few microns. For example, embodiments may have the following pore sizes: about 5 nm (nanometer) to about 100 μm (micrometer), about 50 nm to about 10 μm, about 100 nm to about 1 μm, greater than 100 nm, greater than 500 nm, less than 1 μm, less than 10 μm, less than 100 μm, and combinations and variations of these pore sizes, as well as larger or smaller pores. In some embodiments, the granules include granules of direct reduced iron (DRI). Embodiments of these electrodes in energy storage systems, particularly long-duration energy storage systems, may have one or more of these aforementioned features.

[0141] The packing of the pellets creates macropores, such as openings, spaces, channels or voids, between the individual pellets. The macropores facilitate ion transport through the electrode, which in some embodiments has a minimum size but is still very thick compared to some other types of battery electrodes that are several centimeters in size. The micropores inside the pellets allow the high surface area active material of the pellet to contact the electrolyte to achieve high utilization of the active material. This electrode structure is particularly suitable for improving the rate performance of very thick electrodes for static long-term energy storage, where thick electrodes may be required to achieve extremely high area capacity.

[0142] The pellets of these embodiments, especially the pellets in the embodiments of electrodes for long-term energy storage systems, can be of any volume shape, such as spheres, discs, cakes, beads, small pieces, small balls, rings, crystals, discs, plates, cones, truncated cones, blocks, rectangular blocks, trusses, corners, channels, hollow sealed cavities, hollow spheres, blocks, sheets, films, granules, bundles, rods, corners, flat plates, columns, fibers, short fibers, tubes, cups, pipes and combinations and multiples of these shapes and other more complex shapes. The pellets in the electrodes can be the same shape or different shapes. In a long-term energy storage system, the pellets in an electrode that is one of the multiple electrodes can be the same or different from the pellets in other electrodes in the storage system.

[0143] Unless otherwise expressly provided, the size of the pellet refers to the maximum cross-sectional distance of the pellet, such as the diameter of a sphere. The pellets may be of the same size or of different sizes. It is recognized that the shape, size, and both of the pellets, which are usually smaller than the shape and size of the container or housing that holds the pellets, determine the nature and size of the macropores in the electrode. The pellets may have a diameter of about 0.1 mm to about 10 cm, about 5 mm to about 100 mm, 10 mm to about 50 mm, about 20 mm, about 25 mm, about 30 mm, greater than 0.1 mm, greater than 1 mm, greater than 5 mm, greater than 10 mm, and greater than 25 mm, as well as combinations and variations of these sizes.

[0144] In an embodiment, the pellets configured in an electrode can provide an electrode having a volume density of about 3 g / cm 3 To about 6.5g / cm 3 , about 0.1g / cm 3 To about 5.5g / cm 3 , about 2.3g / cm 3 To about 3.5g / cm 3 、3.2g / cm 3 To about 4.9g / cm 3 , greater than about 0.5 g / cm 3 , greater than about 1g / cm 3 , greater than about 2g / cm 3 , greater than about 3g / cm 3 , as well as multiple combinations of these values ​​and larger or smaller values.

[0145] In certain embodiments, a mixture of reduced DR grade pellets and reduced BF grade pellets may be used together. In certain other embodiments, reduced material (DRI) and run of ore material (DR grade or BF grade) may be used in combination.

[0146] In various embodiments, DRI can be produced by using "artificial ores" (e.g., iron oxide in the form of waste or byproducts). As a non-limiting example, mill scale is a mixed iron oxide formed on the surface of hot rolled steel, which, in various embodiments, is collected and ground to form an iron oxide powder, which is then agglomerated to form pellets and subsequently reduced to form DRI. Other waste streams can also be used similarly to form DRI. As another non-limiting example, a pickling liquor is an acidic solution that can be enriched in dissolved Fe ions. In various embodiments, the Fe-containing pickling liquor can be neutralized with a base (e.g., caustic potash or sodium hydroxide) to precipitate an iron oxide powder, which is then agglomerated to form pellets and subsequently reduced to form DRI.

[0147] In various embodiments, the precursor iron oxide is first reduced and then formed into pellets or other agglomerates. In certain non-limiting embodiments, iron oxide powder from natural or synthetic ores is reduced to metallic iron powder by heat treatment at 900°C in a reducing gas environment, such as in a linear hearth furnace in a hydrogen atmosphere (1% H2 to 100% H2). In embodiments using hydrogen as the reducing gas, the cementite (Fe3C) content of the DRI can be as low as 0 wt%.

[0148] In various embodiments, DRI pellets or DRI agglomerates are formed from iron oxide powder in a single process by using a rotary calciner. The rotary motion of the furnace promotes the agglomeration of the powder into pellets or agglomerates, while the high temperature reducing gas environment simultaneously reduces the iron oxide. In various other embodiments, a multi-stage rotary calciner may be used, wherein the agglomeration step and the reduction step may be independently adjusted and optimized.

[0149] In a number of embodiments, DRI has a non-spherical shape. In certain embodiments, DRI may have a substantially straight or brick-like shape. In certain embodiments, DRI may have a substantially cylindrical or rod-like or disc-like shape. In certain embodiments, DRI may have a substantially planar or flaky shape. In certain embodiments, the iron oxide powder is molded into a cylindrical or any other shape suitable for molding by molding. In certain embodiments, the iron oxide powder is dried by calendering rolls to form a flaky form. In certain embodiments, the iron oxide powder is mixed with a binder (e.g., clay or polymer) and processed into a rod-like shape by extrusion drying. In certain embodiments, the iron oxide powder is mixed with a binder (e.g., clay or polymer) and processed into a flaky form by calendering rolls. The binder may be composed of clay (e.g., bentonite) or a polymer (e.g., corn starch, polyacrylamide, or polyacrylate). Binder can include bentonite, sodium carbonate, calcium chloride, calcium hydroxide, sodium silicate, carboxymethyl cellulose (CMC), Alcotac, Peridur, corn starch, Funa, wheat flour, sodium lignin sulfate, molasses or polyacrylate etc. Binder can be composed of a combination of one or more clays and one or more polymers. In certain embodiments, iron oxide powder is dispersed in a liquid to form a slurry, which is then wet-formed into a variety of shapes. In certain embodiments, iron oxide slurry is slip-cast into a mold close to any shape. In certain embodiments, iron oxide slurry is coated on a sheet by blade coating or other similar coating processes.

[0150] In multiple embodiments, the conductive microporous granule bed comprises an electrode in an energy storage system. In some embodiments, the granules comprise granules of direct reduced iron (DRI). The packing of granules forms macropores between individual granules. The macropores facilitate ion transport through the electrode, and in some embodiments, the electrode has a minimum size, but is still very thick compared to some other types of battery electrodes that are several centimeters in size. Compared to the micropores within the granules, the macropores can form a pore space with low curvature. The micropores inside the granules bring the high surface area active material of the granules into contact with the electrolyte to achieve high utilization of the active material. This electrode structure is particularly suitable for improving the rate performance of extremely thick electrodes for static long-term energy storage, where thick electrodes may be required to achieve extremely high area capacity.

[0151] In various embodiments, fugitive pore formers are added during the production of DRI to increase the porosity of the resulting DRI. In one embodiment, the porosity of the DRI pellets is changed by adding a sacrificial pore former such as ice (solid H2O) during the granulation process, which is then melted or sublimated under thermal treatment. In certain other embodiments, the fugitive pore former comprises naphthalene, which is then sublimated to leave pores. In other embodiments, a fugitive pore former comprising NH4CO3 (ammonium carbonate) can be a fugitive pore former and can be introduced as a solid at multiple points in the production of DRI, and decomposed under heating and completely removed with a gaseous substance or a liquid substance (NH3+CO2+H2O). In various other embodiments, the fugitive additive can play an additional role in the battery cell (e.g., as an electrolyte component). In certain embodiments, the fugitive additive can be an alkaline salt, such as KOH, NaOH or LiOH. In certain embodiments, the fugitive additive may be a soluble electrolyte additive in solid form under dry conditions, such as lead sulfate, lead acetate, antimony sulfate, antimony acetate, sodium molybdenum oxide, potassium molybdenum oxide, thiourea, sodium stannate, ammonium thiosulfate. In various other embodiments, the fugitive additive may be a binder for agglomerating iron ore powder to form pellets or other shapes, such as sodium alginate or carboxymethyl cellulose binders.

[0152] In a number of embodiments, sacrificial pore formers, convertible pore formers, fugitive pore formers, removable pore formers or techniques can be used. In these embodiments, the intermediate material still having pore formers can have a total Fe weight of 20% to 90% by weight. The pore former can be partially removed before being used as an electrode, completely removed before being used as an electrode, or removed during being used as an electrode, and combinations and variations of these modes. In one embodiment, the intermediate can have a total of 25% to 50% by weight of Fe, and after removing the pore former, an electrode with a total of 60% to 90% by weight of Fe is provided.

[0153] In certain embodiments, the reducing gas for forming DRI is hydrogen (H2). In certain embodiments, the hydrogen used as reducing gas is a by-product of an industrial process, a chemical process, or a manufacturing process. In certain embodiments, hydrogen is produced by electrolyzing water from a renewable power source (e.g., wind or solar energy). In certain embodiments, an electrolyzer is coupled to an energy storage system. In certain embodiments, the electrolyzer is a proton exchange membrane (PEM) electrolyzer. In certain embodiments, the electrolyzer is an alkaline electrolyzer. In certain embodiments, hydrogen is a by-product of a chlor-alkali process or a chlor-alkali plant. In embodiments using hydrogen as a reducing gas, the cementite (Fe3C) content of DRI can be as low as 0 weight %.

[0154] In certain embodiments, natural gas (methane, CH4) is used as a reducing agent for producing DRI. In some embodiments, the natural gas used is obtained from naturally occurring underground mineral deposits or agriculture. In certain embodiments, the methane used as a reducing gas is a by-product of an industrial process, a chemical process or a manufacturing process. In certain embodiments, methane is steam reformed (by reacting with water (H2O)) to produce a mixture of carbon monoxide (CO) and hydrogen (H2) by reacting CH4+H2O→CO+3H2. In certain embodiments, the reforming reaction is carried out by an auxiliary reformer separated from the reactor where iron reduction occurs. In certain embodiments, reforming occurs in situ in a reduction reactor. In certain embodiments, reforming occurs in an auxiliary reformer and a reduction reactor. In certain embodiments, coal is used as a reducing agent for producing DRI. In certain embodiments, coke is used as a reducing agent for producing DRI. In embodiments using a carbonaceous reducing gas, the cementite (Fe3C) content of DRI can be higher, up to 80% by weight.

[0155] In certain embodiments, mixtures of DRI produced using multiple reducing gases can be used to achieve a beneficial combination of composition and properties. In one non-limiting embodiment, a mixture of DRI produced by BF-grade pellets reduced in natural gas and DRI produced by DR-grade pellets reduced in hydrogen (50 / 50 by mass) is used as the negative electrode of the battery. Other combinations of mass ratios, feedstock types (DR, BF, other artificial ores, etc.) and reducing media (hydrogen, natural gas, coal, etc.) can be combined in other embodiments.

[0156] In various embodiments, the DRI pellets may be crushed, and the crushed pellets may include a bed (with or without added powders).

[0157] In various embodiments, additives that are beneficial to the electrochemical cycle, such as hydrogen evolution reaction (HER) inhibitors, may be added to the bed in solid form (eg, as a powder or as solid pellets).

[0158] In some embodiments, the metal electrode may have a low initial specific surface area (e.g., less than about 5 m 2 / g, preferably less than about 1m 2 / g). Such electrodes tend to have low self-discharge rates in low-rate, long-duration energy storage systems. An example of a low specific surface area metal electrode is a DRI pellet bed. In a number of typical modern electrochemical cells (e.g., lithium-ion batteries or nickel metal hydride batteries), a high specific surface area is required to facilitate high rate performance (i.e., high power). In long-duration systems, the rate performance requirements are significantly reduced, so low specific surface area electrodes can meet the target rate performance requirements while minimizing the self-discharge rate.

[0159] In some embodiments, the DRI pellets are treated by mechanical methods, chemical methods, electrical methods, electrochemical methods and / or thermal methods, and then the DRI pellets are used in electrochemical cells. This pretreatment can achieve superior chemical and physical properties, and can, for example, increase the available capacity during the discharge reaction. The physical and chemical properties of purchased (sometimes also referred to as "as is") DRI may not be suitable for use as the negative electrode of an electrochemical cell. Improved chemical and physical properties can include introducing a higher content of desired impurities (e.g., HER inhibitors), obtaining a lower content of unwanted impurities (e.g., HER catalysts), obtaining a higher specific surface area, obtaining a higher total porosity, achieving a pore size distribution different from the initial DRI (e.g., a multimodal pore size distribution to reduce mass transfer resistance), achieving a desired particle size distribution (e.g., a multimodal particle size distribution filled to a desired density of pellets) and changing or selecting pellets of a desired aspect ratio (to achieve a desired bed packing density). Mechanical treatment can include tumbling, milling, crushing, grinding and powdering. Chemical treatment can include acid etching. Chemical treatment may include soaking the pellet bed in an alkaline solution to produce necking between pellets, coarsening of micropores within the pellets, or dissolving impurities or second phases to increase the pore volume percentage or change the pore size distribution. Thermal treatment may include treating the DRI at elevated temperatures in an inert, reducing, oxidizing, and / or carburizing atmosphere. In various embodiments, mechanical, chemical, electrical, electrochemical, and / or thermal methods of pretreating the electrode-forming material (e.g., DRI pellets, etc.) may fuse the electrode-forming material into a bed (e.g., a bed of DRI pellets fused together).

[0160] In the embodiments described herein, the iron material can be treated, chemically modified, mechanically modified, or otherwise configured to change one or more of its characteristics. These methods are generally described herein as being performed on DRI materials. It should be understood that these methods can be used for other iron-containing materials, such as reduced iron materials, non-oxidized iron, high-oxidized iron, iron with a valence of 0 to 3+, and combinations and variations of these iron materials. In this way, an iron-containing pellet for an electrode configuration for a long-term storage battery cell is provided, the iron-containing pellet having predetermined characteristics, such as the characteristics described in this specification.

[0161] In certain embodiments, the DRI is subjected to mechanical manipulation to grind, burnish or polish the surface, and / or remove fines. In one embodiment, the DRI pellets are rolled in a drum screen to burnish the surface and remove fines / dust from the surface. This operation can have the beneficial effect of reducing the reactivity of the DRI pellets, making them easier and safer to transport without the need for briquetting or other compacting operations. In another embodiment, the DRI blocks or DRI sheets are passed under a rotating brush to remove fines from the surface, with similar beneficial effects.

[0162] In one embodiment, the porosity is increased by pre-treating the DRI by immersion in an acid bath (e.g., concentrated HCl), which etches the iron and creates larger pores, thereby increasing the overall porosity. The etching time can be optimized to increase the overall capacity of the DRI pellet without causing the DRI to lose too much active material in the acid etching solution.

[0163] In another embodiment, the desired impurities or additives are integrated into the DRI. When these impurities are solid, they can be integrated into the powder additive together with the DRI pellets by ball milling (for example, using a planetary ball mill or similar equipment), and the pellets act as their own grinding media. The powder additive is mechanically introduced into the pores or surface of the DRI pellets in this way. The DRI can also be coated with beneficial additives, for example, by rolling or dipping in a slurry containing the additives. These desired impurities can include alkali sulfide. Alkali sulfide has been shown to greatly improve the utilization of active materials in the Fe anode. Just as soluble alkali sulfide can be added to the electrolyte, insoluble alkali sulfide can be added to the DRI, for example by the above method.

[0164] In various embodiments, the specific surface area of ​​the DRI is increased by a factor of 3 or more, preferably by a factor of 5 or more, as measured by techniques such as Brunauer-Emmett-Teller gas adsorption. In some embodiments, the increase in surface area is achieved by using the DRI as an electrode in an electrochemical cell and electrochemically reducing it by an applied current.

[0165] In some embodiments, the surface area of ​​a material comprising cementite or iron carbide (e.g., a DRI pellet containing cementite or iron carbide) is increased by using the material as an anode of an electrochemical cell and discharging it. In certain embodiments, the specific current density can be 0.1 mA / g to 25 mA / g. Such high surface area iron oxides can also be used in a variety of applications other than electrochemical cells.

[0166] In multiple embodiments, in order to increase conductivity, the pellets can be mixed with more conductive but potentially more expensive powders to produce a higher conductivity composite bed. The powder can increase the area capacity of the battery cell by filling the gaps between the pellets. This can reduce the ratio of the electrolyte volume to the DRI pellets in a systematically changed and optimized manner. In one embodiment, the powder is used in the current collecting part to increase the contact surface area, reducing the interfacial resistivity between the current collector and the small contact area of ​​the spherical pellets, as described in more detail in the previous section. This ensures the ability to change and control the effective current density of the pellets. Changes in particle size in the composite bed can produce controllable costs and conductivity. In another example, the use of additional powders, wires, meshes, yarns or wool fabric conductive materials enables the use of low conductivity pellets in the composite bed by increasing the overall conductivity, such as DR taconite pellets or direct reduction pellets that are not fully metallized (sometimes referred to as "remet" in the industry). In one embodiment, the conductive part can include DRI fines or other waste materials from the DRI process.

[0167] The ratio of electrolyte to iron material (such as DRI material) in the battery cell can be about 0.5 mL 电解质 : 1g 铁材料 To about 5mL 电解质 : 1g 铁材料 , about 0.6mL 电解质 : 1g 铁材料 To about 3mL 电解质 : 1g 铁材料 , about 0.6mL 电解质 : 1g 铁材料 , about 0.7mL 电解质 : 1g 铁材料 , about 0.8mL 电解质 : 1g 铁材料 , about 1mL 电解质 : 1g 铁材料 and their combinations and variations and greater and smaller ratios.

[0168] In one embodiment, the porous sintered iron electrode can be formed from DRI, which can be reduced in particle size or made into a powder, for example by crushing or grinding. DRI fines or other waste materials can also be used to form the sintered iron electrode. The sintered electrode can be formed with a binder under heat and / or pressure, and then the binder can be burned out and the green body sintered at high temperature. It is also possible to directly fuse the DRI pellets together by sintering in a non-oxidizing atmosphere without the use of a binder, optionally with the application of pressure, to establish electrical and physical connectivity between the pellets.

[0169] In various embodiments, a porous negative electrode can be formed by crushing, shredding or grinding hot briquette iron (HBI). In various embodiments, HBI is preferred for shipping and transportation due to its lower surface area and reactivity, but the porosity of HBI may be too low for practical use in thick electrodes due to ion transport limitations. In order to achieve the best combination of transport and performance, DRI can be transported in briquettes to the site of cell assembly or manufacturing, where the DRI is crushed, ground and / or shredded to increase the porosity of the resulting electrode.

[0170] A packed bed of DRI pellets may be an ideal configuration for an iron-based electrode because it provides a conductive percolation path through the packed bed while leaving porosity that can be occupied by an electrolyte that promotes ion transport. In certain embodiments, the ratio of electrolyte volume to DRI mass can range from 0.5 mL / g to 5 mL / g, such as 0.6 mL / g or 1.0 mL / g. DRI pellets are typically in contact with surrounding pellets through a small contact area compared to the surface area of ​​the pellets, and in some cases, the contact can be considered a "point contact." Small cross-sectional contacts may limit current flow, which may result in relatively low conductivity throughout the pellet bed, which in turn may result in high electrode overpotential and low voltaic efficiency for the battery.

[0171] In various embodiments, the conductivity of the DRI pellet bed can be increased in various ways. In some embodiments, the conductivity of the DRI pellet bed can be increased by using additional conductive materials, which can surround individual pellets, be embedded in individual pellets, surround the entire pellet bed, or penetrate the pellet bed. The conductive material can be one or more of a metal, a metal oxide, a metal carbide, a metal nitride, a semiconductor, carbon, a conductive polymer, or a composite comprising at least one such conductive material. The conductive material can be in the form of a powder, a wire, a mesh, or a sheet. In certain embodiments, the conductive material itself can participate in the electrochemical reactions in the battery, including but not limited to providing storage capacity. In certain other embodiments, the conductive material is substantially electrochemically inactive. In one embodiment, the conductive material is a powder, and the powder fills or partially fills the space between the pellets or between the pellets and the current collector to improve the conductivity between the pellets or between the pellets and the current collector. For example, the conductive powder can be composed of DRI "fines", which is a powdered waste product of the direct reduction process, and its composition is similar to DRI. In this case, the fine powder can be used to increase the conductivity of the bed and increase the storage capacity of the anode. In another embodiment, the conductive material is a powder, and the powder is applied to the surface of the pellets to form a coating. Such a coating provides a larger area for electrical contact between the pellets.

[0172] In a number of embodiments, a conductive coating is applied to a low conductivity pellet to enable it to be used in an electrode. In certain embodiments, a low conductivity pellet, such as an under-metallized (sometimes referred to as "remet" in the industry) taconite pellet or a direct reduction pellet may be coated. The coating may be conductive to reduce the resistance from the current collector to the taconite pellet during the initial reduction step. During or after the reduction step, the coating may or may not be removed. In one embodiment, the coating is a thin conformal metal layer, such as stainless steel, which is wrapped around each pellet in a circumferential direction. In another embodiment, the coating is a thin lead layer that is coated on the outside of each pellet using a directional deposition technique such as sputtering, evaporation or other physical vapor deposition techniques. In certain embodiments, the coating is applied by rolling the DRI and coating material together in a rotating container. In certain embodiments, the DRI in the rotating container is substantially spherical.

[0173] In another embodiment, some or all of the individual pellets in the pellet bed are wrapped by conductive wire, foil or sheet. In some embodiments, tension is applied to the wire, foil or sheet using a tensioning mechanism such as a screen. Optionally, this current collector around the individual pellets can be attached to a gathered wire or connected to a larger current collector. In another example, a conductive mesh, yarn or wool fabric is spread in the space between the DRI pellets to increase electrical connection. In multiple embodiments, the conductive material is a mesh with an opening (net size), and the opening is selected to be smaller than the pellets so that the pellets will not pass through the mesh. In this case, the conductive material can be stainless steel, nickel or other metals and metal alloys. In another example, the DRI pellets are directly connected to each other by passing through or around individual pellets through a wire. For example, a wire can be passed through a hole in the DRI pellets, similar to forming a string of beads, resulting in not only electrical contact between the pellets, but also electrical contact inside the pellets. Optionally, an electrical terminal or "plug" can be used to keep the pellet string in contact, and tension is optionally applied to the wire at the electrical terminal or "plug". The electrical terminals may optionally be electrically connected to a larger current collecting device, such as a plate.

[0174] In another embodiment, the conductivity of the pellet bed can be improved by applying a compressive load to the DRI pellet bed anode to increase the inter-pellet force and / or the contact area between the pellets or the contact area between the pellets and the current collector, thereby reducing the contact resistance and enhancing the electrochemical performance. Typical DRI pellets are approximately spherical, have internal pores, and can be elastically deformed to >5% linear strain before yielding. Applying a load to compress the DRI bed can increase the effective contact area between the pellets and the interface between the pellets and the current collector. It is advantageous to use pellets with a yield strain that allows deformation to achieve the desired increase in conductivity without breaking. In one embodiment, pellets with a compressive strength of 700 psi to 2500 psi are used in a pellet bed electrode to which a compressive load is applied. In addition, a mechanical component that provides a compressive load on the pellet bed can also be used as a current collector. The resistance of such a pellet bed (measured in a dry state before filling with a liquid electrolyte) can be reduced by two to 100 times or more by applying a compressive load. In certain embodiments, the range of the applied load can be from 0.1psi to 1000psi, such as 50psi or 100psi. In certain embodiments, the range of the applied load can be from 0.1psi to 10psi, such as 1psi or 5psi. In one example, the metal plates on the opposite sides of the granule bed are used to provide current collection and compression loads on the granule bed. Optionally, one or more of the plates can be replaced with macroporous current collectors (e.g., metal mesh) to promote the transport of ions throughout the electrode. Relative current collectors are preferably connected so that they are at the same potential, thereby facilitating the electrochemical reaction rate of the entire electrode to be more uniform. In another example, the container containing the granule bed is used as both a current collector and a method for applying a compressive load. In another embodiment, an array of conductive posts (or rods) connected to a common, bottom-facing current collector is used. Therefore, many current collection areas can be placed throughout the granule bed. The method can also reduce the effective transport length from the total granule bed thickness to the inter-column spacing in the electrode. Additionally, these posts can be used to secure a mechanical clamping mechanism, such as a plate or perforated plate, on top of the pellet bed to incorporate a downward force onto the pellet bed while acting as a current collecting element.

[0175] In some embodiments, the compressive load can be provided in part or in whole by magnetic force. For example, a permanent magnet located on one or more sides of the bed can be used to apply force so that the pellets in the bed are attracted by the magnet. For a bed of DRI pellets mainly composed of metallic iron, it is expected that the pellet bed is mainly ferromagnetic and the pellet bed will be attracted by the magnet. Magnets can also be embedded in other fixtures around the pellet bed. Magnets and fixtures are used to hold the pellet bed in place and provide compressive stress, resulting in improved electrical contact between pellets and between pellets and current collectors as described above.

[0176] In some embodiments, inter-agglomerate contact resistance in an aggregate bed can be reduced by using a pretreatment applied to the aggregate bed prior to battery assembly and / or battery operation. Several such pretreatment processes are described in the following paragraphs.

[0177] In some embodiments, the entire DRI pellet is filled into the bed and sintered in an inert atmosphere or a reducing (i.e., non-oxidizing) atmosphere, and mechanical pressure is optionally applied during the sintering process, for example, using a material that is stable at the sintering temperature and atmosphere. The sintering temperature may range from 600°C to 1100°C. The non-oxidizing atmosphere may be composed in part or in whole of an inert gas (e.g., nitrogen or argon). The non-oxidizing atmosphere may also include a gas mixture that tends to reduce iron, such as CO and CO2 and H2 and H2O. The exact composition of the mixture may be optimized according to the Ellingham diagram to ensure that the oxidation of iron is thermodynamically unfavorable. In one embodiment, a forming gas (5% H2, 95% N2) is used at a sintering temperature of about 600°C to about 1100°C (e.g., 600°C to about 850°C, 850°C, about 850°C to about 1100°C, etc.) to provide non-oxidizing conditions. The combination of high temperature and non-oxidizing atmosphere may promote atomic diffusion and pellet coarsening at pellet contacts, resulting in pellets bonding to each other. The result is a bed of DRI pellets fused together with low inter-pellet contact resistance. The pellets can also be fused to a current collector by the same method.

[0178] In another embodiment, the pellets are combined using a heat treatment, wherein a flux or sintering aid is used to significantly reduce the heat treatment temperature required to form sintering necks between the pellets. Examples of flux or sintering aids include one or more metals with a lower melting point than iron, such as zinc, tin, copper, aluminum, bismuth, and lead, or metals that form alloys with iron and have a lower melting point than iron (e.g., metals that exhibit a low melting point eutectic liquid). Other examples of sintering aids include one or more glass-forming compositions, including but not limited to silicates, borates, and phosphates.

[0179] In another embodiment, the pellets can be electrically fused together by a process such as welding. In some such embodiments, welding is accomplished by passing an electric current through a bed of pellets. In some such embodiments, such an electric current is delivered by discharging a capacitor.

[0180] In a number of embodiments, the anode electrode is an ordered array of pellets. In certain embodiments, the pellets are arranged into a cylinder. In certain embodiments, the pellets are arranged into a plate. In certain embodiments, the pellets are arranged into a disk. In certain embodiments, the pellets are arranged into a rectangular prism. In certain embodiments, the pellets are arranged into a hexagonal prism. In certain embodiments, the pellets are arranged into an arbitrary volume.

[0181] In multiple embodiments, an electrolyte management system may be provided in which different electrolyte additives or formulations are added to the battery when switching between operating states. The optimal electrolyte formulation for operation in battery charging, discharging, and idle states may be very different. The electrolyte management system of multiple embodiments can improve the capacity utilization of the iron electrode, the self-discharge of the battery cell, and inhibit the hydrogen evolution reaction (HER). One or more of these benefits can be achieved simultaneously. In one embodiment of such an electrolyte management system, any number of different electrolyte formulation reservoirs are provided, each reservoir being connected to the electrochemical cell via a separate flow controller. At different operating stages, different relative amounts of each electrolyte formulation flow into the battery cell based on the optimal concentration of the constituent substances for the transient operating mode (charging, discharging, idle). The electrolyte management system can be configured to adjust the electrolyte composition based on the transient state of battery charging.

[0182] Multiple embodiments can provide methods and instruments for maintaining the level of liquid electrolyte in a battery. When a container containing water is exposed to air, evaporation will occur until the partial pressure of water vapor in the air is equal to the vapor pressure of water at the system temperature. Specifically, this same evaporation will occur in electrochemical systems where aqueous electrolytes are exposed to the environment. Dehydration of the electrolyte can cause problems due to the reduction in electrolyte volume, and changes in electrolyte concentration can change electrochemical performance. To alleviate this problem, in multiple embodiments, the level of the electrolyte can be maintained by a constant or intermittent inflow of the electrolyte into the cell volume. Specifically, the electrolyte level can be maintained by introducing the electrolyte into the container until it flows out of the overflow point. Since the liquid level cannot rise above the overflow point, the liquid level can be maintained in a relatively controlled manner. Specifically, multiple volumes can be arranged in cascade so that the overflow from one chamber can flow into the next chamber, thereby establishing "liquid communication" between the cells. Connecting these cells in series allows one source to supply liquid electrolyte to multiple cells simultaneously. The overflow from the final container can be recycled to the first container. In systems utilizing shared electrolytes, where electrolytes flow in a cascade between cells, electrolyte properties can be monitored and manipulated at a central location across many cells. To mitigate issues associated with electrolyte carbonation, electrolyte dehydration, etc., electrolyte adjustments, such as composition adjustments or additions, can be advantageously made at this collected source of circulating electrolyte.

[0183] Various embodiments can provide compositions and methods for adding beneficial additives to the electrolyte of aqueous electrochemical cells. During the charging process of aqueous secondary cells, the electrolytic production of hydrogen can lead to low Coulombic efficiency, gas accumulation in the cell housing, safety issues, and consumption of electrolyte. In addition, self-discharge of metal electrodes can occur through the spontaneous reaction of the metal with the electrolyte to form a metal hydroxide, in which hydrogen is produced as a product. Certain solid-phase hydrogen evolution inhibitors (e.g., Bi, Sb, As) can reduce these deleterious effects, but integrating solid-phase inhibitors into porous metal electrodes of batteries can be expensive and difficult to manufacture. Therefore, in various embodiments, a soluble salt of the desired hydrogen evolution inhibitor is added to the liquid electrolyte to dissolve to provide the desired additive ions in the solution (e.g., Bi 3+ , Sb 3+ 、As 3 + ). The additive is selected so that the redox potential of the inhibitor ion-metal plating reaction (e.g. Bi 3+ →Bi 0 ) occurs at a higher half-cell potential (measured relative to RHE) than the charge reaction potential of the anode active material (but at a lower cell potential). Therefore, during battery charging (reduction of the metal electrode), the HER inhibitor in ionic form is electrodeposited onto the surface of the metal electrode, providing an inexpensive and simple strategy for introducing HER inhibitors into the battery electrolyte chemistry. The electrodeposited inhibitor suppresses the hydrogen evolution reaction on the electrode surface, which can be an electrode with open pores. In discharge mode, the deposit may dissolve back into the electrolyte. The salt addition is preferably selected so that it does not degrade the operation of the cathode during charge or discharge operation.

[0184] In another embodiment, the electrochemical cell includes an electrode on which a hydrogen oxidation reaction (HOR) is performed to capture hydrogen produced in the HER side reaction, thereby mitigating the escape of potentially dangerous hydrogen. Hydrogen bubbles produced during the HER process may be captured and exposed to the HOR electrode, which may be a working electrode of the battery cell or an additional electrode added to the system. In one embodiment, hydrogen is captured by arranging the electrodes of the cell so that buoyancy brings hydrogen bubbles to the HOR electrode. For example, the system can be tilted or include a funnel designed to facilitate such flow.

[0185] In various embodiments, a liquid electrolyte is flowed through a collection of DRI pellets or a bed of DRI pellets. For thick (up to several centimeters) battery electrodes composed of active material pellets, it may be challenging to achieve sufficient transport of reactants, reactant products, and additives through a thick bed within a time scale commensurate with the battery operation (charging and discharging) time scale. Insufficient transport rates in the electrolyte can produce a variety of adverse effects, including but not limited to increasing overpotential losses in pellet-based electrodes and reducing the utilization of active materials. In metal electrode batteries with alkaline electrolytes, bubble formation and pH gradient formation under charging and discharging conditions may lead to undesirable performance degradation or corrosion in one or both electrodes. In various embodiments, a liquid electrolyte is flowed through a bed of DRI pellets to reduce the adverse effects of limited transport. The flow of the electrolyte produces convective transport of individual pellets of the electrolyte. Among other benefits, electrochemical reaction rates and reaction uniformity can be improved by reducing the electrolyte concentration boundary layer, which can pass through the thickness of the entire pellet bed or appear in the macropores in the pellet bed. Electrolyte flow generally reduces overpotential losses by homogenizing the electrolyte composition throughout the macrostructure and microstructure of the electrode. In some embodiments, active methods (e.g., mechanical pumps) are used to achieve electrolyte flow. The flow rate of the electrolyte can be very low, as low as 1 mL / min / cm 2 or lower. In other embodiments, the electrolyte flow is achieved by passive means, such as buoyancy-driven flow due to thermal gradients or composition gradients. In a specific example, the portion of the battery where resistive heat dissipation occurs is located at or near the bottom of the electrode bed, causing the electrolyte to be heated and rise through the bed of aggregates. In another specific example, an electrochemical reaction in an electrode within the battery changes the electrolyte density, such as by an exothermic reaction or an endothermic reaction or a change in the composition of the electrolyte in contact with the electrode, thereby producing buoyancy-driven flow. In this example, the electrode reaction that produces a lower density electrolyte can be located at or near the bottom of the DRI aggregate bed, and the reaction that increases the electrolyte density can be located at the top of the aggregate bed.

[0186] In some embodiments, additives that inhibit side reactions (e.g., corrosion inhibitors that inhibit HER reactions or inhibit self-discharge) are combined with additives that improve capacity utilization. Additives to battery electrolytes that include metal electrodes (including iron electrodes) can advantageously perform several functions, including increasing the capacity utilization of iron, inhibiting undesirable side reactions, or both. Different additives have different advantages, and these advantages can be combined by combining additives at appropriate concentrations. An example of an additive that improves utilization is sulfur or sulfide. In some embodiments, more than one corrosion inhibitor can be used with one or more sulfides. For example, sulfur helps to depassivate iron electrodes, but it will be consumed during the electrochemical cycle of the battery. Therefore, after multiple cycles, the consumption of sulfur may cause a decrease in capacity. In one embodiment, a delivery system is used to replenish sulfur to maintain battery performance. An example of such a system is a pump that delivers a sulfur-containing liquid to a battery cell. Another example is a drying hopper that delivers polysulfide salts to a closed or open battery cell.

[0187] In one embodiment, iron sulfide (FeS) can be added to a metal-air battery using an alkaline electrolyte as a sparingly soluble additive to improve the electrochemical stability of the OER electrode and extend the electrode life. This embodiment helps mitigate the degradation of catalyst performance on the oxygen evolution reaction (OER) electrode under alkaline conditions, which can limit the operating life of the electrode.

[0188] In certain embodiments, sulfur can be added to the DRI by additional process operations. In certain embodiments, the low melting temperature of sulfur can be utilized to immerse the DRI in a bath of molten sulfur. In certain other embodiments, hydrogen sulfide gas can flow through hot DRI or cold DRI to deposit a layer of sulfur and / or a layer of iron sulfide on the surface of the DRI. In certain other embodiments, sulfur can be sublimated and vapor deposited on the surface of the DRI; the DRI can be hot or cold. In certain embodiments, sulfur is melt diffused into the pores of the DRI by melting the sulfur and then wicking it into the pores of the DRI.

[0189] In some embodiments, sulfur can be added to DRI by a wet deposition process involving a process solvent. In certain embodiments, a colloidal mixture can be used to deposit sulfur or sulfide (e.g., FeS) materials on or in DRI. For example, a dispersion of sulfur in water can be prepared by ultrasonic treatment, and DRI is subsequently added thereto. Water can be evaporated to deposit sulfur or sulfide materials on the surface of DRI pellets and inside DRI pellets. In certain other embodiments, sulfur can be dissolved in an organic solvent (e.g., ethanol or acetone). DRI is added to the solution, and the solvent is subsequently evaporated to obtain a sulfur coating.

[0190] In some embodiments, an additive comprising molybdate ions is used in an alkaline battery comprising an iron anode. Without being limited to any particular scientific explanation, such additives can help suppress the hydrogen evolution reaction (HER) at the iron electrode and improve the cycle efficiency of the battery. The concentration of the additive is selected to be able to suppress HER while still being able to carry out the desired iron charging process / iron discharging process. As an example, molybdate ions can be added via a molybdate compound such as KMoO4. In a specific example, the electrolyte comprises 10 mM (mM is millimole, 10 -3 In other embodiments, the electrolyte comprises an additive concentration of molybdate anions ranging from 1 mM to 100 mM.

[0191] In some embodiments, surfactants are used to control wetting and foaming during the operation of metal-air batteries. During the charging process, at least two gas evolution reactions that lead to bubble formation may occur. One is hydrogen evolution at the metal anode, which is a parasitic reaction that may lead to a decrease in coulombic efficiency during battery cycling. The other is the oxygen evolution reaction necessary for the function of the metal-air battery. Surfactant additives can alleviate the adverse effects associated with the two reactions. In the case of HER, hydrophobic surfactant additives can inhibit the hydrogen evolution reaction of the metal anode by physically blocking water (HER reactants) from entering the metal anode during charging. In the case of ORR, surfactant additives can reduce the surface tension and viscosity of the electrolyte at the oxygen evolution electrode, thereby generating smaller, uniformly sized and controllable bubbles during charging. In a non-limiting example, 1-octanethiol at a concentration of 10mM is added to an alkaline electrolyte to alleviate these two difficulties.

[0192] In some embodiments, carbonate is added to the electrolyte of the metal-air battery using alkaline electrolyte to reduce the rate of carbon dioxide absorption from the air. In the air, the electrolyte based on potassium hydroxide or sodium hydroxide will form potassium carbonate or sodium carbonate by reacting with carbon dioxide (CO2) present in the air, and lose potassium cations or sodium cations from the solution. This is especially problematic for batteries with air electrodes because ambient air provides the required reactant (oxygen) in the lowest cost form to the oxygen reduction reaction (ORR) electrode. Electrolyte carbonation can cause several adverse effects on battery performance associated with undesirable side reactions and reduced electrolyte conductivity, all of which can lead to reduced operating efficiency of the battery. However, as the carbonate concentration in the electrolyte increases, the rate of carbonate formation slows down significantly. In one embodiment, carbonate is intentionally added to the electrolyte before operation to reduce the rate of carbonation reaction of the battery with air during operation. Intentionally added carbonate can mitigate the harmful effects of carbonation and maintain acceptable carbonate levels in the electrolyte over a longer operating life.

[0193] In one embodiment, the health of the electrolyte in the metal-air battery is monitored periodically or continuously. The aging and quality of the electrolyte can significantly affect the electrochemical performance of the iron-air battery. In some cases, the degradation of performance is related to the negative electrode (e.g., the iron electrode). Generally, as the electrolyte ages, the discharge capacity of the negative electrode decreases. This may be the result of changes in the concentration of electrolyte components over time due to spontaneous reactions to form undesirable products (especially those formed due to exposure to air). In some embodiments, the health of the electrolyte is monitored during battery operation to determine the appropriate time to replenish, replace or treat the electrolyte. The feedback mechanism can be manual or automatic. In an automated system, the electrolyte quality measurement can be used as an input to a proportional integral differential (PID) loop that continuously adjusts the concentration of the electrolyte components. The electrolyte quality measurement is done ex situ on a small portion of the electrolyte, or on an active electrolyte while the cell is running. A non-limiting method for assessing the health of the electrolyte is to measure the conductivity of the electrolyte. One mechanism of degradation is due to the dissolution of CO2 from the air into the electrolyte, resulting in carbonization of the electrolyte over time. In a specific example, an experiment was conducted to show that the electrolyte conductivity changes linearly with the carbonate concentration in the electrolyte. Conductivity probes are used to assess the concentration of carbonates in electrolytes. Conductivity probes are used to monitor the health of electrolytes.

[0194] In some embodiments, corrosion inhibitors used in the field of iron and steel metallurgy to inhibit water corrosion are used as part of a battery with an iron negative electrode to improve performance. In some embodiments, direct reduced iron (DRI) is used as a negative electrode, and favorable performance characteristics can be obtained by using one or more corrosion inhibitors in a suitable concentration range. In these embodiments, the principles of corrosion science are used to prevent undesirable side reactions (e.g., hydrogen evolution) from occurring under charging conditions, mitigate the spontaneous self-discharge rate during electrochemical maintenance, and maximize the utilization of iron active materials during discharge. In general, there are two types of corrosion inhibitors: interface inhibitors that react with metal surfaces at the metal-environment interface to prevent corrosion, and environmental scavengers that remove corrosive elements from the environment around the metal surface to inhibit corrosion. Under the broad protection of corrosion inhibitors, inhibitors of appropriate concentrations can be added to electrochemical cells to obtain performance characteristics that are favorable to the efficiency and capacity of electrochemical cells. For the iron electrode of a metal-air battery, a class of applicable universal inhibitors is liquid and interphase interface inhibitors. This category includes three main types of interface inhibitors: anode inhibitors, cathode inhibitors, and mixed inhibitors. Anode inhibitors can form a passivation layer that inhibits the dissolution reaction of anode metals. Cathodic inhibitors may reduce the rate of the reduction reaction (HER in the case of an iron electrode), or precipitate at the cathode active sites to block the same reduction reaction. Mixed inhibitors may inhibit corrosion by one or both pathways, and include, but are not limited to, molecules that physically or chemically adsorb on the metal surface to form a film that blocks the active sites for the reduction reaction. Inhibitors may be added to the base electrolyte at any concentration.

[0195] In various embodiments, an inhibitor that forms a passivation layer on the metal surface is paired with an additive that depassivates the iron surface. At the correct concentration, an optimal balance of corrosion inhibition and active material utilization can be achieved. In a specific embodiment, when direct reduced iron is used as the negative electrode, 10 mM molybdate anions are used as passivating agents and 10 mM sulfide anions are used as depassivating agents in an alkaline electrolyte consisting of 5.5 M potassium hydroxide or 5.5 M sodium hydroxide. Specific examples of electrolyte compositions include: 5.5M KOH + 0.5M LiOH + 10mM Na2S + 10m M 1-octanethiol; 5.95M NaOH + 50mM LiOH + 50mM Na2S + 10mM 1-octanethiol; 5.95M NaOH + 50mM LiOH + 50mM Na2S + 10mM 1-octanethiol + 10mM K2MoO4; and 5.95M NaOH + 50mM LiOH + 50mM Na2S + 10mM K2MoO4. However, the present disclosure is not limited to any specific concentration of the additives in the above electrolytes. For example, the electrolyte may include one or more of the above additives in a concentration range of about 2mM to about 200mM, such as about 5mM to about 50mM or about 5mM to about 25mM.

[0196] In certain embodiments, other electrolyte additives are incorporated into the electrolyte. The electrolyte additive may be selected from the following non-limiting group: sodium thiosulfate, sodium thiocyanate, polyethylene glycol (PEG) 1000, trimethylsulfoxide iodide, zincate (by dissolving ZnO in NaOH), hexanethiol, decanethiol, sodium chloride, sodium permanganate, lead (IV) oxide, lead (II) oxide, magnesium oxide, sodium chlorate, sodium nitrate, sodium acetate, ferric phosphate, phosphoric acid, sodium phosphate, ammonium sulfate, ammonium thiosulfate, lithopone, magnesium sulfate, iron (III) acetylacetonate, hydroquinone monomethyl ether, sodium metavanadate, sodium chromate, glutaric acid, dimethyl phthalate, methyl methacrylate, methylpentynol, adipic acid, allyl urea, citric acid, thiomalic acid, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, propylene glycol, trimethoxysilane Alkyldiethylene, aminopropyl trimethoxysilane, dimethyl acetyl dicarboxylate (DMAD), 1,3-diethylthiourea, N,N'-diethylthiourea, aminomethyl propanol, methyl butynol, amino modified organosilane, succinic acid, isopropanolamine, phenoxyethanol, dipropylene glycol, benzoic acid, N-(2-aminoethyl)-3-aminopropyl, behenic acid amide, 2-phosphonobutane tricarboxylic acid, boric acid mipa salt, 3-methacryloyloxypropyl trimethoxysilane, 2-ethylhexanoic acid, isobutyl alcohol, tert-butylaminoethyl methacrylate, diisopropanolamine, propylene glycol n-propyl ether, sodium benzotriazole, pentasodium aminotrimethylenephosphonate, sodium cocoyl sarcosinate, lauryl pyridinium chloride, steartrimonium chloride chloride), stearalkonium chloride, calcium montanate, quaternary ammonium-18 chloride, sodium hexametaphosphate, dicyclohexylamine nitrite, lead stearate, calcium dinonylnaphthalene sulfonate, iron (II) sulfide, sodium hydrosulfide, pyrite, sodium nitrite, complex alkyl phosphates (such as RA 600 emulsifier), 4-mercaptobenzoic acid, ethylenediaminetetraacetic acid, ethylenediaminetetraacetate (EDTA), 1,3-propylenediaminetetraacetate (PDTA), nitrilotriacetate (NTA), ethylenediamine disuccinate (EDDS), diethylenetriaminepentaacetate (DTPA) and other aminopolycarboxylates (APC), diethylenetriaminepentaacetic acid, 2-methylbenzenethiol, 1-octanethiol, bismuth sulfide, bismuth oxide, antimony (III) sulfide, oxide Antimony (III), antimony (V) oxide, bismuth selenide, antimony selenide, selenium sulfide, selenium (IV) oxide, propargyl alcohol, 5-hexyn-1-ol, 1-hexyn-3-ol, N-allylthiourea, thiourea, 4-methylcatechol, trans-cinnamaldehyde, iron (III) sulfide, calcium nitrate, hydroxylamine, benzotriazole, furfurylamine, quinoline, tin (II) chloride, ascorbic acid, tetraethylammonium hydroxide, calcium carbonate, magnesium carbonate, antimony dialkylphosphorodithioate, potassium stannate, sodium stannate, tannic acid, gelatin, saponin, agar, 8-hydroxyquinoline, bismuth stannate, potassium gluconate, lithium molybdate, potassium molybdate, hydrogenated light petroleum, heavy naphthenic petroleum (e.g., as 631), antimony sulfate, antimony acetate, bismuth acetate, hydrogenated heavy naphtha (e.g., as For sale), tetramethylammonium hydroxide, NaSb tartrate, urea, D-glucose, C6Na2O6, potassium antimony tartrate, hydrazinsulfate, silica gel, triethylamine, potassium antimonate trihydrate, sodium hydroxide, 1,3-di-o-tolyl-2-thiourea, 1,2-diethyl-2-thiourea, 1,2-diisopropyl-2-thiourea, N-phenylthiourea, N,N'-diphenylthiourea, sodium L-antimony tartrate, disodium rose palm acid, sodium selenide and combinations thereof.

[0197] In certain embodiments, the electrolyte is gelled. In certain embodiments, silicon dioxide (SiO2) or other oxides forming a network (e.g., boron oxide (B2O3) or aluminum oxide (Al2O3) are dissolved in an alkaline liquid to form a gel. In certain embodiments, organic molecules forming a network are dispersed in a liquid electrolyte to form a gel electrolyte. In certain embodiments, the organic molecules include polymers. In certain embodiments, a liquid electrolyte is added to a solid polymer (e.g., polyethylene oxide (PEO), polyvinyl alcohol (PVA), polyacrylamide (PAM) or polyacrylic acid (PAA)) to form a gel electrolyte. Bio-derived polymers (e.g., cassava or gelatin) can also be used as polymer additives. In certain embodiments, a gel electrolyte is formed in situ by dissolving silicon dioxide (or other oxides) from DRI. In certain other embodiments, additional gel forming agents are intentionally added to the liquid electrolyte in order to produce a gel. In certain embodiments, a gel electrolyte is formed in situ due to evaporation of a solvent (e.g., water) from the electrolyte, concentrating the dissolved salts and converting the electrolyte from a liquid to a gel or supersaturated solution.

[0198] In some embodiments, the electrolyte is a semi-solid or slurry electrolyte. In some embodiments, the liquid is supersaturated with salt, and the electrolyte is a two-phase mixture of solid salt and saturated solution. In some embodiments, the electrolyte can be a saturated solution of NaOH in water and an additional dispersed solid phase of NaOH, which together form a slurry electrolyte. Such an electrolyte can have mechanical properties similar to gels.

[0199] In certain embodiments, the electrolyte additive is delivered to the electrode as a solid mixture. The electrolyte additive may have a range of solubility, and some electrolyte additives may have the most beneficial effect when they are intimately mixed with the solid electrode. In one embodiment, the solid pellets are primarily composed of the additive, and these additive pellets are added to or mixed with the metal electrode, which in one embodiment includes a plurality of DRI pellets. In another embodiment, the electrolyte additive is mixed with a metal that may be a redox active electrode, and the pellets made from the mixture are mixed with the metal electrode, which in one embodiment includes a plurality of DRI pellets. Non-limiting examples of additives include sodium sulfide (Na2S), potassium sulfide (K2S), lithium sulfide (Li2S), iron sulfide (FeS x, wherein x = 1-2), bismuth sulfide (Bi2S3), lead sulfide (PbS), zinc sulfide (ZnS), antimony sulfide (Sb2S3), selenium sulfide (SeS2), tin sulfide (SnS, SnS2, Sn2S3), nickel sulfide (NiS), molybdenum sulfide (MoS2) and mercury sulfide (HgS), FeS, bismuth oxide (Bi2O3), combinations thereof, etc. In some embodiments, pellets having different ratios of redox active metals and additives are prepared, and pellets of different compositions are mixed to produce a mixed electrode.

[0200] In some embodiments, an electrochemical formation cycling scheme is used to change the properties of the starting DRI pellets and improve the subsequent electrochemical performance of the DRI in operation as an anode. The DRI pellets made may not be in a form optimized for electrochemical cycling in a battery. For example, native oxides may be present on the free surface of the DRI, hindering electrochemical contact with the active material; the specific surface area may be too low to achieve the desired specific capacity; and / or the pore structure may restrict ion transport and limit the specific capacity. In a specific embodiment, the initial cycle, referred to as "formation", consists of one or more repetitions of one or more of the following steps. One step may be a short charging step ("pre-charge"), during which any native oxide layer that adversely passivates the as-is DRI can be chemically reduced, or the specific surface area of ​​the DRI pellets can be increased, in some cases by up to 10 times. These changes may increase the available capacity of the DRI in subsequent discharges. Another step may be a discharge step that oxidizes metallic iron until the conversion from Fe to Fe 2+ Or from Fe 2+ To Fe 3+ One or more reactions are completely or partially completed. The charge capacity and discharge capacity may not be the same between repetitions of the formation cycle. In some embodiments, the formation may include repeated pre-charge and discharge cycles that systematically increase the capacity. In a specific embodiment, the formation cycle includes the following steps: pre-charge to a capacity of 250 mAh / g, then cycle n times the following loop: discharge to 25+n*25 mAh / g, then charge to (25+n*25)*1.1 mAh / g, where n is the number of cycles. The pre-charge step increases the specific surface area of ​​the DRI from about 0.5 m 2 / g increased to 12m 2 / g or more, which can enhance the available capacity for subsequent discharge. The remaining formation cycles are carried out in n cycles, with an increasing capacity increment of 25mAh / g (assuming a Coulombic efficiency of 90%), gradually approaching the charge and discharge capacity corresponding to the deep cycle.

[0201] In some embodiments, a specific operation strategy is used to control the potential of the negative electrode charge. During the charging process of the iron-air battery, the iron reduction reaction and the parasitic hydrogen evolution reaction are expected to occur simultaneously within a large potential range, but the relative rate of each reaction depends on the potential. In some potential cases, the hydrogen evolution reaction will be thermodynamically and / or kinetically favorable, while in other cases, the iron reduction reaction will be favorable. Strategies involving adjusting the working potential of the negative electrode during charging include but are not limited to the following strategies. For example, in one strategy, the negative electrode is charged at a current rate higher than its discharge rate. This may be affected under constant current, constant power or other more complex cycle conditions. By charging at a greater rate than during the discharge process, the electrode can be driven to a potential that is thermodynamically and / or kinetically favorable for iron reduction rather than parasitic reactions (e.g., hydrogen evolution). The result is a higher coulombic efficiency and a higher electrode utilization in multiple cycles. As another example, in another strategy, the negative electrode is charged at a constant potential rather than a constant current or constant power. The charging potential is selected to optimize electrochemical performance. For example, the charging potential can be optimized to maximize coulombic efficiency and obtain a higher electrode utilization. As another example, in another strategy, the effective resistance of other battery core parts (i.e., non-solid Fe electrodes or negative electrode current collectors) is increased. By doing so, a greater overall battery polarization is achieved, which results in a greater polarization of the negative electrode. If the additional negative electrode polarization is large enough, the absolute potential of the Fe electrode can become low enough to favor iron reduction rather than hydrogen evolution reaction. The effect can be achieved by increasing the effective resistance of the electrolyte, cathode, or cathode current collector.

[0202] In some embodiments, the self-discharge of the negative electrode is limited by using a passivating chemical layer on the metal anode, which is optionally used with one or more electrical pulses during the charging process. The metal anode (e.g., Fe, Al, Zn) in alkaline batteries usually self-discharges through corrosion reactions, forming hydrogen and metal hydroxides as products of the self-discharge corrosion reaction. Generally, passivating electrolyte additives are considered unnecessary for slowing down self-discharge because the passivating layer also makes the metal anode unreactive in the desired discharge reaction. According to this embodiment, an electrolyte additive (e.g., Na2MoO4) is used to form a thin passivating film. Therefore, the self-discharge of the anode is limited to a small layer on the surface of the anode. However, in order to restore the reactivity of the metal anode, a short and violent charging pulse is used to reduce the surface film. Once the surface film is reduced, the discharge reaction can proceed.

[0203] In this embodiment, non-in-situ measurements of the composition of the metal electrode are used to determine its state of charge and state of health. In an electrochemical cell comprising an iron electrode, the state of charge and state of health of the electrode are related to the proportion of metallic iron. Therefore, the proportion of measuring metallic iron can be used to determine the state of charge or state of health of the battery. In a specific embodiment, magnetic susceptibility measurements are performed on one or more portions of the iron electrode to determine the state of charge or state of health. In order to perform this measurement, the sample can be formed into a disc or cylinder with a thickness in the range of several millimeters and a diameter of 0.25 cm to 4 cm. The measured magnetic susceptibility is analyzed to extract the relative amounts of metallic iron, ferrous iron, and ferric iron.

[0204] In various embodiments, DRI is used as a redox-active electrode material in a primary or secondary type of battery. In one embodiment, DRI is used as an anode active material in a primary battery. In one embodiment, DRI is used as an anode active material in a primary battery that can be refueled (or mechanically recharged), wherein the anode can be mechanically replaced by fresh DRI. In one embodiment, DRI is used as an anode active material in a secondary battery. In another embodiment, DRI is used as an electrode material with an alkaline electrolyte (pH>9). In a specific embodiment, an alkaline secondary battery can use a nickel cathode. In this embodiment, DRI is used as a starting material for the anode of a Ni-Fe alkaline secondary battery, and can be used in its original state or can be processed before use according to other embodiments described herein. Other electrochemical couples (combinations of cathodes and anodes) of alkaline cells using DRI anodes include iron / nickel (Fe / Ni cells) or iron / silver (Fe / Ag cells). In various embodiments, DRI can be used as an anode active material in a primary or secondary battery, wherein the pH of the electrode spans an acidic (pH<5.5) or neutral (5.5<pH<9) range. As an example, DRI can be used as an anode active material in a battery using an electrolyte containing hydrochloric acid (HCl) in a concentration range of 1M-5M. At the anode, DRI can participate in the following half-cell reaction during discharge: Fe + 2Cl - →FeCl2+2e - .

[0205] DRI can be specifically used as an anode material for an all-Fe battery, where Fe is the reactive species at both the anode and cathode. In such an embodiment, DRI can be used as a solid metallic Fe anode at 100% SOC, and the anode will form soluble Fe upon discharge. 2+Substance (i.e., FeCl2). The cathode active material can be a soluble inorganic salt based on Fe, such as the FeCl2 / FeCl3 redox pair. The cathode active material can also be an inorganic coordination compound or an organic coordination compound, such as K3Fe(CN)6. At the cathode, the soluble Fe substance will undergo a redox reaction related to the Fe 2+ / Fe 3+ redox pair. A specific example of an all-Fe battery using DRI as the active material is to use DRI as the anode material and an electrolyte containing HCl with a concentration of 1M - 5M. At the anode, DRI participates in the following half-cell reaction during discharge: Fe + 2Cl - →FeCl2 + 2e - . At the cathode, soluble FeCl3 will undergo the following half-cell reaction during discharge: 2FeCl3 + 2e - →2FeCl2 + 2Cl - . The overall cell reaction during discharge is Fe + 2FeCl3 → 3FeCl2. DRI can be used as a raw material for the required soluble FeCl2 in the solution to participate in the cathode reaction by allowing DRI to react with HCl in the solution, thus participating in the following spontaneous chemical reaction: Fe + 2HCl → FeCl2 + H2.

[0206] In some embodiments, DRI is used as the anode in a flow battery, where DRI pellets are transported from a storage tank to an electrochemical reactor where the DRI pellets undergo an electrochemical reaction. The DRI pellets remain in electrical contact with each other as they flow through the electrochemical reactor, thus enabling sufficient electroosmotic flow to provide high electrical conductivity by collecting the pellets. The electrolyte can be acidic (pH < 5), neutral (5 < pH < 9), or basic (pH > 9). In a specific embodiment, the discharge reaction can proceed such that the metallic Fe anode forms a soluble product (e.g., FeCl2) during discharge, or a slightly soluble (e.g., Fe(OH)2) discharge product film forms on the surface of the transported DRI. Specific embodiments of methods for transporting DRI pellets through the battery include any methods known in the art for transporting pellet materials or slurries or suspensions, including but not limited to pressure-driven fluid flow, using a fluidized bed, by mechanical conveyors (such as conveyor belts, rollers, or using a screw conveyor). In some embodiments, the mechanical conveyor or screw conveyor includes a conductive material, such as metal or carbon, which also serves as the current collector for the battery.

[0207] In various embodiments, DRI is used as a raw material source of metallic Fe in the synthesis of FeCl2 according to the following spontaneous chemical reaction: Fe + 2HCl → FeCl2 + H2. DRI can be used as a raw material in the form of pellets, or the pellets can be crushed into a powder. In addition, DRI fines (pellets or particle size < 0.5 cm) which are waste products of the DRI process can be used as a raw material. Iron iodide (FeI2) and iron bromide (FeBr2) can be synthesized in a similar manner, with HI and HBr being alternative acids to HCl in the salt synthesis.

[0208] In various embodiments, DRI is used to form a packed catalyst bed for a gas phase reaction or a liquid phase reaction. In some embodiments, a packed catalyst bed of DRI can be used as a catalyst in the Haber process for producing ammonia. DRI can replace iron powder, or can be used together with iron powder, which is commonly used in the Haber process. Specifically, the pyrite coating present in commercially produced DRI may be desirable to promote reactions in the Haber process. In some embodiments, the iron or iron salt component of DRI, which can be iron oxide, hydroxide, or carbide, reacts with another component, such as another metal or metal salt, to form a catalytically active surface on DRI. DRI can be used as a raw material for the production of alkaline ferrocyanide. First, DRI can be used to synthesize FeCl2 according to the following spontaneous chemical reaction: Fe+2HCl→FeCl2+H2. Subsequently, Na4Fe(CN)6·10H2O can be synthesized using FeCl2 from DRI according to the following reactions: calcium ferrocyanide synthesis: 6HCN+FeCl2+3Ca(OH)2→Ca2Fe(CN)6·11H2O+CaCl2; conversion to mixed salt: Ca2Fe(CN)6·11H2O+2NaCl→CaNa2Fe(CN)6·11H2O(solid)+CaCl2(solution); and conversion to Na salt: CaNa2Fe(CN)6·11H2O+Na2CO3→Na4Fe(CN)6·10H2O+CaCO3. In this conventional Na4Fe(CN)6·10H2O synthesis method, FeCl2 (about $0.2 / mol) accounts for about 54% of the total raw material cost. Therefore, replacing FeCl2 with DRI (about $0.01 / mol) has the potential to significantly reduce the raw material cost of Na4Fe(CN)6·10H2O by half.

[0209] In various embodiments, DRI is used as an electrode for the hydrogen evolution reaction (HER) for producing hydrogen (H2) by electrolysis. DRI can be used as a catalytic surface to promote HER, or as a conductive substrate for one or more other catalyst materials. In embodiments of the substrate, DRI can be coated in a continuous layer of catalyst material or decorated with catalyst particles. Metallic platinum (Pt) is an example of a catalyst that can be used to coat or decorate a DRI substrate for HER. DRI can be used for HER in acidic or alkaline solutions.

[0210] In various embodiments, the porous DRI pellets are used as OER electrodes. Non-limiting examples of the ways in which DRI can be used for this purpose include: in a pristine state, after electroplating the surface with a transition metal, after electrolessly plating the surface with a transition metal, after modifying the surface by chemical etching, after modifying the surface by thermal treatment, or after thermally applying an OER catalyst to the surface of the DRI substrate.

[0211] In various embodiments, DRI is used as an electrode for oxygen evolution reaction (OER) for producing oxygen (O2) by electrolysis. Non-limiting ways in which DRI can be used include as a catalytic surface to promote OER, or as a conductive substrate for one or more other catalyst materials. In embodiments where DRI is a substrate, DRI can be coated in a continuous layer of a catalyst material or decorated with catalyst particles. Metallic nickel (Ni) is an example of a catalyst that can be used to coat or decorate a DRI substrate for OER. DRI can be used for OER electrodes in acidic or alkaline solutions. DRI can be used as a catalyst or electrode substrate in an alkaline electrolyzer.

[0212] In another embodiment, DRI is used in an oxygen reduction reaction (ORR) electrode. In some embodiments, the iron or iron salt component of DRI (which may be iron oxide, hydroxide or carbide) reacts with another component (such as another metal or metal salt) to form an ORR catalyst. This catalyst can be formed on the surface of the DRI pellet or can penetrate into the DRI pellet, and can be a part of the DRI pellet as a whole or substantially change the DRI pellet as a whole. DRI fine powder and DRI pellets or crushed pellets can be used as ORR electrodes. In some embodiments, the ORR catalyst formed by DRI is a mixed metal oxide comprising iron. In other embodiments, the ORR catalyst is an oxide comprising iron and another transition metal. In multiple embodiments, the ORR catalyst is a spinel structure oxide comprising iron and manganese.

[0213] In various embodiments, a DRI packed bed is used in a water filtration device. In such an embodiment, the DRI can be contained in a column to produce a packed bed of DRI pellets. The pelletized material is captured in the pores inside the DRI pellets and in the spaces between the DRI pellets. Using pelletized iron as a filter medium can provide the ability to adjust pressure drop and filtration efficiency.

[0214] In various embodiments, DRI is used as a metallic iron feedstock for the production of iron-containing industrial or specialty chemicals, such as ferrocyanate, iron tris-bipyridine, and ferrocene.

[0215] Figure 1 is a schematic diagram of a battery (or (battery cell)) 100 according to various embodiments of the present disclosure. Figure 1 The battery 100 includes a container 101 in which an air electrode 103, a negative electrode 102, a liquid electrolyte 104, and a current collector 106 are disposed. The liquid electrolyte 104 can separate the air electrode 103 from the negative electrode 102.

[0216] The negative electrode 102 may include a metal pellet 105, which may contain at least 50% by weight of metal, such as at least 60% by weight of metal, by elemental mass. In some embodiments, the metal pellet 105 may contain at least 60% by weight of iron by elemental mass. Therefore, the pellet 105 may be referred to as an iron-containing pellet. The pellets 105 may be electrically connected to each other and may be arranged in one or more layers to form the negative electrode 102. In various embodiments, the negative electrode 102 may be a slurry. In various embodiments, the slurry may include one or more metal pellets 105 therein. In various embodiments, the slurry may include dissolved particles, such as particles corresponding to the composition of the metal pellets 105 discussed herein. As a specific example, the negative electrode 102 may be a slurry containing iron. In various embodiments, the positive electrode 103 may be a slurry. In various embodiments, the negative electrode 102 may take the form of a gel. A flowable semi-solid negative electrode 102 (e.g., a flowable semi-solid iron electrode, etc.) may be valuable for large-scale energy storage systems due to its low manufacturing cost and ease of assembly into a cell architecture. For example, iron in a reduced form has high conductivity. By suspending iron particles in a polymer gel, a percolation network of iron particles can be generated to form a conductive and electroactive gel that can form the negative electrode 102. For example, a polymer gel can be formed by dissolving an organic polymer (e.g., carboxymethyl cellulose (CMC), or by dissolving an inorganic oxide-forming network (e.g., SiO2 dissolved in concentrated KOH). In some embodiments, the electrolyte is gelled. In some embodiments, silicon dioxide (SiO2) or other oxides that form a network (e.g., boron oxide (B2O3) or aluminum oxide (Al2O3) are dissolved in an alkaline liquid to form a gel. In some embodiments, organic molecules that form a network are dispersed in a liquid electrolyte to form a gel electrolyte. In some embodiments, the organic molecules include polymers. In some embodiments, the liquid electrolyte is added In some embodiments, the gel electrolyte is formed in situ by dissolving silica (or other oxide) from DRI. In some other embodiments, additional gel forming agents are intentionally added to the liquid electrolyte in order to produce a gel. In some embodiments, the gel electrolyte is formed in situ due to the evaporation of the solvent (e.g., water) from the electrolyte, concentrating the dissolved salts and converting the electrolyte from a liquid to a gel or supersaturated solution.

[0217] In various embodiments, pellets 105 include a primary iron-containing phase and one or more secondary phases ("gangue"). In various embodiments, the oxidation state of the primary phase can range from highly reduced (e.g., metallic iron) to highly oxidized (e.g., ionic). For example, pellets 105 can be substantially metallic iron, i.e., having a valence state of zero (e.g., Fe 0 ). Thus, in some embodiments, the pellets may contain at least 60 wt% metallic iron by mass, preferably at least 80 wt% metallic iron, and in some embodiments, 90 wt% to 98 wt% metallic iron. In various other embodiments, the pellets 105 may be composed of iron (e.g., Fe2O3) that is fully oxidized to a valence state of 3. In various other embodiments, the valence state of iron may be 0 to 3+. In various embodiments, the primary phase may be an oxide, hydroxide, sulfide, carbide, or a combination thereof. For example, the primary phase may have Fe, FeO, Fe2O3, Fe3O4, FeO x (OH) y 、Fe3C、FeS x ,FeO x S y and / or FeO x S y H z In some embodiments, pellets 105 may include direct reduced iron (DRI) pellets, and pellets 105 may account for at least 60% of the total mass of negative electrode 102. In various embodiments, negative electrode 102 may consist of DRI pellets.

[0218] In various embodiments, the second phase comprises silicon. For example, the second phase may comprise silicon dioxide (SiO2) and / or one or more silicates, such as feldspar, mica, amphibole, pyroxene, olivine, tourmaline and / or forsterite. In various other embodiments, the second phase may comprise titanium, vanadium, manganese, magnesium, calcium, phosphorus, carbon, aluminum, zirconium or any combination thereof.

[0219] The pellets 105 may be spherical, such as Figure 1 As shown. For example, in various embodiments, pellets 105 can have an average diameter ranging from about 0.5 mm to about 10 cm, such as about 10 mm. As a specific example, pellets 105 can have an average diameter of 4 mm to 20 mm. As used herein, the term "spherical" is used to describe any rounded form that resembles a three-dimensional object (all surface points of which are equidistant from its center), but in which all surface points may not actually be equidistant from the center. In other words, "spherical" includes shapes that are perfect spheres and shapes that may have a general appearance of a sphere but may not be perfect spheres, such as a ball. However, the present disclosure is not limited to any specific pellet shape. For example, the pellets can be in the form of a briquette, as described below with respect to Figure 2A In addition, although shown as intact pellets, the pellets 105 may be fragments of crushed pellets. For example, the pellets as is may be crushed, and those crushed pellet fragments may form pellets 105 in the negative electrode, such as pellets 105 filled into a bed. In various embodiments, the crushed pellets may have a diameter of less than 10 nm (nm = 10 -9 m) to 10 mm (mm = 10 - 3 m), for example, 10 nm-100 nm, 1 nm-100 μm (μm=10 -6 In some embodiments, the crushed pellets may include a combination of pellets having different average particle sizes.

[0220] In a plurality of non-limiting embodiments, the pellets 105 may have an internal porosity ranging from about 2% to 80%, for example, from about 50% to about 75%. In a plurality of non-limiting embodiments, the negative electrode 102 may have a pellet packing density ranging from about 40% to about 74%. Therefore, the liquid electrolyte 104 may penetrate into the space between the pellets 115 to impregnate the negative electrode 102. In order to ensure good conductivity through the pellets 105, low contact resistance may be required. In a plurality of embodiments, compression of the pellets 105 of the negative electrode 102 may ensure contact of the pellets 105. In a plurality of embodiments, the pellets 105 may have a compressive strength of about 700 psi to about 2500 psi. In some embodiments, such a compressive strength pellet 105 may be placed on a bed constituting the negative electrode 102, and a compressive force may be applied to the pellets to improve conductivity.

[0221] Liquid electrolyte 104 may include positively charged elements, such as Li, K, Na, or a combination thereof. In some embodiments, liquid electrolyte 104 may be alkaline, i.e., have a pH greater than 7. In some embodiments, the pH of electrolyte 104 is greater than 10, and in other embodiments, greater than 12. For example, electrolyte 104 may include potassium hydroxide (KOH) at a concentration of 6M (mol / L). In certain embodiments, electrolyte 104 may include a combination of ingredients, such as 5.5M potassium hydroxide (KOH) and 0.5M lithium hydroxide (LiOH). For iron materials, since iron is slightly soluble in high pH liquids, high pH is beneficial for improving mechanical stability. In a plurality of embodiments, pH is greater than 10, or greater than 12, or greater than 14, to ensure this low solubility of iron. On the contrary, at low pH, such as pH less than 5, or pH less than 3, or pH less than 2, iron is soluble and the pellets dissolve.

[0222] In a plurality of non-limiting embodiments, the thickness of the negative electrode 102 may range from about 0.5 cm to about 50 cm, for example, from about 0.75 cm to about 25 cm. The pellets 105 may be arranged in the negative electrode 102 at a packing density ranging from about 30% to about 74%. In a plurality of non-limiting embodiments, the pellets 105 may be placed one upon another (e.g., by dispersion or spreading, such as in a gravel bed), or may be mechanically attached or mechanically connected to one another by methods such as compaction or pressing. In other embodiments, the pellets 105 may be physically connected by methods such as welding or brazing. In other embodiments, the pellets 105 may be combined with one another by arc welding. In other embodiments, the pellets 105 may be connected by a combination of such connection methods. In other embodiments, the pellets 105 may be attached and connected to one another by wires passing through holes in the pellets 105. The holes in the pellets may introduce additional contact points not only in the thickness of the pellet 105 bed as the negative electrode 102, but also in the thickness of a single pellet 105. Once strung together, the wires can be tightened to enhance inter-granule 105 contact, and can then be mechanically held in place by conductive mechanical stoppers, which in turn can be connected to a larger current collector, such as current collector 106. In some embodiments, the granules 105 can be packed into a bed, optionally with the aid of mechanical pressure applied by a high temperature resistant material, and then sintered in a non-oxidizing atmosphere. The result is a bed of granules 105 fused together with low inter-granule 105 contact resistance. The sintered bed of granules 105 can form a negative electrode 102.

[0223] In various embodiments, pellets 105 can be produced from iron ore pellets, such as taconite or magnetite or hematite. In various embodiments, pellets 105 can be produced by reducing iron ore pellets to form a more metallic (more reduced, less oxidized) material, such as metallic iron (Fe 0 ), wüstite (FeO), or a mixture thereof. In various non-limiting embodiments, the pellets 105 can be reduced taconite, direct reduced ("DR") taconite, direct reduced iron ("DRI") pellets, or any combination thereof.

[0224] In a plurality of non-limiting embodiments, the pellet 105 includes a cementite form of iron (Fe3C). Although iron batteries require iron-containing starting materials, the acquisition or transportation of iron (Fe3C) in the form of cementite may be easier or less costly. In a plurality of embodiments, cementite (Fe3C) can be used as a starting electrode material for an iron-containing battery. For example, the pellet 105 may initially be formed by cementite (Fe3C). Cementite (Fe3C) may first be converted to magnetite before or during the early operation of the battery 100, and the magnetite may be reversibly circulated between other iron oxidation states to store energy. In either case, the conversion to magnetite may occur in the battery 100, and may not be performed externally before assembling the battery 100. The cementite (Fe3C) starting pellet 105 may be in the form of ore pellets of most cementite (Fe3C) and / or in the form of pellets formed of most cementite (Fe3C) powder. In various embodiments, a high specific surface area iron oxide phase can be generated by using a low specific surface area cementite material pellet 105 as the anode of the battery 100 and discharging the battery 100 at a current density of about 25 mA / g. The high specific surface area iron oxide phase can be used as the negative electrode 102.

[0225] Commercially available DRI pellets may not necessarily have the best chemical and physical properties to maximize electrochemical performance. In multiple embodiments, the DRI pellets are treated ex situ before being assembled into the negative electrode 102. Multiple embodiments include treating the DRI pellets with mechanical, chemical and / or thermal methods (i.e., ex situ treatment of the DRI pellets) before introducing the DRI pellets into the electrochemical cell to achieve better chemical and physical properties. Better chemical and physical properties may include higher levels of desired impurities (e.g., hydrogen evolution reaction (HER) inhibitors), lower levels of unwanted impurities (e.g., HER catalysts), higher specific surface area, higher total porosity, different pore size distributions (e.g., multi-peak pore size distributions to reduce mass transfer resistance), different pellet size distributions (e.g., multi-peak pore size to enhance bed filling), different aspect ratios (e.g., to enhance bed filling), etc. Mechanical methods that can be applied to DRI pellets ex situ may include crushing, grinding and / or powdering. Thermal methods that can be applied to DRI pellets ex situ can include treating DRI pellets in a reducing (e.g., hydrogen) atmosphere, an oxidizing atmosphere, and / or a carburizing (e.g., carbon monoxide and / or carbon dioxide) atmosphere at elevated temperatures. Chemical methods that can be applied to DRI pellets ex situ can include acid etching, etc. In multiple embodiments, in order to increase the available capacity of the DRI pellets during the discharge reaction, the DRI pellets can be pre-treated by soaking them in an acid bath (e.g., concentrated HCl), etching iron and enlarging the pores in the DRI pellets, which will increase the total porosity of the DRI pellets compared to the DRI pellets that are not etched in the acid bath. After pre-treatment, the etched and now porous DRI pellets can be assembled into the negative electrode 102. The etching time can be optimized to increase the available capacity of the DRI pellets without causing the DRI to lose too much active material in the acid etching solution. In multiple embodiments, the DRI can be used as an electrode in an electrochemical cell and can be charged by an electric current. This method can increase the surface area of ​​the DRI.

[0226] The current collector 106 may be in the form of a conductive plate that is electrically connected to the negative electrode 102. However, the current collector 106 may have other configurations, as described below with respect to Figure 2A discussed.

[0227] The positive electrode half reaction occurring during discharge at the air electrode 103 in an alkaline electrolyte may be O2 + 4e - +2H2O→4OH - The corresponding half-reaction occurring at the negative electrode 102, starting from all-metallic iron (fully charged negative electrode), can be 2Fe→2Fe 2+ +4e -, resulting in a net discharge reaction of 2Fe+O2+2H2O→2Fe(OH)2. In various embodiments, oxygen can be delivered to the air electrode 103. The delivery of oxygen to the air electrode 103 can be carried out in a form other than gaseous oxygen, including gaseous, liquid, or solid oxygen-containing compounds.

[0228] The starting materials may have a variety of configurations, with a range of iron valence states (0 to 3+) and counterions O 2- OH - , S 2- For example, other possible discharge products include Fe2O3, Fe3O4, FeO, FeOOH, FeS, FeS2, etc. and combinations thereof.

[0229] In various embodiments, packing the pellets 105 in a bed to form the negative electrode 102 can produce macropores between individual pellets 105. In addition, in multiple embodiments, the individual pellets 105 can each have a porous (e.g., microporous) surface. Compared with the pellets 105 being smooth spheres, the micropores in the surface of the pellets 105 can provide a larger surface area for each individual pellet 105. The pore size of the pellets can vary. In some embodiments, the pellets 105 may have a volume-weighted average pore size greater than 1 micron, such as 1 micron to 10 microns, etc. The pore size distribution within the pellets can be measured by mercury intrusion. Mercury intrusion is a technique that uses a pressurized chamber to press mercury into the pores of the pellets. Mercury is first pressed into larger pores, and as the chamber pressure increases, mercury is pressed into smaller and smaller pores. Physical relationships (such as the Washburn equation) can be used to relate the applied pressure to the pore size, thereby obtaining a pore size distribution weighted by volume or area. The pore size distribution can be converted to a cumulative distribution, from which the d values ​​described in Tables 1, 2 and 3 above can be derived. 孔,90%体积 and d 孔,50%表面积 The value given.

[0230] Figure 6604 is a schematic diagram of a battery 100, showing an enlarged view of macropores 602 and micropores 604 according to multiple embodiments of the present disclosure. When the pellets 105 are filled into the bed, the macropores 602 are generated by the gaps between the individual pellets 105. The macropores 602 can promote ion transport through very thick (e.g., several centimeters) electrodes 102. The micropores 604 can be deformations on the surface of the pellets 105 themselves. The micropores 604 can allow high surface area active materials to contact the electrolyte 104, achieving high utilization of active materials through solid-solid electrochemical reactions. The micropores may include cracks in the pellets. Such cracks can be formed during the production of the pellets, or can be introduced later, such as by applying a mechanical load that causes cracks. This electrode structure with macropores 602 and micropores 604 is particularly suitable for improving the rate performance of extremely thick electrodes for static long-term energy storage, where thick electrodes may be required to achieve extremely high area capacity.

[0231] Figure 7 A single pellet 105 of the battery 100 is shown. The pellet 105 can include micropores 604 in a solid surface 702 of the pellet 105. The electrolyte 104 can fill the micropores 604, thereby giving the pellet 105 an outer surface area of ​​a sphere, i.e., a liquid electrolyte area of ​​the pellet 105 associated with the micropores 604 and the solid area surface 702. The filling of the micropores 604 with electrolyte reduces the solid area of ​​the surface 702 in contact with the electrolyte on the pellet's outer surface, giving the pellet 105 a low effective specific surface area (e.g., low m 2 / g), which reduces the electrolyte concentration boundary layer on the solid surface 702. Many metal anodes in aqueous batteries (e.g., Zn, Fe, Al) are known to self-discharge due to spontaneous reactions with the electrolyte to form oxidized metal and hydrogen. For long-term energy storage systems (e.g., systems with discharge durations of 8 hours or more, such as 8 hours to 20 hours, 20 hours to 24 hours, 24 hours or more, etc.), self-discharge may limit performance because the cell may self-discharge a large portion of its storage capacity before a complete discharge cycle is completed. In some embodiments, a cell with a low specific surface area (e.g., low m 2 Metal electrodes with low surface area (r / g) are used to suppress self-discharge in low-rate, long-duration energy storage systems. In many typical modern electrochemical cells, high surface area is required to promote high-rate performance (i.e., high power) by introducing many surface sites for reaction. In long-duration systems, the rate performance requirements are significantly reduced, so low surface area electrodes can meet the rate performance requirements while minimizing the self-discharge rate.

[0232] In various embodiments, an electrolyte 104 additive (e.g., Na2MoO4) that forms a thin passivation film is added to the battery 100. In this way, the self-discharge of the anode can be limited to only a small layer on the anode surface. This passivation film will limit the extent of the self-discharge reaction. In order to restore the reactivity of the metal anode, a short and violent charging pulse can reduce the surface film. Once the surface film is reduced, the discharge reaction can proceed.

[0233] In various embodiments, a resistive element is intentionally introduced into the battery 100 to achieve slow charging. By increasing the effective resistance of other cell parts (i.e., not the negative electrode 102 or the negative electrode current collector 106), a greater overall cell polarization can be achieved. Doing so may result in the negative electrode 102 having a greater polarization. If the polarization of the additional negative electrode 102 is large enough, the absolute potential of the electrode 102 may become low enough to activate the reaction Fe(OH)2→Fe at a lower cell level current when the negative electrode 102 is an Fe electrode. The effect can be achieved by increasing the effective resistance of the electrolyte 104, the cathode (e.g., electrode 103), or the cathode current collector.

[0234] Figure 2A is a schematic diagram of a battery 200 according to various embodiments of the present disclosure. Battery 200 is similar to battery 100, and therefore only the differences therebetween are discussed in detail herein.

[0235] Reference Figure 2A , the battery 200 includes a container 101, in which an air electrode 103, a negative electrode 102, a liquid electrolyte 104, and a current collector 106 are disposed. The liquid electrolyte 104 can separate the air electrode 103 from the negative electrode 102. The liquid electrolyte 104 can also impregnate the negative electrode 102.

[0236] In various embodiments, the negative electrode 102 may include a compacted pellet 115. In this article, "compacted pellet" may refer to a rounded rectangular prism. For example, the pellet 115 may have a length ranging from about 10 mm to about 500 mm, a width ranging from about 5 mm to about 250 mm, and a thickness ranging from about 5 mm to about 200 mm. In some embodiments, the pellet 115 may have a length of about 100 mm, a width of about 50 mm, and a thickness of about 30 mm. In various non-limiting embodiments, the pellet 115 may have an internal porosity ranging from about 50% to about 1%.

[0237] In various other embodiments, the pellets 115 may be formed from hot briquette iron ("HBI"), which may be formed by combining and agglomerating pellets, or may be formed by combining and agglomerating powdered metals (eg, powdered iron fines).

[0238] The current collector 106 can be formed of a conductive material electrically connected to the negative electrode 102. The current collector 106 can directly contact the lower surface and the side surface of the negative electrode 102. In some embodiments, the current collector 106 can optionally include a protrusion 109 extending through the negative electrode 102 so as to directly contact the internal area of ​​the negative electrode. The protrusions 109 can also reduce the effective transport length within the electrode 102 from the total thickness of the pellet bed to the spacing between the protrusions 109. In addition, these protrusions 109 can be used to fix a mechanical clamping mechanism to combine a downward force on the pellet bed while serving as a current collecting element. For example, Figure 2B An example of a plate 250 compressing an electrode 102 above a bed of pellets 115 is shown. The plate 250 is fixed to the protrusion 109 by a clamp 252, which attaches the plate 250 to the protrusion 109 and causes the plate 250 to apply a compressive force on the bed of pellets 115 as the negative electrode 102. In this way, the plate 250 and the clamp 252 can be a mechanical clamping mechanism. Similarly, the current collector can use a magnet to compress the material forming the negative electrode 102. For example, the plate 250 can be a magnet attracted to the bottom of the housing 101, the protrusion 109 and / or the current collector 106, which can pull the plate 250 onto the pellets 115 to compress the bed of pellets 115 as the negative electrode. In some embodiments, the current collector 106, the protrusion 109 and / or another element in the battery 200 can be magnetic, and the pellets 115 can be pulled down and / or together to compact the pellet 115 bed. In some embodiments, current collector 106 can be a two-part current collector, a first part attached to the front of negative electrode 102, and a second part attached to the back of negative electrode 102. The front of the electrode can be a surface that is usually set to face the electrolyte, and the back of the electrode can be a surface that is usually set to be away from the electrolyte. In some embodiments, the first part that can be connected to the front can be a porous structure (e.g., a grid), and the second part that is connected to the back can be a solid. Having a current collector on the front and back of the electrode can help to apply a clamping force, and a more uniform reaction rate can be achieved over the entire electrode. The front and rear of the current collector may be short-circuited together, thereby affecting the reaction rate distribution. In some embodiments, current collector 106 can be clamped on the negative electrode 102.

[0239] In metal-air batteries, granular and briquetted electrode materials have multiple advantages, including high surface area, large internal porosity, and high electronic conductivity. Additional advantages include more efficient shipping and handling methods, which are greatly simplified compared to powdered materials. Additional advantages include simplified manufacturing of negative electrodes. In some embodiments, the electrode can be formed by dispersing or pouring the pellets into a container or receptacle. The combination of the high electronic conductivity of the material and the weight of the pellets (possibly a result of the high density of the iron-rich material) can provide low contact resistance between the pellets.

[0240] The electrical conductivity of the materials that can constitute the pellets is generally ranked from high to low: metallic Fe>FeO>Fe3O4>Fe2O3. However, more highly reduced materials have higher conductivity and also require greater input energy in processing, and are therefore more expensive and difficult to prepare. Therefore, materials such as pyrite and mixed phases containing a certain amount of metallic iron (e.g., Fe / FeO, or Fe / Fe3O4, or Fe / Fe2O3) are generally preferred. For example, pyrite (FeO) can provide a desired balance between input energy and processing costs and electrical conductivity. As a specific but non-limiting example, the pellets can be made into reduced taconite pellets, whose composition is close to FeO.

[0241] As a specific example, the pellets can be metallic iron pellets that are primarily spherical, have a porosity of 50% (by volume) and a typical diameter of 10 millimeters (mm). The negative electrode can be 2 centimeters (cm) thick and can be formed from a packed bed of pellets. For hard packed spheres, it is known that the packing density of randomly densely packed spheres can be about 64%, while densely packed spheres can reach a packing density of 74%. Therefore, the total solid phase density of the negative electrode can be about 32% (50%×64%) to 39% (50%×74%). The negative electrode is infiltrated with a liquid electrolyte consisting of potassium hydroxide (KOH) at a concentration of 6M (mol / L).

[0242] Other advantages of the proposed negative electrode structure include the presence of low-curvature electrolyte channels in the interstices between the particles, allowing rapid liquid-phase ion transport, and the use of thick, high-areal capacity (>0.1 Ah / cm 2 ) metal negative electrode. The disclosed concept also allows independent tuning of the electrode surface area (ie, solid-liquid interface area) and electrode porosity, since the pellet porosity and packing density can be independently varied.

[0243] As another advantage of the present invention, the pellets can be assembled by spreading and filling in a dry state. In other embodiments, the pellets can be first dispersed in a liquid electrolyte and then poured and spread into a battery container. In various embodiments, the container supporting the pellets can take a variety of forms. Although in Figure 1 2 is shown as a pellet bed, but the negative electrode 102 can have a variety of different shapes, such as conical, tubular, etc.

[0244] FIG. 12A to FIG. 12F 1 is a cross-sectional view of exemplary cells 1200A-1200F having alternative electrode configurations including an ordered array of pellets 105. Cells 1200A-1200F may be similar to cell 100, and thus only the differences therebetween will be discussed in detail.

[0245] Reference Fig. 12A , the cell 1200A may include one or more conical containers 1202 that support pellets 105. The conical containers 1202 may allow the pellets 105 to self-align. The conical containers 1202 may enable a modular design of the negative electrode 102 by having a large "swimming pool" type reactor, where multiple conical containers 1202 are located at the bottom of a pool of electrolyte 104. The conical containers 1202 may be a cost-effective design for bed current collection.

[0246] Reference Fig. 12B , the battery 1200B may include a container 101 that supports an array of negative electrode pellets 105 forming a negative electrode 102. One or more positive electrodes 103 may be inserted into the negative electrode 102. The pellets 105 may be electrically connected to each other and / or to a current collector 106. A separator 107 may surround the positive electrode 103 and electrically insulate the positive electrode 103 from the negative electrode 102.

[0247] like Fig. 12C As shown, the battery 1200C may include a positive electrode 103 extending completely through an array of negative electrode pellets. In the battery 1200C, pellets 105 may be arranged in a stack alternating with electrodes 103. Fig.12D , Cell 1200D, Cell 1200D is similar to Cell 1200C, except that the spacer is omitted. In Cell 1200D, pellets 105 may be arranged in a support bed suspended in electrolyte 104 along with electrodes 103 .

[0248] Fig.12E Another example battery 1200E is shown according to various embodiments of the present disclosure. In battery 1200E, pellets 105 may be arranged in a hexagonal array around electrode 103, which may be circular. Fig.12F Another example battery 1200F is shown according to various embodiments of the present disclosure. In battery 1200F, pellets 105 may be arranged in a hexagonal array around electrode 103, which may be hexagonal.

[0249] As mentioned above, the pellets of the present disclosure are not limited to any particular pellet shape. In various embodiments, the pellets may be iron agglomerates having a variety of different shapes, such as Figure 3A305. The sintered iron agglomerated particles 305 shown in . The sintered iron agglomerated particles can have symmetrical and / or asymmetrical shapes. As an example, the sintered iron agglomerated particles can have symmetrical shapes, such as spherical, elliptical, cylindrical or plate-shaped, or irregular shapes (such as granular). In multiple embodiments, the sintered iron agglomerates 305 can be formed in a furnace, such as a continuous feed calciner, a batch calciner, a vertical furnace or any other type of furnace. As a specific example, when the furnace is a continuous feed calciner, the furnace 307 can be configured with a rotating tube. In operation, iron powder particles 302 can be fed into the furnace 307. The furnace 307 can rotate and heat the iron powder agglomerates 302 to sinter the iron powder agglomerates 302 together, thereby manufacturing sintered iron agglomerated particles, such as sintered iron agglomerated particles 305. Sintered iron agglomerated particles, such as sintered iron agglomerated particles 305, can provide the same chemical properties and morphology as the sintered agglomerates described herein (e.g., agglomerates 105, agglomerates 115, etc.), and can replace agglomerates of other shapes in various embodiments. Sintered iron agglomerated particles, such as sintered iron agglomerated particles 305, can include a neck 309 at the sintered joint of iron powder agglomerates 302 that are bonded together to form a sintered iron agglomerated particle, such as sintered iron agglomerated particles 305.

[0250] An advantage of using iron agglomerate-forming pellets is that such iron agglomerate pellets (eg, sintered iron agglomerated particles 305) may be cheaper to manufacture than spherical and / or briquette-shaped pellets (eg, pellets 105, 115, etc.).

[0251] In various embodiments, sintered iron electrodes (e.g., entire electrodes and / or individual pellets (e.g., pellets 105, 115, 305, etc.) can be formed from crushed precursor and / or byproduct materials (e.g., DRI) (e.g., fines) from a steelmaking process. For example, DRI precursor and DRI fines can be crushed, formed with a binder under heat and pressure, and then sintered to form porous iron electrodes in the shape of pellets 105, 115, 305, etc. and / or electrodes in other shapes, including but not limited to sheets, plates, strips, cylinders, and other shapes.

[0252] Refer to the following Figure 3B-Figure 3D Various embodiments discussed provide sintered porous metal electrodes for use in preparing batteries, such as batteries 100, 200, 400, 800, 814, 900, 1000, 1100, and 1200 described herein.

[0253] Figure 3B One method 350 embodiment for preparing a sintered porous metal electrode is shown. The method 350 may include mixing a metal and one or more additives to form a green shaped pellet in block 351, and sintering the green shaped pellet to form a porous metal electrode in block 352.

[0254] In block 351, mixing the metal and one or more additives to form a "green" shaped pellet may include hot pressing the mixture of the metal and one or more additives to form a green shaped pellet. In various embodiments, the metal may include iron. In various embodiments, the additive may include a combination of pore former and binder additives. As a specific example, a mixture of iron, polyethylene, and bismuth sulfide powder may be hot pressed into a green shaped pellet. In various embodiments, polyethylene may serve as both a green forming binder and a pore former that evaporates during the sintering step. Polyethylene may sublime at a temperature below the sintering temperature. In various embodiments, other pore former additives that do not necessarily serve as binders may be used, such as any inorganic or organic material that is solid at room temperature and liquid or gaseous in nitrogen between room temperature and the sintering temperature in a nitrogen (e.g., N2) atmosphere or an argon / hydrogen (e.g., Ar (95%) / H2 (5%) or other corresponding argon and hydrogen concentration) atmosphere. In various embodiments, multiple types of binders may be mixed together as additives for the metal. Mixtures of multiple types of binders can be used to target specific microstructural morphologies and stabilize the powder bed during binder burnout.

[0255] Sintering the green-formed pellets to form a porous metal electrode in frame 352 may include sintering the green-formed pellets in a gas atmosphere with a time-temperature curve. The gas atmosphere may be a nitrogen (e.g., N2) atmosphere or an argon / hydrogen (e.g., Ar (95%) / H2 (5%) or other corresponding argon and hydrogen concentrations) atmosphere. In multiple embodiments, the time-temperature curve may be a linear time-temperature curve or a nonlinear time-temperature curve. For example, the linear time-temperature curve may include a linear temperature rise period, followed by a constant temperature holding period, followed by a linear decline period. As a specific example, sintering the green-formed pellets in a gas atmosphere with a time-temperature curve may include sintering the green-formed pellets in a nitrogen (e.g., N2) atmosphere or an argon / hydrogen (e.g., Ar (95%) / H2 (5%) or other corresponding argon and hydrogen concentrations) atmosphere, wherein the linear temperature rises to 850°C, is maintained at 850°C for 15 minutes, and then linearly decreases to room temperature. As another example, the nonlinear time-temperature curve can have multiple temperature rise zones and temperature holding zones to better control the evaporation rate of the pore former (e.g., polyethylene pore former). For example, the nonlinear time-temperature curve can have a nonlinear temperature rise period, two or more temperature holding periods with a fall period and a rise period therebetween, and a nonlinear fall period.

[0256] Figure 3CAn embodiment of a system 360 for forming a sintered porous metal electrode 362 is shown. The system 360 may include a continuous roller furnace having a series of heating elements 364 and a belt 366, the roller being configured to convey the items on the belt 366 from one end of the furnace to the other end when heated by the heating elements 364. The area below the heating elements 364 may be configured to have controlled atmospheric conditions, such as an atmosphere of pure hydrogen (H2) supplied by a hydrogen tank 369. The system 360 may include a powder supply source 370 (e.g., a hopper, a container, a roller, etc.) to provide a metal powder 371 (e.g., an iron oxide powder, etc.) for forming a sintered porous metal electrode 362. When the metal powder 371 is an iron oxide powder, the iron oxide powder may or may not be oxidized in air at high temperatures, which will result in a fully oxidized (Fe2O3) powder feedstock. The metal powder 371 may be deposited onto the belt 366 from the powder supply source and compressed (i.e., below the heating element 364) before being fed into the furnace. As an example, the metal powder 371 can be compressed by a slot die, rollers 372, a press or other compacting device at the front of the furnace. The compressed metal powder can be fed by belt 366 along the length of the furnace under the heating element 364. As the metal powder 371 is heated by the heating element 364 in the hydrogen atmosphere while being moved by belt 366, H2O vapor can be released from the metal powder 371. The hydrogen reduces the iron oxide at high temperature to form water and metallic iron (i.e., FeO x +H2→H2O+Fe). The resulting metal powder (e.g., iron powder) is rolled on a belt 366 and continuously passed through the furnace, so that the particles are sintered together to form a sintered porous metal electrode 362 (e.g., a sintered porous Fe electrode) in a continuous manner. In some embodiments, the sintered porous metal electrode 362 can be cut into pieces after leaving the furnace, such as by a knife 378, a clamp cutter, a cutting jet, or any other type of device configured to cut the sintered porous metal electrode 362 into pieces. In some embodiments, the weight of the sintered porous metal electrode 362 can break it up.

[0257] Figure 3DA system 380 for forming a sintered porous metal electrode 362 is shown. System 380 can be similar to system 360 described above, except that a metal sheet 382 can be placed under the metal powder 371 before the metal powder 371 is fed into the furnace. In this way, the metal powder 371 can be sintered directly onto the metal sheet 382, ​​thereby continuously forming a sintered porous metal electrode 362 with an integrated current collector. The metal sheet 382 can be a metal roll that is fed into the furnace under the metal powder 371 and supports the metal powder 371 on the belt 366. For example, before the metal powder 371 is deposited and compressed, the metal sheet 382 can be fed to the belt 366 by a reel of a reel system. In multiple embodiments, the metal sheet 382 can be a metal foil. In multiple embodiments, the metal sheet 382 can be formed of any metal selected for use as a current collector, such as nickel, iron, steel, etc.

[0258] Figure 4 4 is a schematic diagram of a battery according to various embodiments of the present disclosure. Battery 400 is similar to battery 100, and therefore only the differences between battery 100 and battery 400 will be discussed in detail. Battery 400 may include spherical pellets 105 distributed in a smaller pellet composition (e.g., a composition formed of powdered metal raw materials, metal fines, metal abrasive particles, etc.).

[0259] Long-duration electrochemical energy storage can benefit from very low-cost material inputs. Although the pellets 105 of the battery 100 can provide very low-cost materials, the electrical and ionic conductivity through the pellets 105 may not be ideal due to the limited contact points inherent to the pellets 105. One solution to provide better electrical and ionic conductivity can be to use powdered metal raw materials as electrodes, such as the negative electrode 102. Although powdered metal raw materials used as electrodes can provide customized electrical and ionic conductivity, the production cost of the powdered metal raw materials can be high, especially compared to the pellets 105.

[0260] Various embodiments can provide a composite metal electrode framework that provides lower cost than pure powdered metal raw material electrodes and / or higher conductivity than pure spherical pellet electrodes. As used herein, the average width or diameter of the pellets is at least 10 times the average width or diameter of the powdered pellets in the powdered metal raw material. In various embodiments, the composite metal electrode framework can include a mixture of spherical pellets and smaller metal pellet compositions (e.g., powdered metal raw materials). For example, Figure 4As shown, the negative electrode 102 may include spherical pellets 105 distributed in a smaller metal pellet composition 402 (e.g., powdered metal raw material). The spherical pellets 105 and the powdered metal raw material may provide a mixture of larger and smaller pellets similar to marbles in sand or other combinations of corresponding particle sizes as the negative electrode 102. In some embodiments, the macropores between the larger pellets contain smaller pellets. The composite metal electrode formed by the spherical pellets 105 and the powdered metal raw material may provide an electrode framework with highly adjustable cost, conductivity, and / or ionic conductivity. In some embodiments, the composite metal electrode may be wetted with a liquid electrolyte 104. Since the powdered metal raw material contained in the composite metal electrode may be wetted, the composite metal electrode formed by the spherical pellets 105 and the powdered metal raw material may have a lower iron to electrolyte ratio than an electrode formed only by the spherical pellets 105. The powdered metal raw material 402 may improve the conductivity between the pellets 105 in the electrode 102, and may also improve the overall packing density of the electrode.

[0261] In various embodiments, the composite metal electrode framework may include a mixture of spherical aggregates and smaller metal aggregate compositions (e.g., metal fines or metal shavings). Figure 4 As shown, the negative electrode 102 may include a pelletized pellet 105 composed of taconite and a smaller metal pellet composition 402 composed of conductive DRI fines. By combining low-cost taconite pellets and scrap used as bulk iron raw materials for the pellets 105 with the conductive DRI fines used as the smaller metal pellet composition 402, the cost of forming the conductive electrode when assembling the battery 400 can be reduced. As another example, the composite metal electrode framework may include a mixture of iron ore pellets of different sizes, such as larger iron ore pellets (e.g., taconite, DRI, sponge iron, atomized iron, etc.) and smaller metal pellet compositions, such as metal fines or metal turnings (e.g., fines or turnings of DRI, taconite, sponge iron, atomized iron, etc.).

[0262] In some embodiments, the conductivity of the metal electrode is increased by adding conductive fibers, filaments, meshes or sheets to the pellets so that the conductive material is dispersed between the pellets.

[0263] Multiple embodiments provide in-situ synthesis of active materials for large-capacity energy storage systems using excess renewable electricity. In multiple embodiments, energy storage power stations including battery cell embodiments (e.g., metal-air electrochemical battery cell embodiments discussed herein) can be configured as dual-purpose to reduce chemical costs. The initial use of the energy storage power station can be to synthesize key active materials, such as metal granules, such as granules 105, 115, 305, etc., in situ using chemicals with lower cost input and very cheap or free renewable electricity. The next use of the energy storage power station can be an actual energy storage power station, in which the synthesized chemicals are active materials, such as metal granules, such as granules 105, 115, 305, etc. For example, metal powders that will eventually be used for ultra-large batteries can be synthesized in situ at a dual-purpose energy storage power station before the battery is commissioned, by using direct reduction of hydrogen, which is electrochemically generated in situ by alkaline electrolysis or PEM electrolysis powered by renewable resources (e.g., wind energy, solar energy, etc.). The in-situ production of active materials in the first stage can not only reduce production costs, but also potentially avoid transportation costs. In embodiments where iron ore is the source of active material, renewable electricity can be used to provide heat to reduce the ore in the dual-purpose energy storage power station. In addition, renewable electricity can optionally be used to generate hydrogen as a reducing gas to reduce the ore. The ore or reduced ore can optionally be in the form of iron-containing pellets.

[0264] In various embodiments, metal pellets (eg, pellets 105, 115, 305, etc.) can be synthesized in a first stage of a dual-purpose energy storage power plant and used in the negative electrode in a second stage of the dual-purpose energy storage power plant. Figure 5 A method 500 embodiment for providing in-situ synthesis of active materials (e.g., metal granules, such as granules 105, 115, 305, etc.) for a large-capacity energy storage system using excess renewable electricity is shown. In box 501, during a first stage of operation, a dual-purpose energy storage power station can be operated to produce active materials, such as metal granules, such as granules 105, 115, 305, etc. For example, when iron ore is the source of the active material, the ore can be reduced in situ in the dual-purpose energy storage power station to synthesize metal granules, such as granules 105, 115, 305, etc. During a second stage of operation in box 502, the dual-purpose energy storage power station can use the active material for long-term energy storage. For example, the synthesized metal granules (e.g., granules 105, 115, 305, etc.) can be loaded (or otherwise deposited, added, formed, etc.) into a negative electrode (e.g., electrode 102 of a battery, etc.) to support long-term energy storage of the dual-purpose energy storage power station. In various embodiments, the operations of blocks 501 and / or 502 may be performed using renewable electrical energy.

[0265] Fig. 8A800 is a schematic diagram of a battery 800 according to multiple embodiments of the present disclosure. Battery 800 is similar to battery 100, so only the differences between them will be discussed in detail. Battery 800 can be configured to flow electrolyte 104 over negative electrode 102. For example, battery 800 can include a circulation pump 802 and a pipeline that is configured to pump electrolyte 104 to pellets 105 including electrode 102 at a selected rate (e.g., constant flow rate, variable flow rate, etc.). It may be challenging to transport electrolyte 104 through very thick (several centimeters) battery electrodes 102 (composed of active material pellets 105). The low transport rate of electrolyte 104 may increase the overpotential loss in the electrode 102 based on pellets 105. By flowing electrolyte 104 through thick electrode 102, convective transport can be introduced, which promotes the flow of electrolyte to individual pellets 105. As described above, the pellets 105 can be microporous, and the reaction conditions can benefit by reducing the concentration boundary layer of the electrolyte 104, which can occur in the thickness of the entire pellet 105 bed through the electrode 102 and through the macropores (e.g., macropores 602) in the pellet 105 bed. By homogenizing the electrolyte 104 composition in the macrostructure and microstructure of the entire electrode 102, the electrolyte 104 flow will generally reduce the overpotential loss. The flow rate of the electrolyte 104 can preferably be selected to be low enough so that any energy consumed by pumping will not consume undesirable energy. In multiple embodiments, the flow rate of the electrolyte 104 can be a steady flow rate or a variable flow rate.

[0266] In various embodiments, by flowing the electrolyte 104 through the battery electrode 102 (e.g., a battery electrode 102 composed of active material pellets 105) at a low but constant flow rate, convective transport can be introduced that promotes the flow of electrolyte 104 to individual pellets 105. The pellets 105 can be microporous and the reaction conditions can benefit by reducing the electrolyte 104 concentration boundary layer that can occur through the thickness of the entire pellet 105 (e.g., through the electrode 102) and through the macropores in the pellet 105 bed (e.g., in the electrode 102). Electrolyte 104 flow can generally reduce overpotential losses by homogenizing the electrolyte 104 composition throughout the macrostructure and microstructure of the electrode 102.

[0267] In various embodiments, the electrolyte 104 formulation may be different for the charge, discharge, and idle states of the battery 800. When switching between states, flowing different electrolyte 104 formulations into the battery 800 can simultaneously improve utilization, self-discharge, and HER. For example, in the case of an electrolyte management system with continuous flow, there may be optionally any number of different electrolyte formulation reservoirs, each of which is connected to the electrochemical cell by a separate flow controller (e.g., a combination of three reservoirs and flow controllers 805, 806, 807). During different operations, different relative amounts of each electrolyte formulation may flow based on the optimal concentration of the constituent substances for the instantaneous operating mode (e.g., charge, discharge, idle). In some embodiments, the electrolyte formulation may be adjusted based on the instantaneous charge state of the battery 800. In various embodiments, a combination of a reservoir and a flow controller (e.g., 805, 806, 807) may be used to add additional electrolyte 104 to the battery 800, for example, to compensate for the evaporation of the electrolyte 104. In various embodiments, the battery 800 can include an overflow 820 or overflow channel that can allow the electrolyte 104 to overflow from the battery 800. For example, the level of the electrolyte 104 can be maintained because when the level of the electrolyte 104 reaches the overflow 820, it can leave the battery 800 to maintain the level of the electrolyte 104 at the level of the overflow 820.

[0268] Figure 8B 814 is a block diagram of an embodiment of a cell 814 including an additive delivery system 815. Cell 814 is similar to cell 100, so only the differences therebetween will be discussed in detail. In one embodiment, additive delivery system 815 can be a pump that delivers a liquid containing additives to cell 814. In another embodiment, additive delivery system 815 can be a dry hopper that delivers solids containing additives to cell 814. As an example, additive delivery system 815 can be a sulfur delivery system. As a specific example, when additive delivery system 815 is a sulfur delivery system, the sulfur delivery system can be a pump that delivers a sulfur-containing liquid to cell 814. In another specific example, when additive delivery system 815 is a sulfur delivery system, the sulfur delivery system can be a dry hopper that delivers sulfur-containing solids (e.g., polysulfide salts, iron sulfide (FeS), etc.) to cell 814. In another example, additive delivery system 815 can be a salt delivery system. Specifically, the additive delivery system 815 can add certain solid phase hydrogen evolution inhibitors (e.g., Bi, Sb, As) as soluble salts. For example, the soluble salts of the desired hydrogen evolution inhibitors can be added to the liquid electrolyte 104 by the additive delivery system 815 to dissolve to provide the desired additive ions (i.e., Bi, Sb, As) in the solution. 3+ , Sb 3+ 、As 3+The additive may be selected so that the redox potential of the inhibitor's ion-metal plating reaction (e.g., Bi 3+ →Bi 0 ) can be at a higher half-cell potential (measured relative to RHE) than the charge reaction potential of the anode active material (but at a lower cell potential). Therefore, during the charging process of the battery 800, the HER inhibitor in ionic form is electrodeposited onto the surface of the metal electrode, providing an inexpensive and simple strategy for introducing HER inhibitors into the battery 800 electrolyte 104 chemistry. The electrodeposited inhibitor suppresses the hydrogen evolution reaction on the electrode surface, which can be an electrode with open pores. In the discharge mode, the deposit may dissolve back into the electrolyte 104. The salt additive can be preferably selected so that it does not degrade the operation of the cathode during charge or discharge operation. As another example For example, the added salt can be a carbonate. In some embodiments, the additive delivery system 815 can deliver multiple additives to the battery 800. For example, a combined additive composition, such as a corrosion inhibitor that inhibits the HER reaction or inhibits self-discharge combined with an additive that improves capacity utilization, can be delivered by the additive delivery system 815. As another example, an inhibitor that forms a passivation layer on a metal surface is paired with an additive that depassivates the iron surface, and both can be delivered by the additive delivery system 815. In some embodiments, the additive delivery system 815 can deliver an additive comprising molybdate ions. As an example, a molybdate compound (such as In one specific example, the electrolyte 104 may include an additive having a concentration of 10 mM molybdate anions. In other embodiments, the electrolyte 104 may include an additive having a concentration range of 1 mM to 100 mM molybdate anions. In some embodiments, a surfactant additive may be delivered by an additive delivery system 815. The surfactant additive may reduce the surface tension and viscosity of the electrolyte at the oxygen evolution electrode, thereby generating smaller, uniformly sized and controllable bubbles during charging. In a non-limiting example, 1-octanethiol at a concentration of 10 mM is added to the alkaline electrolyte 104. In some embodiments, In some embodiments, the corrosion inhibitor additive can be delivered by the additive delivery system 815. In some embodiments, the additive delivery system 815 can deliver liquid inhibitors and / or interphase interface inhibitors. In some embodiments, the additive delivery system 815 can deliver additives as solid mixtures. In some embodiments, the additive delivery system 815 can deliver electrolyte additives (e.g., Na2MoO4) that form a thin, passivating film. Therefore, the self-discharge of the anode is limited to a small layer on the surface of the anode. However, in order to restore the reactivity of the metal anode, a short and violent charging pulse can be used to reduce the surface film. Once the surface film is reduced, the discharge reaction can proceed.

[0269] Figure 8C 800 。It is a block diagram of a battery system 850 according to multiple embodiments, which includes a series of fluid-connected (or otherwise liquid-connected) battery 800 embodiments. The battery 800 can be arranged in a cascade manner so that the overflow electrolyte 104 from one battery 800 can flow into the next battery 800 via its overflow port 820, thereby establishing "liquid communication" between the batteries 800. Connecting these batteries 800 in series allows a source to supply liquid electrolyte 104 to multiple batteries 800 at the same time. For example, a single electrolyte supply tube 851 connected to a pump 802 can supply electrolyte 104 to the first battery 800. The electrolyte overflowing from the first battery 800 can flow to the second battery 800 and the third battery 800. The electrolyte can overflow from the third battery 800 into the return tube 852 and circulate back to the supply tube 851 by the pump 802. In this way, the overflow from the final battery 800 can be recycled to the first battery 800. In the system 850 utilizing a shared electrolyte 104, the electrolyte flows in a cascade between the batteries 800, and the properties of the electrolyte 104 can be monitored and processed at a central location (e.g., a monitoring station 853) of many batteries. In order to alleviate problems related to electrolyte carbonation, electrolyte dehydration, etc., the electrolyte 104 can be advantageously adjusted at the monitoring station 853, such as adjusting the composition or adding components. The monitoring station 853 can be juxtaposed with a collection structure (e.g., a reflux pipe 852) for circulating the electrolyte 104. As an example, the monitoring station 853 can control the supply of electrolyte 104 from different reservoirs and flow controller combinations (e.g., 805, 806, 807), a filter 860, and / or a backup electrolyte supply tank 855. In multiple embodiments, the monitoring station 853 can be configured to monitor electrolyte health. The health of the electrolyte can be monitored during battery operation to determine the appropriate time to replenish, replace, or process the electrolyte 104. The feedback mechanism used by the monitoring station 853 can be manual or automatic. When the monitoring station 853 is an automated system, the electrolyte quality measurement can be used as an input to a control loop (e.g., a proportional integral derivative (PID) loop) that continuously adjusts the concentration of the electrolyte components. The electrolyte quality measurement can be done ex situ on a small portion of the electrolyte 104, or can be done on the active electrolyte 104 while the cell 800 is operating. One non-limiting method of assessing the health of the electrolyte is to measure the conductivity of the electrolyte. One mechanism of degradation is due to carbon dioxide dissolving from the air into the electrolyte, causing the electrolyte to carbonize over time. For example, conductivity probes are used to assess the concentration of carbonates in the electrolyte. Conductivity probes are used to monitor the health of the electrolyte. Although shown as part of a cascade system 850, the monitoring station 853 can equally be part of an electrolyte delivery system for a single cell, such as Fig. 8AThe monitoring station 853 can control the release of electrolyte 104 from and / or to the backup electrolyte supply tank 852 to increase and / or decrease the volume of electrolyte 104 in the system 850. The monitoring station 853 can control the flow of liquid through the filter device 860. The filter device 860 can be configured to filter the liquid (e.g., water, electrolyte 104, etc.) flowing through it, and the monitoring station 853 can control the flow of liquid into and out of the filter device 860. For example, the filter device 860 can be a water filter, such as Fig.14 Water filter 1400 is shown. Water filter 1400 can be a packed bed 1401 of DRI, which can be used as a water filtration device. In such an embodiment, the DRI can be contained in a column to produce a packed bed 1401 of DRI pellets 197. As water flows through the bed 1401, the pellet material will be captured in the pores inside the DRI pellets 197 and in the spaces between the DRI pellets 197. Using granular iron as a filtering mechanism can achieve the ability to adjust the pressure drop and filtering effect.

[0270] Fig. 9 is a schematic diagram of a battery 900 according to various embodiments of the present disclosure. Battery 900 is similar to battery 100, and therefore only the differences therebetween will be discussed in detail. Alkaline iron electrode cells operate best when certain additives are present in the electrolyte and / or the cell. Electrolyte additives may have a range of solubilities, and some electrolyte additives may have the most beneficial effect when intimately mixed with the solid electrode. Fig. 9 As shown, in various embodiments, the pellets 902 including the additive can be mixed with the pellets 105 dominated by the active material, so that the negative electrode 102 can be a mixed electrode. The additive pellets 902 can be formed partially and / or entirely of additives, such as iron sulfur compounds, such as FeS, FeS2, etc. In various embodiments, the liquid electrolyte 104 can include additives to inhibit the hydrogen evolution reaction at the anode or cathode. These inhibitors can be soluble or insoluble, and can include semi-metallic HER inhibitors, such as bismuth, antimony, tin, boron, indium, gallium, selenium. The additive can be plated out of the solution or undergo a phase change during operation, for example, starting from a dissolved solution and then precipitating in solid form.

[0271] Fig.10 1 is a schematic diagram of a battery 1000 according to various embodiments of the present disclosure. Battery 1000 is similar to battery 100, and therefore only the differences therebetween will be discussed in detail. Due to the spherical structure of pellets 105 contacting current collector 106 in battery 100, the interfacial resistivity between current collector 106 and negative electrode 102 composed of pellets 105 may be high. As a result, electrode 102 experiences an increase in effective current density at the pellet contact. In various embodiments, as Fig.10As shown in the battery 1000 of FIG. 1 , adding an iron powder (Fe) layer 1002 to the interface of the electrode 102 and the current collector 106 can reduce the interfacial resistivity. In the battery 1000, the iron powder layer 1002 can be added to the bottom of the pellet 105 bed to reduce the interfacial resistivity. The iron powder layer 1002 can be configured to form an interface between the pellet 105 and the current collector 106 of the battery 1000. The average width or diameter of the pellet 105 is at least 10 times the average width or diameter of the powder pellets in the layer 1002.

[0272] Fig.11 1 is a schematic diagram of a battery 1100 according to various embodiments of the present disclosure. Battery 1100 is similar to battery 100, and therefore only the differences therebetween will be discussed in detail. Battery 1100 may include a monitoring system including one or more sensors connected (e.g., wirelessly or via wires) to a controller 1110 that is configured to monitor the state of charge (SOC) and / or state of health (SOH) of iron electrode 102. Monitoring SOC and / or SOH may be valuable for improving control and health monitoring of battery 1100.

[0273] Various embodiments may include one or more of a plurality of methods of monitoring the chemical and / or physical properties of the negative electrode 102, including using a Mössbauer spectrometer, using a charge coupled device (CCD) detector (e.g., a color camera, etc.), using a strain gauge, using a temperature sensor, measuring ion concentration, measuring electrolyte level displacement, measuring pellet bed height, measuring pellet size, measuring battery 1100 cell mass, measuring magnetic susceptibility, and using gas induction. In various embodiments, NiOH / NiOOH electrodes containing carbon conductive additives and / or binders can be used as quasi-reference electrodes to monitor the potential. These NiOH / NiOOH electrodes can be placed at multiple locations throughout the electrolyte container to monitor the potential distribution of the entire system.

[0274] For example, the SOC and / or SOH may be monitored in situ via one or more strain gauges 1102 connected to the container 101. The one or more strain gauges 1102 may be connected to a controller 1110 and may output to the controller 1110 a measurement of the strain on the container 101. The controller 1110 may be configured to convert the strain measurement into an SOC and / or SOH measurement.

[0275] As another example, the SOC and / or SOH may be monitored in situ by a Mössbauer spectrometer including a gamma source 1103 and a gamma detector 1104. The gamma source 1103 may output gamma rays through the battery 1100, which may be detected by the gamma detector 1104. The gamma source 1103 may be connected to a controller 1110, and the controller 1110 may control the gamma source 1103 to output gamma rays. The gamma detector 1104 may be connected to the controller 1110, and may output a measurement value of the gamma rays to the controller 1110. The controller 1110 may be configured to convert the measurement value of the gamma rays into a SOC and / or SOH measurement value.

[0276] As another example, the SOC and / or SOH can be monitored in situ by one or more CCD detectors 1105 (e.g., a color camera, etc.) connected to the controller 1110. The CCD detector 1105 can capture an image of the negative electrode 102 and output it to the controller 1110. The controller 1110 can be configured to use the image to determine the SOC and / or SOH measurements. For example, the controller 1110 can be configured to associate the color of the pellets 105 in the image with the SOC and / or SOH measurements. As another example, the controller 1110 can be configured to measure the size of the pellets 105 from the image data and / or can be configured to measure the height of the pellet 105 bed from the image data.

[0277] As another example, the SOC and / or SOH can be monitored in situ by one or more ultrasonic transducers 1106 connected to the controller 1110. The ultrasonic transducer 1106 can output the acoustic wave measurements to the controller 1110. The controller 1110 can be configured to use the acoustic wave measurements to determine the SOC and / or SOH measurements. For example, based on the round trip time of the acoustic waves to the surface of the pellet 105 bed, the height change of the pellet 105 bed can be determined by the controller 1110 and correlated with the SOC and / or SOH measurements.

[0278] As another example, SOC and / or SOH can be monitored in situ by one or more ion sensing electrodes 1107 connected to the controller 1110. The ion sensing electrodes 1107 can output ion measurements (e.g., ion concentrations) to the controller 1110. The controller 1110 can be configured to use the ion measurements to determine SOC and / or SOH measurements.

[0279] As another example, the SOC may be monitored in situ via one or more thermocouples 1108 connected to the controller 1110. Thermocouples 1108 may output temperature measurements to the controller 1110. The controller 1110 may be configured to use the temperature measurements to determine SOC and / or SOH measurements.

[0280] As another example, SOC and / or SOH may be monitored in situ by one or more gas sensors 1109 connected to the controller 1110. The gas sensors 1109 may output gas measurements, such as specific particle detections, concentrations, etc., to the controller 1110. The controller 1110 may be configured to use the gas measurements to determine SOC and / or SOH measurements.

[0281] In various embodiments, the physical and / or chemical properties of the battery 1100, and more specifically the physical and / or chemical properties of the negative electrode 102, measured by the plurality of sensors 1102-1109, may be used by the controller 1100 to determine control actions to be taken with respect to the battery 1100, such as ensuring healthy operation of the battery 1100 based on monitoring the SOC and / or SOH of the negative electrode 102.

[0282] Fig.13A A battery 1300 according to various embodiments is shown. As an example, the battery 1300 is a static battery using DRI. In some embodiments, the battery 1300 is an aqueous battery without flow. In some embodiments, the battery 1300 may be a primary battery. In some embodiments, the battery 1300 may be a secondary battery. In some embodiments, the battery 1300 may include a DRI pellet 198 in one electrode 1302 and / or may include a DRI pellet 199 in another electrode 1306. Although illustrated as including DRI pellets 198, 199, in some configurations, only one of the electrodes 1302 or 1306 may include DRI pellets 198, 199, respectively, and in other configurations, the two electrodes 1302, 1306 may include DRI pellets 198, 199, respectively. In various embodiments, the electrodes 1302 and 1306 may be separated by an electrolyte 1304. In various embodiments, the battery 1300 may be a sealed battery. In various embodiments, the cell 1300 can be an open cell, such as an open cell to the air. In various embodiments, the DRI pellets 198 can be similar to the various DRI pellets (or other DRI type configurations) described herein, such as DRI pellets 105, 115, 305, etc.

[0283] In various embodiments, electrode 1302 is the anode of battery 1300, and electrode 1306 is the cathode of battery 1300. In various embodiments, when battery 1300 is of primary or secondary type, DRI is used as a redox active electrode material. In one embodiment, when battery 1300 is a secondary battery, DRI (e.g., DRI pellets 198) is used as an anode active material. In another embodiment, DRI (e.g., DRI pellets 198, 199) is used as an electrode material with an alkaline electrolyte (pH>9). In a specific embodiment, when battery 1300 is an alkaline secondary battery, battery 1300 can use a nickel cathode. In this embodiment, DRI is used as the starting material for the anode of Ni-Fe alkaline secondary battery 1300, and can be used in its original state or can be processed before use according to other embodiments described herein. When the battery 1300 is an alkaline battery using a DRI anode, other electrochemical couples (combinations of cathode and anode) can be used including iron / nickel (Fe / Ni battery) or iron / silver (Fe / Ag battery). In various embodiments, when the battery 1300 is a primary or secondary battery, DRI can be used as an anode active material, where the pH of the electrode spans an acidic (pH < 5.5) or neutral (5.5 < pH < 9) range. As an example, DRI can be used as an anode active material in a battery 1300 using an electrolyte containing hydrochloric acid (HCl) in a concentration range of 1M-5M. At the anode, DRI can participate in the following half-cell reaction during discharge: Fe + 2Cl - →FeCl2+2e - .

[0284] DRI can be used specifically as an anode material when the cell 1300 is an all-Fe cell, where Fe is a reactive species at both the anode and the cathode. In such an embodiment, the DRI can be used as a solid metallic Fe anode at 100% SOC, and the anode will form soluble Fe upon discharge. 2+ The cathode active material can be a soluble inorganic salt based on Fe, such as a FeCl2 / FeCl3 redox pair. The cathode active material can also be an inorganic coordination compound or an organic coordination compound, such as K3Fe(CN)6. At the cathode, the soluble Fe species will undergo a reaction with Fe 2+ / Fe 3+ Redox reactions associated with redox pairs. As a specific example, when cell 1300 is an all-Fe cell using DRI as an active material, cell 1300 can use DRI as an anode material and use an electrolyte containing HCl (at a concentration of 1M-5M). At the anode, DRI participates in the following half-cell reaction during discharge: Fe+2Cl - →FeCl2+2e -。At the cathode, the soluble FeCl3 will undergo the following half-cell reaction during discharge: 2FeCl3 + 2e - → 2FeCl2 + 2Cl - 。The full-cell reaction during discharge is Fe + 2FeCl3 → 3FeCl2. DRI can be used as a raw material for the soluble FeCl2 required in the solution to participate in the cathode reaction by allowing DRI to react with HCl in the solution, thus participating in the following spontaneous chemical reaction: Fe + 2HCl → FeCl2 + H2.

[0285] Fig. 13B FIG. shows a battery 1310 according to multiple embodiments. The battery 1310 is similar to the battery 1300 described above, except that the battery 1310 is a flow battery using DRI. In multiple embodiments, the DRI pellets 198, 199 are transported through the respective electrodes 1302, 1306 of the flow battery 1310 via one or more corresponding transport systems 1314, 1316 from the respective storage tanks 1311, 1312. As an example, DRI can be used as the anode in the flow battery 1310, where the DRI pellets are transported from the storage tank to the electrochemical reactor, and the DRI pellets undergo an electrochemical reaction in the reactor. The DRI pellets maintain electrical contact with each other as they flow through the electrochemical reactor, thus enabling sufficient electroosmotic flow to provide high electrical conductivity by collecting the pellets. The electrolyte 1304 can be acidic (pH < 5), neutral (5 < pH < 9), or basic (pH > 9). In a specific embodiment, the discharge reaction can be carried out such that the metal Fe anode forms a soluble product (e.g., FeCl2) during discharge, or a slightly soluble (e.g., Fe(OH)2) discharge product film forms on the surface of the transported DRI pellets. Specific embodiments of the method for transporting the DRI pellets through the battery 1310 via one or two of the transport systems 1314, 1316 include any method known in the art for transporting pellet materials or slurries or suspensions. For example, one or both of the transport systems 1314, 1316 can be, but are not limited to, a pressure-driven fluid flow system, a fluidized bed system, or a mechanical conveyor system (such as a conveyor belt, roller, or screw conveyor). In some embodiments, the transport systems 1314, 1316, such as mechanical belt-type, screw-type, drum-type, etc., include a conductive material that can also be used as the current collector of the battery 1310, such as metal or carbon.

[0286] A method for preparing a sintered porous metal electrode is provided in various embodiments, the method comprising mixing a metal and one or more additives to form a green body molded pellet, and sintering the green body molded pellet to form a sintered porous metal electrode. In various embodiments, the method comprises mixing a metal and one or more additives to form a green body molded pellet, and hot pressing a mixture of the metal and one or more additives to form a green body molded pellet. In various embodiments, the metal comprises iron. In various embodiments, at least one of the one or more additives is both a pore former and a binder additive. In various embodiments, the one or more additives include polyethylene additives and bismuth sulfide powder additives. In various embodiments, at least one of the one or more additives is a pore former additive, and at least another of the one or more additives is a binder additive. In various embodiments, the binder additive is a mixture of two or more different types of binders. In various embodiments, sintering the green body molded pellets to form a sintered porous metal electrode comprises sintering the green body molded pellets in a gas atmosphere with a time-temperature curve. In various embodiments, the gas atmosphere is an N2 atmosphere or an Ar / H2 atmosphere. In various embodiments, the gas atmosphere is an Ar (95%) / H2 (5%) atmosphere. In various embodiments, the time-temperature curve includes a linear temperature rise period, followed by a constant temperature holding period, followed by a linear decline period. In various embodiments, the linear temperature rise period increases the temperature of the green body molded pellets to 850°C, the temperature is 850°C, and the linear decline period reduces the temperature of the green body molded pellets to room temperature. In various embodiments, the constant temperature holding period is 15 minutes. In various embodiments, the time-temperature curve includes a nonlinear temperature rise period, two or more temperature holding periods with a decline period and a rise period therebetween, and a nonlinear decline period.

[0287] Multiple embodiments may provide a method for manufacturing a sintered porous metal electrode, comprising feeding a compressed metal powder into a continuous roller furnace and passing the compressed metal powder through the furnace to sinter the metal powder together to form a sintered porous metal electrode. In multiple embodiments, the metal powder comprises iron oxide powder. In multiple embodiments, the method may include compressing the metal powder before feeding the metal powder into the furnace. In multiple embodiments, compressing the metal powder comprises passing the metal powder through a slit die or under a compression roller. In multiple embodiments, the method may include placing a metal sheet under the powder before feeding the metal powder into the furnace. In multiple embodiments, the metal sheet originates from a metal coil fed into the furnace and supports the compressed metal powder in the furnace. In multiple embodiments, the metal sheet is a metal foil. In multiple embodiments, the metal sheet comprises nickel, iron or steel. In multiple embodiments, the method may include cutting the sintered porous metal electrode into multiple parts. In multiple embodiments, the continuous roller furnace heats the metal powder in a hydrogen atmosphere. In multiple other embodiments, the continuous roller furnace heats the metal powder in an inert atmosphere of nitrogen or argon. In various other embodiments, the continuous roller furnace heats the metal powder in an atmosphere comprising a mixture of hydrogen, nitrogen, and / or argon.

[0288] Multiple embodiments may provide apparatus and / or methods for large-capacity energy storage systems, such as long-duration energy storage (LODES) systems, short-duration energy storage (SDES) systems, and the like. As an example, multiple embodiments may provide batteries and / or components for large-capacity energy storage systems (e.g., batteries 100, 200, 400, 800, 814, 900, 1000, 1100, 1200, 1300, 1310; pellets 105, 115, 305, 198, 199; any one of systems 850, etc.), such as batteries for LODES systems. Renewable electricity is becoming more common and more cost-effective. However, many renewable electricity sources face intermittency issues, which hinder the use of renewable electricity. By matching renewable electricity with large-capacity energy storage systems (such as LODES systems, SDES systems, etc.), the impact of the intermittent trend of renewable electricity can be mitigated. In order to support the use of combined power generation, transmission and storage systems (e.g., a power plant with a renewable power generation source matched with a bulk energy storage system and transmission facilities in any power plant and / or bulk energy storage system), devices and methods are needed to support the design and operation of such combined power generation, transmission and storage systems, such as the multiple device and method embodiments described herein.

[0289] The combined power generation, transmission and storage system can be a power plant including one or more power generation sources (e.g., one or more renewable power generation sources, one or more non-renewable power generation sources, a combination of renewable and non-renewable power generation sources, etc.), one or more transmission facilities, and one or more large-capacity energy storage systems. The transmission facilities of any power plant and / or large-capacity energy storage system can be optimized together with the power generation and storage system, or constraints can be imposed on the design and operation of the power generation and storage system. Under multiple design and operation constraints, the combined power generation, transmission and storage system can be configured to meet multiple output targets.

[0290] Example

[0291] The following examples are provided to illustrate various embodiments of the systems, methods, compositions, applications and materials of the present invention. These examples are for illustrative purposes, may be prophetic, and should not be considered limiting, and do not otherwise limit the scope of the present invention.

[0292] Figure 15-Figure 23 Multiple system examples are shown in which one or more aspects of the multiple embodiments are used as part of a bulk energy storage system, such as a LODES system, an SDES system, etc. For example, the multiple battery and / or component embodiments described herein (e.g., any of batteries 100, 200, 400, 800, 814, 900, 1000, 1100, 1200, 1300, 1310; pellets 105, 115, 305, 198, 199; system 850, etc.) can be used as batteries and / or components of a bulk energy storage system (e.g., a LODES system, an SDES system, etc.). The term "LODES system" as used herein, unless expressly specified otherwise, refers to a large-capacity energy storage system configured to have a rated duration (energy / power ratio) of 24 hours or longer, such as a duration of 24 hours, a duration of 24 hours to 50 hours, a duration greater than 50 hours, a duration of 24 hours to 150 hours, a duration greater than 150 hours, a duration of 24 hours to 200 hours, a duration greater than 200 hours, a duration of 24 hours to 500 hours, a duration greater than 500 hours, etc.

[0293] Example 1

[0294] A storage system having one, five, ten, 50, 100, 500 or more electrochemical cells having one or more electrodes comprising direct reduced iron pellets. Preferably, the storage system is a long-term storage system having long-term electrochemical cells.

[0295] Example 1A

[0296] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1A below:

[0297] Table E1A

[0298] Granule shape sphere Total Fe content of pellets (wt%) 92 <![CDATA[Agglomerate contains SiO2 (wt%)]]> 1.5 <![CDATA[Agglomerate contains Al2O3 (wt%)]]> 0.2 MgO content in pellets (wt%) 0.1 CaO content in pellets (wt%) 0.9 <![CDATA[TiO2 content in the aggregates (wt%)]]> 0.05 <![CDATA[Agglomerate contains Fe2C (wt%)]]> 80 Metallization (%) 94 Electrode volume density (g / cc) 1.7 Apparent density of pellets (g / cc) 3.5 Actual density of pellets (g / cc) 6 <![CDATA[Minimum d of the aggregates 孔,90%体积 (μm)]]> 0.966 <![CDATA[Minimum d of the aggregates 孔,50%表面积 (μm)]]> 0.0114 <![CDATA[Specific surface area of the aggregates (m 2 / g)]]> 0.31

[0299] Example 1B

[0300] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1B below:

[0301] Table E1B

[0302]

[0303]

[0304] Example 1C

[0305] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1C below:

[0306] Table E1C

[0307] Granule shape ball Total Fe content of pellets (wt%) 91 <![CDATA[Agglomerate contains SiO2 (wt%)]]> 1 <![CDATA[The aggregate contains Al2O3 (wt%)]]> 0.5 Granules containing MgO (weight %) 0.1 CaO content in pellets (wt%) 0.9 <![CDATA[TiO2 content in aggregates (wt%)]]> 0.05 <![CDATA[The pellets contain Fe2C (wt%)]]> 0 Metallization (%) 94 Electrode volume density (g / cc) 1.7 Apparent density of pellets (g / cc) 3.3 Actual density of pellets (g / cc) 5.9 <![CDATA[Minimum d of the aggregates 孔,90%体积 (μm)]]> 4.4 <![CDATA[Minimum d of the aggregates 孔,50%表面积 (micrometers)]]> 11.1 <![CDATA[Specific surface area of aggregates (m 2 / g)]]> 0.74

[0308] Example 1D

[0309] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1D below:

[0310] Table E1D

[0311] Granule shape piece Total Fe content of pellets (wt%) 89 <![CDATA[Agglomerate contains SiO2 (wt%)]]> 2 <![CDATA[Agglomerate contains Al2O3 (wt%)]]> 0.5 Granules containing MgO (weight %) 0.1 CaO content in pellets (wt%) 0.9 <![CDATA[The TiO2 content (wt%) in the aggregates]]> 0.05 <![CDATA[Agglomerate contains Fe2C (wt%)]]> 15 Metallization (%) 94 Electrode volume density (g / cc) 2.1 Apparent density of pellets (g / cc) 3.6 Actual density of pellets (g / cc) 6.2 <![CDATA[Minimum d of the aggregates 孔,90%体积 (μm)]]> 4.2 <![CDATA[Minimum d of the aggregates 孔,50%表面积 (μm)]]> 10.8 <![CDATA[Specific surface area of aggregates (m 2 / g)]]> 0.72

[0312] Example 1E

[0313] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1E below:

[0314] Table E1E

[0315]

[0316]

[0317] Example 1F

[0318] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1F below:

[0319] Table E1F

[0320] Granule shape column Total Fe content of pellets (wt%) 85 <![CDATA[Agglomerate contains SiO2 (wt%)]]> 10 <![CDATA[Agglomerate contains Al2O3 (wt%)]]> 1.5 Granules containing MgO (weight %) 0.1 CaO content in pellets (wt%) 1.5 <![CDATA[Agglomerate contains TiO2 (wt%)]]> 0.05 <![CDATA[Agglomerate contains Fe2C (wt%)]]> 3 Metallization (%) 92 Electrode volume density (g / cc) 2 Apparent density of pellets (g / cc) 3.4 Actual density of pellets (g / cc) 5.8 <![CDATA[Minimum d of the aggregates 孔,90%体积 (μm)]]> 2.55 <![CDATA[Minimum d of the aggregates 孔,50%表面积 (μm)]]> 1.74 <![CDATA[Specific surface area of aggregates (m 2 / g)]]> 0.34

[0321] Example 1G

[0322] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1G below:

[0323] Table E1G

[0324]

[0325]

[0326] Example 1H

[0327] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1H below:

[0328] Table E1H

[0329] Granule shape ball Total Fe content of pellets (wt%) 84 <![CDATA[Agglomerate contains SiO2 (wt%)]]> 2 <![CDATA[Agglomerate contains Al2O3 (wt%)]]> 0.2 Granules containing MgO (weight %) 10 CaO content in pellets (wt%) 0.9 <![CDATA[TiO2 content in aggregate (wt%)]]> 0.05 <![CDATA[Agglomerate contains Fe2C (wt%)]]> 10 Metallization (%) 92 Electrode volume density (g / cc) 2 Apparent density of pellets (g / cc) 3.4 Actual density of pellets (g / cc) 5.8 <![CDATA[Minimum d of the aggregates 孔,90%体积 (μm)]]> 1.27 <![CDATA[Minimum d of the aggregates 孔,50%表面积 (μm)]]> 0.42 <![CDATA[Specific surface area of aggregates (m 2 / g)]]> 0.41

[0330] Example 1I

[0331] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1I below:

[0332] Table E1I

[0333] Granule shape piece Total Fe content of pellets (wt%) 84 <![CDATA[Agglomerate contains SiO2 (wt%)]]> 1.5 <![CDATA[Agglomerate contains Al2O3 (wt%)]]> 2 MgO content in pellets (wt%) 0.1 CaO content in pellets (wt%) 10 <![CDATA[TiO2 content in aggregates (wt%)]]> 0.05 <![CDATA[Agglomerate contains Fe2C (wt%)]]> 2 Metallization (%) 92 Electrode volume density (g / cc) 2 Apparent density of pellets (g / cc) 3.4 Actual density of pellets (g / cc) 5.8 <![CDATA[Minimum d of the aggregates 孔,90%体积 (μm)]]> 0.95 <![CDATA[Minimum d of the aggregates 孔,50%表面积 (micrometers)]]> 0.78 <![CDATA[Specific surface area of the aggregates (m 2 / g)]]> 0.63

[0334] Example 1J

[0335] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1J below:

[0336] Table E1J

[0337]

[0338]

[0339] Example 1K

[0340] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1K below:

[0341] Table E1K

[0342] Granule shape Great Total Fe content of pellets (wt%) 84 <![CDATA[Agglomerate contains SiO2 (wt%)]]> 5 <![CDATA[Agglomerate contains Al2O3 (wt%)]]> 5 MgO content in pellets (wt%) 2 CaO content in pellets (wt%) 1 <![CDATA[TiO2 content in aggregates (wt%)]]> 1.5 <![CDATA[The pellets contain Fe2C (wt%)]]> 0 Metallization (%) 94 Electrode volume density (g / cc) 1.8 Apparent density of pellets (g / cc) 3.5 Actual density of pellets (g / cc) 6 <![CDATA[Minimum d of the aggregates 孔,90%体积 (μm)]]> 2.72 <![CDATA[Minimum d of the aggregates 孔,50%表面积 (μm)]]> 2.79 <![CDATA[Specific surface area of aggregates (m 2 / g)]]> 0.22

[0343] Example 1L

[0344] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1L below:

[0345] Table E1L

[0346]

[0347]

[0348] Example 1M

[0349] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1M below:

[0350] Table E1M

[0351]

[0352]

[0353] Example 1N

[0354] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1N below:

[0355] Table E1N

[0356] Granule shape Briquetting Total Fe content of pellets (wt%) 86 <![CDATA[Agglomerate contains SiO2 (wt%)]]> 9 <![CDATA[Agglomerate contains Al2O3 (wt%)]]> 0.2 MgO content in pellets (wt%) 0.5 CaO content in pellets (wt%) 0.9 <![CDATA[TiO2 content in aggregates (wt%)]]> 0.05 <![CDATA[The pellets contain Fe2C (wt%)]]> 40 Metallization (%) 90 Electrode volume density (g / cc) 2.5 Apparent density of pellets (g / cc) 5 Actual density of pellets (g / cc) 6.3 <![CDATA[Minimum d of the aggregates 孔,90%体积 (micrometers)]]> 1.84 <![CDATA[Minimum d of the aggregates 孔,50%表面积 (μm)]]> 0.0171 <![CDATA[Specific surface area of aggregates (m 2 / g)]]> 0.015

[0357] Example 10

[0358] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E10 below:

[0359] Table E10

[0360]

[0361]

[0362] Example 1P

[0363] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1P below:

[0364] Table E1P

[0365] Granule shape strip Total Fe content of pellets (wt%) 84 <![CDATA[Agglomerate contains SiO2 (wt%)]]> 6 <![CDATA[Agglomerate contains Al2O3 (wt%)]]> 3 Granules containing MgO (weight %) 0.5 CaO content in pellets (wt%) 0.9 <![CDATA[TiO2 content in the aggregates (wt%)]]> 0.05 <![CDATA[The pellets contain Fe2C (wt%)]]> 10 Metallization (%) 90 Electrode volume density (g / cc) 1.8 Apparent density of pellets (g / cc) 3.9 Actual density of pellets (g / cc) 6.1 <![CDATA[Minimum d of the aggregates 孔,90%体积 (μm)]]> 1.98 <![CDATA[Minimum d of the aggregates 孔,50%表面积 (μm)]]> 0.0123 <![CDATA[Specific surface area of the aggregate (m 2 / g)]]> 0.027

[0366] Example 1Q

[0367] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1Q below:

[0368] Table E1Q

[0369] Granule shape powder Total Fe content of pellets (wt%) 88 <![CDATA[Agglomerate contains SiO2 (wt%)]]> 7 <![CDATA[The aggregate contains Al2O3 (wt%)]]> 2 MgO content in pellets (wt%) 0.5 CaO content in pellets (wt%) 0.9 <![CDATA[TiO2 content in aggregates (wt%)]]> 0.05 <![CDATA[Agglomerate contains Fe2C (wt%)]]> 10 Metallization (%) 95 Electrode volume density (g / cc) 3.5 Apparent density of pellets (g / cc) 6.3 Actual density of pellets (g / cc) 6.6 <![CDATA[Minimum d of the aggregates 孔,90%体积 (μm)]]> 0.015 <![CDATA[Minimum d of the aggregates 孔,50%表面积 (μm)]]> 0.012 <![CDATA[Specific surface area of aggregates (m 2 / g)]]> 1.21

[0370] Example 1R

[0371] The long-term storage system of Example 1, wherein the electrode has the properties shown in Table E1R below:

[0372] Table E1R

[0373]

[0374]

[0375] Example 2

[0376] Fig.15 A system example is shown in which one or more aspects of multiple embodiments can be used as part of a large-capacity energy storage system. As a specific example, a large-capacity energy storage system integrating one or more aspects of multiple embodiments can be a LODES system 1504. As an example, the LODES system 1504 can include any of the multiple battery and / or component embodiments described herein (e.g., any of batteries 100, 200, 400, 800, 814, 900, 1000, 1100, 1200, 1300, 1310; pellets 105, 115, 305, 198, 199; system 850, etc.), either alone or in combination. The LODES system 1504 can be electrically connected to a wind farm 1502 and one or more transmission facilities 1506. The wind farm 1502 can be electrically connected to a transmission facility 1506. The transmission facility 1506 can be electrically connected to a power grid 1508. The wind farm 1502 can generate electricity, and the wind farm 1502 can output the generated electricity to the LODES system 1504 and / or the transmission facility 1506. The LODES system 1504 can store the electricity received from the wind farm 1502 and / or the transmission facility 1506. The LODES system 1504 can output the stored electricity to the transmission facility 1506. The transmission facility 1506 can output the electricity received from one or both of the wind farm 1502 and the LODES system 1504 to the power grid 1508, and / or can receive electricity from the power grid 1508 and output the electricity to the LODES system 1504. The wind farm 1502, the LODES system 1504, and the transmission facility 1506 together can constitute the power plant 1500, which can be a combined power generation, transmission, and storage system. The electricity generated by the wind farm 1502 can be directly fed to the power grid 1508 through the transmission facility 1506, or can be first stored in the LODES system 1504. In some cases, the power supplied to the grid 1508 may come entirely from wind farm 1502, entirely from LODES system 1504, or from a combination of wind farm 1502 and LODES system 1504. The dispatch of power from the power plant 1500, from the combined wind farm 1502 and LODES system 1504, may be controlled according to a determined long-term (multi-day or even multi-year) plan, or may be controlled according to the market one day in advance (24 hours advance notice), or may be controlled according to the market one hour in advance, or may be controlled in response to real-time pricing signals.

[0377] As an example of operating power plant 1500, LODES system 1504 can be used to reshape and "consolidate" the electricity generated by wind power plant 1502. In one such example, wind power plant 1502 can have a peak power generation output (capacity) of 260 megawatts (MW) and a capacity factor (CF) of 41%. LODES system 1504 can have a rated power (capacity) of 106MW, a rated duration (energy / power ratio) of 150 hours (h), and an energy rating of 15,900 megawatt hours (MWh). In another such example, wind power plant 1502 can have a peak power generation output (capacity) of 300MW and a capacity factor (CF) of 41%. LODES system 1504 can have a rated power of 106MW, a rated duration (energy / power ratio) of 200 hours, and an energy rating of 21,200MWh. In another such example, wind power plant 1502 can have a peak power generation output (capacity) of 176MW and a capacity factor (CF) of 53%. The LODES system 1504 may have a rated power (capacity) of 88 MW, a rated duration (energy / power ratio) of 150 hours, and an energy rating of 13,200 MWh. In another such instance, the wind farm 1502 may have a peak power generation output (capacity) of 277 MW and a capacity factor (CF) of 41%. The LODES system 1504 may have a rated power (capacity) of 97 MW, a rated duration (energy / power ratio) of 50 hours, and an energy rating of 4,850 MWh. In another such instance, the wind farm 1502 may have a peak power generation output (capacity) of 315 MW and a capacity factor (CF) of 41%. The LODES system 1504 may have a rated power (capacity) of 110 MW, a rated duration (energy / power ratio) of 25 hours, and an energy rating of 2,750 MWh.

[0378] Example 2A

[0379] The system of Example 2, wherein the LODES system utilizes one or more storage systems of Examples 1, 1A, 1B, 1C, 1D, 1E, 1F, 1G, 1H, 1I, 1J, 1K, 1L, 1M, 1N, 1O, 1P, 1Q, and 1R.

[0380] Example 3

[0381] Fig.16An example of a system is shown in which one or more aspects of multiple embodiments can be used as part of a bulk energy storage system. As a specific example, a bulk energy storage system integrating one or more aspects of multiple embodiments can be a LODES system 1504. As an example, the LODES system 1504 can include any of the multiple battery and / or component embodiments described herein (e.g., any of batteries 100, 200, 400, 800, 814, 900, 1000, 1100, 1200, 1300, 1310; pellets 105, 115, 305, 198, 199; system 850, etc.), either alone or in a plurality of combinations. Fig.16 The system can be similar to Fig.15 1506. The LODES system 1504 may be electrically connected to the PV plant 1602 and one or more transmission facilities 1506. The PV plant 1602 may be electrically connected to the transmission facility 1506. The transmission facility 1506 may be electrically connected to the grid 1508. The PV plant 1602 may generate electricity, and the PV plant 1602 may output the generated electricity to the LODES system 1504 and / or the transmission facility 1506. The LODES system 1504 may store the electricity received from the PV plant 1602 and / or the transmission facility 1506. The LODES system 1504 may output the stored electricity to the transmission facility 1506. The transmission facility 1506 may output the electricity received from one or both of the PV plant 1602 and the LODES system 1504 to the grid 1508, and / or may receive electricity from the grid 1508 and output the electricity to the LODES system 1504. PV power plant 1602, LODES system 1504, and transmission facility 1506 together may constitute power plant 1600, which may be a combined power generation, transmission, and storage system. The power generated by PV power plant 1602 may be fed directly to grid 1508 via transmission facility 1506, or may be first stored in LODES system 1504. In some cases, the power supplied to grid 1508 may come entirely from PV power plant 1602, entirely from LODES system 1504, or from a combination of PV power plant 1602 and LODES system 1504. The dispatch of power from power plant 1600, from the combined PV power plant 1602 and LODES system 1504, may be controlled according to a determined long-term (multi-day or even multi-year) plan, or may be controlled according to a market one day in advance (24 hours advance notice), or may be controlled according to a market one hour in advance, or may be controlled in response to real-time pricing signals.

[0382] As an example of operating power plant 1600, LODES system 1504 can be used to reshape and "consolidate" the electricity generated by PV power plant 1602. In one such example, PV power plant 1602 can have a peak power generation output (capacity) of 490MW and a capacity factor (CF) of 24%. LODES system 1504 can have a rated power (capacity) of 340MW, a rated duration (energy / power ratio) of 150 hours, and an energy rating of 51,000MWh. In another such example, PV power plant 1602 can have a peak power generation output (capacity) of 680MW and a capacity factor (CF) of 24%. LODES system 1504 can have a rated power (capacity) of 410MW, a rated duration (energy / power ratio) of 200 hours, and an energy rating of 82,000MWh. In another such example, PV power plant 1602 can have a peak power generation output (capacity) of 330MW and a capacity factor (CF) of 31%. The LODES system 1504 may have a rated power (capacity) of 215 MW, a rated duration (energy / power ratio) of 150 hours, and an energy rating of 32,250 MWh. In another such instance, the PV power plant 1602 may have a peak power generation output (capacity) of 510 MW and a capacity factor (CF) of 24%. The LODES system 1504 may have a rated power (capacity) of 380 MW, a rated duration (energy / power ratio) of 50 hours, and an energy rating of 19,000 MWh. In another such instance, the PV power plant 1602 may have a peak power generation output (capacity) of 630 MW and a capacity factor (CF) of 24%. The LODES system 1504 may have a rated power (capacity) of 380 MW, a rated duration (energy / power ratio) of 25 hours, and an energy rating of 9,500 MWh.

[0383] Example 3A

[0384] The system of Example 3, wherein the LODES system utilizes one or more storage systems of Examples 1, 1A, 1B, 1C, 1D, 1E, 1F, 1G, 1H, 1I, 1J, 1K, 1L, 1M, 1N, 1O, 1P, 1Q, and 1R.

[0385] Example 4

[0386] Fig.17An example of a system is shown in which one or more aspects of multiple embodiments can be used as part of a bulk energy storage system. As a specific example, a bulk energy storage system incorporating one or more aspects of multiple embodiments can be a LODES system 1504. As an example, the LODES system 1504 can include any of the multiple battery and / or component embodiments described herein (e.g., any of batteries 100, 200, 400, 800, 814, 900, 1000, 1100, 1200, 1300, 1310; pellets 105, 115, 305, 198, 199; system 850, etc.), either alone or in a plurality of combinations. Fig.17 The system can be similar to Fig.15 and Fig.16 1504, except that wind power plant 1502 and photovoltaic (PV) power plant 1602 may both be generators working together in power plant 1700. PV power plant 1602, wind power plant 1502, LODES system 1504, and transmission facility 1506 together may constitute power plant 1700, which may be a combined power generation, transmission, and storage system. The electricity generated by PV power plant 1602 and / or wind power plant 1502 may be fed directly to grid 1508 via transmission facility 1506, or may be first stored in LODES system 1504. In some cases, the electricity supplied to grid 1508 may come entirely from PV power plant 1602, entirely from wind power plant 1502, entirely from LODES system 1504, or from a combination of PV power plant 1602, wind power plant 1502, and LODES system 1504. The dispatch of power from the combined wind plant 1502, PV plant 1602 and LODES system 1504 power plant 1700 can be controlled based on a determined long-term (multi-day or even multi-year) plan, or can be controlled based on the market one day in advance (24 hours advance notice), or can be controlled based on the market one hour in advance, or can be controlled in response to real-time pricing signals.

[0387] As an example of operating power plant 1700, LODES system 1504 can be used to reshape and "consolidate" the electricity generated by wind power plant 1502 and PV power plant 1602. In one such example, wind power plant 1502 can have a peak power generation output (capacity) of 126MW and a capacity factor (CF) of 41%, and PV power plant 1602 can have a peak power generation output (capacity) of 126MW and a capacity factor (CF) of 24%. LODES system 1504 can have a rated power (capacity) of 63MW, a rated duration (energy / power ratio) of 150 hours, and an energy rating of 9,450MWh. In another such example, wind power plant 1502 can have a peak power generation output (capacity) of 170MW and a capacity factor (CF) of 41%, and PV power plant 1602 can have a peak power generation output (capacity) of 110MW and a capacity factor (CF) of 24%. The LODES system 1504 may have a rated power (capacity) of 57 MW, a rated duration (energy / power ratio) of 200 hours, and an energy rating of 11,400 MWh. In another such instance, the wind plant 1502 may have a peak power generation output (capacity) of 105 MW and a capacity factor (CF) of 51%, and the PV plant 1602 may have a peak power generation output (capacity) of 70 MW and a capacity factor (CF) of 31%. The LODES system 1504 may have a rated power (capacity) of 61 MW, a rated duration (energy / power ratio) of 150 hours, and an energy rating of 9,150 MWh. In another such instance, the wind plant 1502 may have a peak power generation output (capacity) of 135 MW and a capacity factor (CF) of 41%, and the PV plant 1602 may have a peak power generation output (capacity) of 90 MW and a capacity factor (CF) of 24%. LODES system 1504 may have a rated power (capacity) of 68 MW, a rated duration (energy / power ratio) of 50 hours, and an energy rating of 3,400 MWh. In another such example, wind power plant 1502 may have a peak power generation output (capacity) of 144 MW and a capacity factor (CF) of 41%, and PV power plant 1602 may have a peak power generation output (capacity) of 96 MW and a capacity factor (CF) of 24%. LODES system 1504 may have a rated power (capacity) of 72 MW, a rated duration (energy / power ratio) of 25 hours, and an energy rating of 1,800 MWh.

[0388] Example 4A

[0389] The system of example 4, wherein the LODES system utilizes one or more storage systems of examples 1, 1A, 1B, 1C, 1D, 1E, 1F, 1G, 1H, 1I, 1J, 1K, 1L, 1M, 1N, 1O, 1P, 1Q, and 1R.

[0390] Example 5

[0391] Fig.18 A system example is shown in which one or more aspects of multiple embodiments can be used as part of a bulk energy storage system. As a specific example, a bulk energy storage system that integrates one or more aspects of multiple embodiments can be a LODES system 1504. As an example, the LODES system 1504 can include any of the multiple battery and / or component embodiments described herein (e.g., any of batteries 100, 200, 400, 800, 814, 900, 1000, 1100, 1200, 1300, 1310; pellets 105, 115, 305, 198, 199; system 850, etc.), either alone or in combination. The LODES system 1504 can be electrically connected to one or more transmission facilities 1506. In this way, the LODES system 1504 can operate in a "stand-alone" manner to balance energy around market prices and / or avoid transmission constraints. The LODES system 1504 can be electrically connected to one or more transmission facilities 1506. Transmission facility 1506 may be electrically connected to grid 1508. LODES system 1504 may store power received from transmission facility 1506. LODES system 1504 may output stored power to transmission facility 1506. Transmission facility 1506 may output power received from LODES system 1504 to grid 1508, and / or may receive power from grid 1508 and output the power to LODES system 1504.

[0392] LODES system 1504 and transmission equipment 1506 together can constitute power plant 1800. As an example, power plant 1800 can be located downstream of transmission constraints, close to the power consumption end. In such a power plant instance 1800 located downstream, LODES system 1504 can have a duration of 24 hours to 500 hours, and can undergo one or more full discharges a year to support peak power consumption when transmission capacity is insufficient to serve users. In addition, in such a power plant instance 1800 located downstream, LODES system 1504 can undergo several shallow discharges (daily or at a higher frequency) to adjudicate the difference between night and daytime electricity prices and reduce the total cost of power service to users. As another example, power plant 1800 can be located upstream of transmission constraints, close to the power generation end. In such an upstream power plant instance 1800, LODES system 1504 can have a duration of 24 hours to 500 hours, and can undergo one or more full charges a year to absorb excess power generation when transmission capacity is insufficient to distribute electricity to users. Furthermore, in such an upstream located power plant example 1800, the LODES system 1504 may undergo shallow charging and discharging several times (daily or more frequently) to balance the difference between nighttime and daytime electricity prices and maximize the output value of the generation facility.

[0393] Example 5A

[0394] The system of Example 5, wherein the LODES system utilizes one or more storage systems of Examples 1, 1A, 1B, 1C, 1D, 1E, 1F, 1G, 1H, 1I, 1J, 1K, 1L, 1M, 1N, 1O, 1P, 1Q, and 1R.

[0395] Example 6

[0396] Fig.19A system example is shown in which one or more aspects of multiple embodiments can be used as part of a large-capacity energy storage system. As a specific example, a large-capacity energy storage system integrating one or more aspects of multiple embodiments can be a LODES system 1504. As an example, the LODES system 1504 can include any of the multiple battery and / or component embodiments described herein (e.g., any of batteries 100, 200, 400, 800, 814, 900, 1000, 1100, 1200, 1300, 1310; pellets 105, 115, 305, 198, 199; system 850, etc.), either alone or in multiple combinations. The LODES system 1504 can be electrically connected to a commercial and industrial (C&I) user 1902, such as a data center, a factory, etc. The LODES system 1504 can be electrically connected to one or more transmission facilities 1506. The transmission facility 1506 can be electrically connected to a power grid 1508. Transmission facility 1506 may receive power from grid 1508 and output the power to LODES system 1504. LODES system 1504 may store the power received from transmission facility 1506. LODES system 1504 may output the stored power to C&I user 1902. In this manner, LODES system 1504 may operate to reshape the power purchased from grid 1508 to match the consumption patterns of C&I user 1902.

[0397] LODES system 1504 and transmission equipment 1506 together can constitute power plant 1900. As an example, power plant 1900 can be located near the power consumption end, that is, near C&I users 1902, such as between power grid 1508 and C&I users 1902. In such an example, LODES system 1504 can have a duration of 24 hours to 500 hours, and can purchase electricity from the market to charge LODES system 1504 when electricity is cheaper. LODES system 1504 can then discharge to provide electricity to C&I users 1902 when the market price is expensive, thereby offsetting the market purchase of C&I users 1902. As an alternative configuration, power plant 1900 can be located between renewable electric energy (e.g., PV power plant, wind power plant, etc.) and transmission facilities 1506 that can be connected to the renewable energy, rather than between power grid 1508 and C&I users 1902. In such an alternative example, the LODES system 1504 can have a duration of 24 hours to 500 hours, and the LODES system 1504 can be charged when renewable output is available. The LODES system 1504 can then be discharged to provide renewable generated electricity to the C&I user 1902, thereby meeting part or all of the electricity needs of the C&I user 1902.

[0398] Example 6A

[0399] The system of Example 6, wherein the LODES system utilizes one or more storage systems of Examples 1, 1A, 1B, 1C, 1D, 1E, 1F, 1G, 1H, 1I, 1J, 1K, 1L, 1M, 1N, 1O, 1P, 1Q, and 1R.

[0400] Example 7

[0401] Fig. 20A system example is shown in which one or more aspects of multiple embodiments can be used as part of a large-capacity energy storage system. As a specific example, a large-capacity energy storage system integrating one or more aspects of multiple embodiments can be a LODES system 1504. As an example, the LODES system 1504 can include any of the multiple battery and / or component embodiments described herein (e.g., any of batteries 100, 200, 400, 800, 814, 900, 1000, 1100, 1200, 1300, 1310; pellets 105, 115, 305, 198, 199; system 850, etc.), either alone or in multiple combinations. The LODES system 1504 can be electrically connected to a wind farm 1502 and one or more transmission facilities 1506. The wind farm 1502 can be electrically connected to the transmission facility 1506. The transmission facility 1506 can be electrically connected to a C&I user 1902. The wind farm 1502 can generate electricity, and the wind farm 1502 can output the generated electricity to the LODES system 1504 and / or the transmission facility 1506. The LODES system 1504 can store the electricity received from the wind farm 1502. The LODES system 1504 can output the stored electricity to the transmission facility 1506. The transmission facility 1506 can output the electricity received from one or both of the wind farm 1502 and the LODES system 1504 to the C&I user 1902. The wind farm 1502, the LODES system 1504, and the transmission facility 1506 together can constitute the power plant 2000, which can be a combined power generation, transmission, and storage system. The electricity generated by the wind farm 1502 can be directly fed to the C&I user 1902 through the transmission facility 1506, or can be first stored in the LODES system 1504. In some cases, the electricity supplied to C&I users 1902 comes entirely from LODES system 1504, or from a combination of wind farm 1502 and LODES system 1504. LODES system 1504 can be used to reshape the electricity generated by wind farm 1502 to match the consumption pattern of C&I users 1902. In one such example, LODES system 1504 can have a duration of 24 hours to 500 hours, and can be charged when the renewable power generation of wind farm 1502 exceeds the load of C&I users 1902. Then when the renewable power generation of wind farm 1502 is insufficient to meet the load of C&I users 1902, LODES system 1504 can discharge, thereby providing C&I users 1902 with a reliable renewable spectrum that offsets part or all of the electricity consumption of C&I users 1902.

[0402] Example 7A

[0403] The system of Example 7, wherein the LODES system utilizes one or more storage systems of Examples 1, 1A, 1B, 1C, 1D, 1E, 1F, 1G, 1H, 1I, 1J, 1K, 1L, 1M, 1N, 1O, 1P, 1Q, and 1R.

[0404] Example 8

[0405] Fig.21An example of a system is shown in which one or more aspects of multiple embodiments can be used as part of a bulk energy storage system. As a specific example, a bulk energy storage system integrating one or more aspects of multiple embodiments can be a LODES system 1504. As an example, the LODES system 1504 can include any of the multiple battery and / or component embodiments described herein (e.g., any of batteries 100, 200, 400, 800, 814, 900, 1000, 1100, 1200, 1300, 1310; pellets 105, 115, 305, 198, 199; system 850, etc.), either alone or in a plurality of combinations. The LODES system 1504 can be part of the power plant 2100 for integrating large amounts of renewable power generation into a microgrid, and coordinate the output of renewable power generation such as the PV power plant 1602 and the wind power plant 1502 with existing thermal power generation such as the thermal power plant 2102 (e.g., a gas-fired power plant, a coal-fired power plant, a diesel generator set, etc., or a combination of thermal power generation methods), and the renewable power generation and thermal power generation supply the C&I user 1902 load with high availability. A microgrid, such as a microgrid consisting of the power plant 2100 and the thermal power plant 2102, can provide 90% or higher availability. The power generated by the PV power plant 1602 and / or the wind power plant 1502 can be fed directly to the C&I user 1902, or can be stored in the LODES system 1504 first. In some cases, the power supplied to C&I user 1902 may come entirely from PV plant 1602, entirely from wind plant 1502, entirely from LODES system 1504, entirely from thermal plant 2102, or from any combination of PV plant 1602, wind plant 1502, LODES system 1504, and / or thermal plant 2102. As an example, LODES system 1502 of power plant 2100 may have a duration of 24 hours to 500 hours. As a specific example, C&I user 1902 load may have a peak of 100 MW, LODES system 1504 may have a rated power of 14 MW and a duration of 150 hours, the cost of natural gas may be $6 per million British thermal units (MMBTU), and the renewable penetration may be 58%. As another specific example, the load of C&I user 1902 may have a peak of 100 MW, LODES system 1504 may have a rated power of 25 MW and a duration of 150 hours, the cost of natural gas may be $8 / MMBTU, and the renewable penetration may be 65%.

[0406] Example 8A

[0407] The system of example 8, wherein the LODES system utilizes one or more storage systems of examples 1, 1A, 1B, 1C, 1D, 1E, 1F, 1G, 1H, 1I, 1J, 1K, 1L, 1M, 1N, 1O, 1P, 1Q, and 1R.

[0408] Example 9

[0409] Fig. 22 An example of a system is shown in which one or more aspects of multiple embodiments can be used as part of a bulk energy storage system. As a specific example, a bulk energy storage system integrating one or more aspects of multiple embodiments can be a LODES system 1504. As an example, the LODES system 1504 can include any of the multiple battery and / or component embodiments described herein (e.g., any of batteries 100, 200, 400, 800, 814, 900, 1000, 1100, 1200, 1300, 1310; pellets 105, 115, 305, 198, 199; system 850, etc.), either alone or in a plurality of combinations. LODES system 1504 can be used to augment nuclear power plant 2202 (or other inflexible power generation facilities, such as thermal power generation facilities, biomass power generation facilities, etc., and / or any other type of power plant with a ramp rate of less than 50% of rated power and a high capacity factor of 80% or more within an hour) to increase the flexibility of the combined output of power plant 2200 consisting of the combined LODES system 1504 and nuclear power plant 2202. Nuclear power plant 2202 can operate at a high capacity factor and the highest efficiency point, while LODES system 1504 can charge and discharge to effectively reshape the output of nuclear power plant 2202 to match user power consumption and / or the market price of electricity. As an example, the LODES system 1502 of power plant 2200 can have a duration of 24 hours to 500 hours. In a specific example, nuclear power plant 2202 can have a rated output of 1000MW, and nuclear power plant 2202 can be forced into a long period of minimum stable power generation, or even shut down due to low market prices for electricity. The LODES system 1502 can avoid shutting down facilities and charge when market prices are low; and the LODES system 1502 can subsequently discharge and increase total generation output when market prices increase.

[0410] Example 9A

[0411] The system of example 9, wherein the LODES system utilizes one or more storage systems of examples 1, 1A, 1B, 1C, 1D, 1E, 1F, 1G, 1H, 1I, 1J, 1K, 1L, 1M, 1N, 1O, 1P, 1Q, and 1R.

[0412] Example 10

[0413] Fig.23 A system example is shown in which one or more aspects of multiple embodiments can be used as part of a large-capacity energy storage system. As a specific example, a large-capacity energy storage system integrating one or more aspects of multiple embodiments can be a LODES system 1504. As an example, the LODES system 1504 can include any of the multiple battery and / or component embodiments described herein (e.g., any of batteries 100, 200, 400, 800, 814, 900, 1000, 1100, 1200, 1300, 1310; pellets 105, 115, 305, 198, 199; system 850, etc.), either alone or in combination. The LODES system 1504 can operate in series with the SDES system 2302. The LODES system 1504 and the SDES system 2302 together can constitute a power plant 2300. As an example, the LODES system 1504 and the SDES system 2302 can be jointly optimized, whereby the LODES system 1504 can provide multiple services, including long-term backup and / or across multi-day fluctuations (e.g., multi-day fluctuations in market pricing, renewable power generation, power consumption, etc.), and the SDES system 2302 can provide multiple services, including fast auxiliary services (e.g., voltage control, frequency regulation, etc.) and / or through daytime fluctuations (e.g., daytime fluctuations in market pricing, renewable power generation, power consumption, etc.). The SDES system 2302 can have a duration of less than 10 hours and an energy conversion efficiency of greater than 80%. The LODES system 1504 can have a duration of 24 hours to 500 hours and an energy conversion efficiency of greater than 40%. In one such example, the LODES system 1504 can have a duration of 150 hours and support the power consumption of users with insufficient renewable power generation for up to a week. The LODES system 1504 can also support the power consumption of users during daytime power generation shortage events, enhancing the capabilities of the SDES system 2302. In addition, the SDES system 2302 can provide power to users during daytime undergeneration events and provide power regulation and quality services, such as voltage control and frequency regulation.

[0414] Example 10A

[0415] The system of example 10, wherein the LODES system utilizes one or more storage systems of examples 1, 1A, 1B, 1C, 1D, 1E, 1F, 1G, 1H, 1I, 1J, 1K, 1L, 1M, 1N, 1O, 1P, 1Q, and 1R.

[0416] Example 11

[0417] A non-limiting example according to an embodiment of the present invention was established and tested. An electrochemical cell using direct reduced iron (DRI) pellets was assembled and tested. The DRI pellets have the properties listed in Table 4 as characterized by the aforementioned method. The electrochemical cell is a cylindrical cell with three electrodes (working electrode, counter electrode and reference electrode) and is filled with a liquid electrolyte. The electrolyte formula is 5.5M KOH+0.5M LiOH+10mM Na2S. The counter electrode is a NiO / NiOOH electrode obtained from a commercially available Fe / Ni (Edison type) cell. The reference electrode is a Hg / HgO (MMO) electrode filled with a 5.5M KOH+0.5MLiOH solution. A stainless steel hose clamp is used to make electrical contact with the DRI pellets. Fig.24A The voltage of the DRI electrode relative to the MMO reference electrode during the first electrochemical discharge cycle (oxidation of DRI) is shown as the discharge specific capacity (mAh / g) when cycled at a specific current of 5 mA / g. DRI ) function.

[0418] Table 4

[0419] Granule shape ball Total Fe content of pellets (wt%) 88.6 <![CDATA[Agglomerate contains SiO2 (wt%)]]> 6.1 <![CDATA[Agglomerate contains Al2O3 (wt%)]]> 0.2 Granules containing MgO (weight %) 0.4 CaO content in pellets (wt%) 0.5 <![CDATA[TiO2 content in aggregates (wt%)]]> 0.01 <![CDATA[Agglomerate contains Fe2C (wt%)]]> 0.2 Metallization (%) 89.4 Electrode volume density (g / cc) 2.45 Apparent density of pellets (g / cc) 6.35 Actual density of pellets (g / cc) 6.54 <![CDATA[Minimum d 孔,90%体积 (micrometers)]]> 2.72 <![CDATA[Minimum d 孔,50%表面积 (micrometers)]]> 5 <![CDATA[Specific surface area of the aggregates (m 2 / g)]]> 0.22

[0420] Example 12

[0421] Another non-limiting example according to an embodiment of the present invention was established and tested. Ten (10) electrochemical cell groups using direct reduced iron (DRI) pellets were assembled and tested. The DRI pellets had the properties listed in Table 4 as characterized by the aforementioned method. The electrochemical cell was a cylindrical cell with three electrodes (working electrode, counter electrode and reference electrode), and the cell was filled with a liquid electrolyte. The electrolyte formula was 5.5M KOH+0.5M LiOH+10mM Na2S. The counter electrode was a NiO / NiOOH electrode obtained from a commercially available Fe / Ni (Edison type) cell. The reference electrode was a Hg / HgO (MMO) electrode filled with a 5.5M KOH+0.5M LiOH solution. A stainless steel hose clamp was used to make electrical contact with the DRI pellets. The DRI was electrochemically cycled according to the following conditions: 1) precharged at a specific current of 25 mA / g for 60 min; 2) discharged at a specific current of 25 mA / g to 0 voltage relative to MMO; 3) charged at a specific current of 25 mA / g and terminated at coulombic limit with a total charge equal to the first discharge capacity in mAh. Fig. 24B The specific capacity (mAh / gDRI) of the DRI electrode is shown versus the cycle number for the group of cells. The average capacity of all cells is plotted along with error bars representing 95% confidence intervals. Fig.24C The coulombic efficiency (CE) of the same DRI cells is shown.

[0422] Example 13

[0423] In another non-limiting example, a spherical DRI pellet bed was tested in a cylindrical cell. The DRI pellets had the properties listed in Table 4 as characterized by the aforementioned method. The mass of the pellet bed was 251.86 g. The electrolyte formula was 5.5 M KOH + 0.5 M LiOH + 60 mM Na2S, and the volume of the electrolyte used was 348 mL. The counter electrode was a stainless steel mesh (100×100 mesh). A Hg / HgO (MMO) reference electrode with a 5.5 M KOH + 0.5 M LiOH filling solution was used to measure the anode potential. A stainless steel porous plate was used as the current collector for the DRI pellet bed, and a stainless steel plate was used as the counter electrode current collector. The cell was charged and discharged with a specific current of 5 mA / g. Fig.24D Shown is the voltage as a function of the discharge specific capacity (mAh / gDRI) of the DRI electrode relative to the MMO reference.

[0424] The above method description is provided only as an exemplary embodiment and is not intended to require or indicate that the steps of multiple embodiments must be performed in the order presented. As will be appreciated by those skilled in the art, the order of steps in the above embodiments can be performed in any order. Words such as "thereafter", "then", "next", etc. are not necessarily intended to limit the order of steps; these words can be used to guide the reader in the description of the method. In addition, any reference to a claim element in the singular form, such as the use of the article "a", "an", or "the", should not be construed as limiting the element to the singular form. In addition, any step of any embodiment described herein can be used in any other embodiment.

[0425] The foregoing description of the disclosed aspects is provided to enable any person skilled in the art to make or use the present invention. Multiple modifications to these aspects will be apparent to those skilled in the art, and the general principles defined herein may be applied to other aspects without departing from the scope of the present invention. Therefore, the present invention is not limited to the aspects shown herein, but conforms to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A battery comprising: a first electrode; Electrolytes; as well as a second electrode; wherein the first electrode comprises a direct reduced iron ("DRI") pellet, and wherein the pellet comprises from 1 wt % to 5 wt % of a silica-containing compound, by elemental mass, based on the total mass of the pellet.

2. The battery of claim 1, wherein the pellet comprises at least 60 wt% iron by elemental mass, based on the total mass of the pellet.

3. The battery of claim 1, wherein: The pellets include at least 60% by weight of metallic iron based on the total mass of the pellets; The average particle size of the granules is 4 mm to 20 mm; and The pellets account for at least 60% of the total mass of the first electrode.

4. The battery of claim 1, wherein the DRI comprises at least one of iron ore, direct reduction grade iron ore, reduced taconite, wüstite, magnetite, hematite, cementite, or iron oxide.

5. The battery of claim 1, wherein the pellets have an average internal porosity of 10% to 90% by volume.

6. The battery of claim 1, wherein the pellets have a range of 0.19 m 2 / g to 18m 2 / g average specific surface area.

7. The battery of claim 1, wherein the pellets have a volume weighted average pore size ranging from 1 micron to 10 microns.

8. The battery of claim 1, wherein the first electrode has a thickness greater than 0.1 cm.

9. The battery of claim 1, wherein the pellets are spherical and have an average diameter ranging from 0.5 mm to 10 cm.

10. The battery of claim 1, wherein the pellet comprises greater than 0.5 wt% of a silica-containing compound based on the total weight of the pellet.

11. The battery of claim 1, wherein the first electrode comprises a single layer of the particles or multiple layers of the particles.

12. The battery of claim 1, wherein the electrolyte penetrates between the pellets.

13. The battery of claim 1, further comprising a current collector electrically connected to the pellet.

14. The battery of claim 1, wherein the agglomerates are sintered iron agglomerated particles.

15. The battery of claim 1, wherein: The pellets are packed in a bed so that macropores are created between two or more pellets in contact with each other; as well as Each of the pellets includes micropores on its respective outer surface.

16. The battery of claim 15, wherein the pellets are fused together.

17. The battery of claim 1, wherein each of said pellets comprises micropores on its respective outer surface.

18. The battery of claim 1, wherein the first electrode further comprises additive particles comprising Bi2O3.

19. The battery of claim 1, wherein the first electrode further comprises additive pellets comprising FeS, FeS2, Na2S, or a combination thereof.

20. The battery of claim 1, wherein the first electrode further comprises a layer of iron powder configured to form an interface between the pellet and a current collector of the battery.

21. The battery of claim 1, further comprising a monitoring system configured to monitor a state of charge (SOC) and / or a state of health of at least one of the first electrode and the second electrode.

22. The battery of claim 21, wherein the monitoring system comprises one or more sensors connected to a controller.

23. The battery of claim 22, wherein the one or more sensors are selected from the group consisting of a strain gauge, a Mossbauer spectrometer, a CCD detector, an ultrasonic transducer, an ion sensing electrode, a thermocouple, and a gas sensor.

24. The battery of claim 1, wherein said first electrode is a composite metal electrode comprising a mixture of said particles and a conductive material dispersed between individual said particles.

25. The battery of claim 24, wherein the conductive material comprises one or more conductive fibers, one or more wires, one or more grids, and / or one or more sheets.

26. The battery of claim 1, wherein the first electrode is a negative electrode.

27. The battery of claim 1, further comprising an additive delivery system configured to add one or more additives to the electrolyte.

28. The battery of claim 27, wherein the additive delivery system delivers liquid additives or solid additives.

29. The battery of claim 27, wherein the one or more additives comprise a salt.

30. The battery of claim 29, wherein the salt is a carbonate or a polysulfide salt.

31. The battery of claim 27, wherein the one or more additives include a sulfur-based additive.

32. The battery of claim 27, wherein the one or more additives include a surfactant additive.

33. The battery of claim 27, wherein the one or more additives are configured to mitigate self-discharge and / or inhibit hydrogen evolution reactions.

34. The battery of claim 1, wherein the first electrode is under a compressive force.

35. The battery of claim 1, wherein the first electrode comprises an additional conductive material.

36. The battery of claim 35, wherein the additional conductive material surrounds the DRI pellets.

37. The battery of claim 35, wherein the additional conductive material is a foil, sheet, mesh or wire.

Citation Information

Patent Citations

  • Method for the manufacture of iron-containing sintered electrodes

    US4236927A